Analytical solution for a circular shield tunnel with ground-lining interaction considering gravity and non-uniform deformation - Jinyang Fu; Bo Wang; Haoyu Wang; Xinghua Fang; Junsheng Yang; Jiarui Yin; Xiangyu Chen (European Journal of Environmental and Civil Engineering, 2026)

Sulfate-catalyzed denitrifying anaerobic methane oxidation process mediated by Methanobacterium sp. from digestion sludges - Shibo Fu; Wen-Bo Nie; Xin Tan; Xiaoming Wang; Lili Li; Guo-Jun Xie (Water Research, 2026)

Decoding and exploiting intratumoral microbiota: from microenvironment modulation to clinical intervention - Hongyuan Zhang; Xuehua Zhang; Jianran Guo; Xuefang Huang; Meng An; Yongna Qiao; Song Wang; Bo Fu (Molecular Biology Reports, 2026)

Dual-scale flower detection and homography-guided cluster matching for robotic pollination in trellised kiwifruit orchards - Leilei He; Bo Jia; Juncai Huang; Rui Li; Spyros Fountas; Longsheng Fu (Biosystems Engineering, 2026)

Mechanism and parametric analysis on cooperative seismic mitigation of base-isolated structures equipped with negative stiffness amplifying damper based on a distributed parameter model - Qing Lyu; Xianlei Li; Bo Fu; Liangkun Liu; Zhaoyang Zhang (Soil Dynamics and Earthquake Engineering, 2026)

Endophytic fungi mediate litter decomposition dynamics through microbial interactions and temporal shifts - Yuan-Qi Zhao; Fu-Sen Nan; Xiao-Qian Yang; Jian-Fei Yu; Han-Yue Bi; Si-Jun Duan; Xin-Yue Wang; Tian-Ci Chen; Qin-Jiang Mao; Xiao-Bo Wang (Soil Biology and Biochemistry, 2026)

Sulfate addition enhanced antibiotic resistance in lake sediments by enriching resistant bacteria and promoting the potential of horizontal gene transfer - Jingjing Zhang; Juan Chen; Chao Wang; Peifang Wang; Bingbing Feng; Bo Zhang; Shunqing Zhang; Jingjing Fu (Journal of Environmental Sciences, 2026)

Petrogenesis of the middle Jurassic Luorong syenite and Xishan A-type granite in the southern Qin-Hang belt, South China: Implications for contrasting mixed sources and divergent differentiation pathways - Zheng-Wei Qin; Xi-Yao Li; Wolfgang Siebel; Jian-Ming Fu; Sanzhong Li; You-Yue Lu; Yu-Xiao Yao; Yu-Shuai Yu; Bo Bao (Journal of Asian Earth Sciences, 2026)

Early-life supplementation of bovine Milk Osteopontin prevents adult obesity by elevating succinic acid and acting through its receptor GPR91 - Lan Liu; Yilei Lao; Zixin Zhang; Chenming Lin; Yeqing Zhou; Zhimin Zhang; Bo Lönnerdal; Zhijian Cai; Junfen Fu (Food Research International, 2026)

Multi-scale optimization method for metamaterial plates with compression-torsion coupling inertial amplification - Rui Zhang; Nian Long; Hanlin Fu; Lang Zheng; Bo Zhang; Jian Zhu; Zhenhuan Tian (Engineering Structures, 2026)

Laser pyrolysis of poly(methyl methacrylate) to high-yield and high-purity methyl methacrylate monomer: A solvent- and catalyst-free strategy for chemical recycling - Xu-Zhen Zhu; Guang-Jian He; Meng-Meng Wang; Fu-Lu Chang; Zi-Yang Hua; Hao-Bo Wang; Xuan-Qi Wu; Lun Chen (Chemical Engineering Journal, 2026)

MXene hollow microspheres with tunable sizes and heterostructures for high-efficiency broadband microwave absorption - Yan-Qin Wang; Lin Zhang; Hao Chen; Zi-Hao Wang; Fu-Rong Zeng; Hai-Bo Zhao (Chemical Engineering Journal, 2026)

Hydrological sensitivity and carbon dynamics during the evolution of a crater lake peatland in Northeast China - Yuefeng Li; Bo Ding; Zhengyu Xia; Yuwen Fu; Jingjing Sun; Zicheng Yu (CATENA, 2026)

Hydrology–topography controls on biomass responses of emergent wetland plants to drought and flooding in a Yangtze River-connected floodplain wetland - Jiawei Shi; Kerun He; Lianlian Xi; Yining Xia; Peng' ao Liu; Zenghui Peng; Hui Fu; Guixiang Yuan; Yonghong Xie; Youzhi Li; Bo Ren (CATENA, 2026)

Fate of antibiotic resistance genes during rural domestic wastewater treatment: Anaerobic unit as enrichment hotspot versus aerobic unit as attenuation zone - Bingbing Feng; Juan Chen; Chao Wang; Jingjing Fu; Rong Wang; Jingjing Zhang; Bo Zhang; Cheng Cheng (Bioresource Technology, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Microwave synchronous excitation of strong electric field and electrodeless ultraviolet radiation for effective air disinfection - Ying-Xiang Fu; Yu Chen; Yu-Qing Huang; Zhi-Bo Zhang; Yue-Hao Ma; Hua-Cheng Zhu; Ye Du (ENGINEERING Environment, 2026)

Phthalate esters and microplastics in sediments of Haomeiliao Wetland, Southwestern Taiwan: Occurrence, spatial distribution, and management implications - Aila Marie Bandola; Ming-Huang Wang; Bo-Fu Guo; Kristopher Ray S. Pamintuan; Chiu-Wen Chen; Cheng-Di Dong (Marine Pollution Bulletin, 2026)

Decadal gelatinization and phenological advancement of small jellyfish in Laizhou Bay, Bohai Sea - Ping Fu; Shan Sun; Huichao Jiang; Jianlong He; Ling Cheng; Bo Su; Hongyan Xing; Yuanqing Ma; Lijuan Liu; Yuting Zhao; Juan Zhang; Xiaowen Zhang (Marine Pollution Bulletin, 2026)

A salt-tolerant dual-network hydrogel based on tea waste biochar for efficient seawater desalination - Kun-Xiu Liu; Yi-Bin Li; Lei Xu; Cai-Hua Liu; Zhu-Long Yu; Wen-Bo Guo; Ming-Lai Fu; Baoling Yuan (Journal of Environmental Chemical Engineering, 2026)

Integrated photoelectrocatalytic reduction and oxidation processes to achieve efficient degradation of fluoxetine in pharmaceutical wastewater - Yanpeng Liu; Zixiao Zhu; Miao Ren; Jingyi Fu; Bo Yang; Xu Zhao (Journal of Environmental Sciences, 2026)

Visualization analysis of sediment provenance in the Upper Triassic Xujiahe Formation, Northeastern Sichuan Basin, China: Implications for spatiotemporal evolution of the basin–orogen system - Shangshang Bo; Yetong Wang; Guoqiang Sun; Kairui Chen; Shuang Fu (Global and Planetary Change, 2026)

Diversity of Diaporthe species associated with post-harvest decay on kiwifruit in China - Lu Feng; Yang Lin; Chao Li; Jiatao Xie; Jiasen Cheng; Bo Li; Tao Chen; Daohong Jiang; Yanping Fu (Fungal Biology, 2026)

A dynamic DNA nanoconstruct-integrated hydrogel: Reprogramming osteoimmune for diabetic bone defect repair - Mei Zhang; Xiao Fu; Zhen Zhao; Yiliu Zhou; Jiahui Xiong; Bo Huang; Yao He; Zhiqiang Liu; Yunfeng Lin (Chemical Engineering Journal, 2026)

Efficient fractionation of reed biomass by inorganic salt-driven seawater/ethanolamine pretreatment for fermentable sugars and N-containing lignin - Hao Tong; Meizhen Jiao; Bo Mu; Bin Li; Shihao Su; Yehan Tao; Jinwen Hu; Jian Du; Jie Lu; Chenglong Fu; Haisong Wang (Chemical Engineering Journal, 2026)

Waste akebiae trifoliata-derived WO3 hierarchical tubes efficient detection of ppb-level triethylamine gas at low temperature and application in food freshness detection - Wen-Xiao Li; Jia-Wang Wang; Rui-Long Li; Qiu-Yue Zheng; Bao-Yu Song; Bo-Ya Liu; Li-Xia Zhao; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2026)

Nanoscale interfacial scaffold enables perovskite/silicon tandems with 34% efficiency and an open-circuit voltage over 2.01 V - Huimin Zhang; Qingshui Zheng; Hongbo Mo; Fu Zhang; Zhijie Rao; Linyu Ning; Yue Yin; Dongsheng Yang; Zheng Fang; Lei Ding; Yongcai He; Xixiang Xu; et al. (Science Bulletin, 2026)

Tracing microplastics uptake and translocation in plants using aggregation-induced emission materials - Yang Liu; Siqi Yang; Xia Wang; Wei Du; Nan Fu; Penglin Li; Heng Wei; Fen Zhao; Zijie Qiu; Hao Qiu; Yanxu Zhang; Willie J.G.M. Peijnenburg; et al. (Journal of Hazardous Materials, 2026)

Immunomodulatory potential of okara peptides: Matrix limitation, preparation strategy, structure-activity, and action mechanisms - Bin Liu; Shengyu Zhang; Jiayi Guo; Xue Chen; Biao Yang; Hongling Fu; Bo Lyu; Wendan Jing; Hansong Yu (Trends in Food Science & Technology, 2026)

Vibration energy transfer in track–subgrade systems with frequency-dependent rubber damping pads: A power flow analysis - Jin Chen; Shiyu Gong; Ruiyan Peng; Chengyue Wu; Bo Fu; Deliang Ma (Transportation Geotechnics, 2026)

Urinary biomarkers of emerging contaminants in relation to prevalent Parkinson's disease: An exploratory mixture and network toxicology study - Chiqun Shan; Yiming Ge; Junye Bian; Yuli Lin; Bo Fu; Qinru Xiao; Aihua Guo; Mengyan Li; Pan Xu; Yi Chen; Haobo Chen; Shaoyou Lu (Journal of Hazardous Materials, 2026)

Enhanced PM filtration and self-adaptive oxygen supply by intelligent powered respirators under extreme conditions with high dust and low oxygen - Jintuo Zhu; Wei-Wei Huang; Xuejing Liu; Bo Ren; Yunhui Nie; Dayong Fu; Weihua Zhu; Wenjie Fan; Liang Wang; Yuzhen Hou; Huan Xu (Journal of Hazardous Materials, 2026)

Enhanced atomic hydrogen utilization on ordered Pd1Cu intermetallic single-atom alloy for electrochemical hydrodechlorination - Juening Fan; Yang Liu; Runze Si; Piao Hu; Zhiming Liang; Yangsu Xie; Fu-Kuo Chiang; Maohong Fan; Huihuang Chen; Zhimin Ao; Bo Yang (Journal of Hazardous Materials, 2026)

Multi-objective Optimization Design of the Spiral Deflector in the Air Duct of the Integrated Leaf Manipulation Machine for Northern Fujian Oolong Tea - Chengzhi Ruan; Luxuan Zheng; Xiangfa Fu; Kaiyun Zhang; Jun Yang; Shuyu Xue; Bo Guo; Jiayou Chen (Food and Bioproducts Processing, 2026)

Seismic performance of reinforced concrete columns with asymmetric reinforcement corrosion in tensile and compressive side - Xiaojuan Liu; Haitao Lian; Yong Ye; Bo Fu; Zixiong Guo; Yun Guo (Engineering Structures, 2026)

Novel Streptomyces sp. SCUT-3 promoter’ and 5’UTR chimeras enhanced its alginate lyase expression for kelp degradation - Jun Dai; Hai-Ning Wang; Can Qin; Peng-Bo Dan; Jun-Jin Deng; Lei Wu; Zhi-Wei Li; Fu-Gen Zhang; Chu-Yan Liang; Ming-Shu Zhang; Xiao-Chun Luo (Chemical Engineering Journal, 2026)

Dimethylammonium chloride-assisted antisolvent engineering for high-performance and stable CsPbI3 perovskite solar cells - Tingxing Hu; Zelong Zhang; Wenxi Ji; Qiaoyun Chen; Jianfei Fu; Xiaoting Nie; Lijie Wang; Bin Dong; Yi Zhou; Bo Song (Chemical Engineering Journal, 2026)

Recognition of kiwifruit pruning position based on vine segmentation and dormant bud detection with their planar distribution - Shuolin Kong; Bo Jia; Qichen Huang; Juncai Huang; Rui Li; Bao Zhou; Xiancun Zhou; Zhenchao Wu; Jinyong Chen; Xiaoxu Sun; Dateng Zheng; Davut Karayel; et al. (Computers and Electronics in Agriculture, 2026)

Semi-permeable membrane coverage accelerates composting through modulated bacterial succession and organic matter transformation - Fu-Sheng Sun; Chao Wang; Nader Mohamed; Lin Shi; Bo-Hao Yin; Yue-Bing Sun; Guang-Hui Yu (Waste Management, 2026)

Apelin-12 ameliorates diabetic nephropathy via p53/JAM-A axis-mediated preservation of glomerular endothelial integrity - Yuhong Fu; Yue Liu; Bo Huang; Jingqiu Cui (Tissue and Cell, 2026)

Retraction notice to “Rapid transition of aerosol optical properties and water-soluble organic aerosols in cold season in Fenwei Plain” [Sci. Total Environ. 829 (2022) 154661] - Aodong Du; Yan Li; Jiaxing Sun; Zhiqiang Zhang; Bo You; Zhijie Li; Chun Chen; Jie Li; Yanmei Qiu; Xingang Liu; Dongsheng Ji; Wenjie Zhang; et al. (Science of The Total Environment, 2026)

Paleoproterozoic protracted collisional orogeny: Insights from the Wutai Complex in the central North China Craton - Fengyu Qi; Bo Huang; Xiaoxue Shan; Dong Fu (Precambrian Research, 2026)

Proteomic insights into the combined effects of near-threshold bleaching temperature and prometryn exposure on the coral Galaxea fascicularis - Sichen Li; Yanyu Zhou; Haochen Niu; Weilu Kang; Guowei Fu; Bo Hu; Hongwei Zhao (Marine Environmental Research, 2026)

Corrigendum to ‘Wavelength-dependent photobiomodulation attenuates synovial inflammation in fibroblast-like synoviocytes and a collagenase-induced osteoarthritis model’ [Journal of Photochemistry & Photobiology B: Biology Volume 272 (2025) 113276] - Tianxiang Fan; Peng Xia; Safayet Ahmed; Yuen H. Tsang; Zhi Yao; Deli Wang; Ziyu Chen; Lixiang Xue; Dongquan Shi; Bo Wang; Chi Fai Cheung; Marco Y.C. Pang; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

High-throughput computational screening coupled with experimental validation for designing low-viscosity deep eutectic solvents toward 1,2-Dichloroethane capture - Xiaomeng Chen; Wenfei Guo; Zekai Jin; Yongzhen Fu; Gang Zhang; Muhua Chen; Xinbao Zhu; Meisi Chen; Bo Fu (Journal of Hazardous Materials, 2026)

Rhamnolipid@Ag bio-nanofluids for enhanced oil recovery: Multiscale experimental and molecular mechanism elucidation - Yuxiao Han; Shuyuan Deng; Jian Fu; Bo Wang; Jie Gao; Ming Nie; Qijun Wu; Yuehui She; Fan Zhang (Journal of Cleaner Production, 2026)

Constructing Fe3N/MnO heterojunction via heteroatom doping for degrading dye wastewater by heterogeneous electro-fenton system - Yi Wang; Yunliang Fan; Xiaocong Liu; Fuping Zhang; Hangdao Qin; Bo Xing; Xingyong Liu; Chaoting Fu; Yan Luo; Guo Yang; Ning Gou (Journal of Environmental Sciences, 2026)

Multi-responsive and pressure-sensing soft actuator based on MXene/PDMS bilayer film with micro-ridge structures - Bo Ma; Sheng-Bo Sang; Pu Song; Jia-Hui Zhang; Qian Zhao; Hong-Tao Wang; Hui Gao; Xiu-Yan Fu; Zheng-Xiao Wang; Jia-Nan Ma (Chemical Engineering Journal, 2026)

Phosphorus–boron synergistic carbonization/dormancy strategy enables polyurethane foams with aging enhanced fire safety - Shuang Li; Hai-Bo Zhao; Ming-Jun Chen; Lei He; Lin Zhang; Fu-Rong Zeng; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

Analysis of meteorological causes for a spring PM10 pollution episode over Hainan Island, China - Chuan-bo Fu; Li Dan; Jia-xiang Tang; Jin-he Tong (Atmospheric Research, 2026)

Autofocusing-based adaptive SAR pixel offset tracking for high-accuracy landslide deformation retrieval - Menghua Li; Ying Liu; Dong Fan; Mengshi Yang; Weitao Tian; Zhitao Fu; Bo-Hui Tang (Landslides, 2026)

A CNN–Transformer hybrid network for efficient cross-region landslide detection by transfer learning - Zijin Fu; Fawu Wang; Junfei Zhong; Filippo Catani; Jie Dou; Qi You; Bo Zhang (Landslides, 2026)

Non-fickian CO2CH4 transport in carbonate composite cores analyzed with fractional-order model and in-situ NMR characterization - Miao Zhang; Lianlin Deng; Bo Ning; Jianlin Guo; He Yuan; Ninghai Fu; Luis F. Ayala (Advances in Water Resources, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Experimental study on the configuration inversion method for flexible pipes - Wen-hua Wang; Chuang Liu; Lei Wang; Xin Lv; Yi-ming Zhang; Zhi-fu wang Yang; Hao Yang; Lei-lei Dong; Gang Liu; Ying-ying Wang; Hai-bo Sun (Ocean Engineering, 2026)

Elucidating soil dissolved organic nitrogen mineralization across soil depths under contrasting fertilizer-application intensities using FT-ICR MS and a two-component model - Ke Yang; Zhuqing Jiang; Hui Peng; Jia Xin; Bo Guo; Zeliang Shen; Yujiao Fu; Tianyuan Zheng (Journal of Hazardous Materials, 2026)

Soil stabilization using in-situ polymer cross-linking driven by freeze-thaw cycles - Jining Zhang; Xiangjun Pei; Jiaxing Zhang; Guanlan Fu; Bo Qin; Yinhao Liao; Lihong Zhou (Journal of Cleaner Production, 2026)

Biochar-assisted copper removal and metabolic responses of Hydrocotyle vulgaris in a hydroponic system: Insights from untargeted metabolomics and computational modeling - Ziyi Lian; Xiaofan Fu; Haoran Yin; Yuxin Li; Lei Zhao; Jing Shang; Tian Gao; Bo Zhang; Chengbin Xu; Runjie Zhang; Fang Ma; Jieting Wu (Journal of Environmental Management, 2026)

2D3D-SPMatch: cross-modal geometric consistency based on spatial perception for detector-free image and point cloud matching - Yashuai Ji; Zhitao Fu; Han Nie; Bin Luo; Bo-Hui Tang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Contrasting mechanical evolution of bakken shale under hydrous and anhydrous pyrolysis: A nanoindentation-based assessment - Mengdi Sun; Jiajun Fu; Yeping Ji; Yiquan Ma; Bo Liu; Qiuli Huo; Aydin Larestani; Abdolhossein Hemmati-Sarapardeh; Mehdi Ostadhassan (International Journal of Rock Mechanics and Mining Sciences, 2026)

Conserved roles of core morphogens in wing formation of the antlion Myrmeleon bore - Wei Dong; YaNan Li; Qiongqiong Zhang; Yuejun Fu; Xu-Bo Zhang (Insect Biochemistry and Molecular Biology, 2026)

Metabolic basis of quality deterioration in soybean variety Heihe 43 driven by storage time: Based on non-targeted metabolomics - Xue Chen; Bohan An; Junjie Gao; Xintong Jiang; Bin Liu; Hansong Yu; Hongling Fu; Bo Lyu; Wendan Jing; Sainan Wang (Food Research International, 2026)

Glucosamine sulfate as a dietary supplement in alleviating nicosulfuron-induced ovarian injury - Yafei Miao; Jiali Xu; Jiaqi Chen; Junheng Zhang; Yehai Fu; Ying Yang; Bo Zhou; Ziyang Li; Huan Liu; Yong Ruan (Food Bioscience, 2026)

A review of early Paleozoic subduction-accretion tectonics in the North Qilian Orogenic Belt, Northeastern Tibet: Implications for the evolution of the Proto-Tethys Ocean - Dong Fu; Bo Huang; Timothy Kusky; Simon A. Wilde; Fengyu Qi; Xiaoxue Shan; Yilin Qu; Hong Wang (Earth-Science Reviews, 2026)

Indium-doped CuSnO3 perovskite hybrids for chemiresistive CO sensing - Linyan Gu; Yangtao Qian; Yiting Liu; Miao Cheng; Tao Wei; Qianqian Liu; Ruirui Wang; Wanfei Li; Zhenxiao Fu; Haiyang Jiang; Zibo Li; Bo Liu; et al. (Chemical Engineering Journal, 2026)

Continuous shrub expansion enhances soil water retention and plant-available water of alpine meadows in the Qinghai-Tibetan Plateau - Ruiyu Fu; Qiaoyan Chen; Junna Feng; Bo Fan; Yangong Du; Licong Dai; Zhongmin Hu; Xiaowei Guo (CATENA, 2026)

Ferroptosis mediated by aggregation of Triosephosphate isomerase 1 links cadmium exposure to pulmonary fibrosis - Yishan Yin; Xuehan Jiang; Jiayi Li; Hongxue Yang; Yi Fang; Bo Li; Hongyu Fu; Jingzeng Cai; Ziwei Zhang (Chemico-Biological Interactions, 2026)

Context-dependent links between microbial co-occurrence topology and nitrogen mineralization in two adjacent subalpine Picea asperata stands - Lixia Wang; Haoying Gao; Shuangjia Fu; Lin Xu; Li Zhang; Han Li; Chengming You; Sining Liu; Hongwei Xu; Jiao Li; Bo Tan; Zhenfeng Xu (Plant and Soil, 2026)

Canonical Wnt pathway mediates catalpol-induced epithelial differentiation of porcine metanephric mesenchymal cells - Pengcheng Ji; Yuansheng Xie; Guangrui Geng; Wenkai Guo; Jingru Bi; Bing Han; Xu Wang; Bo Fu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Homocysteine-induced bone formation dysfunction reversed by icariin via the AKT/FOXO1 signaling pathway - Suzhen Chao; Yunying Fu; Xinyi Peng; Yili Zhou; Junjie Xia; Ming Chen; Yang Li; Shengyuan Li; Min Shi; Xunli Xia; Bo Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Metamorphism and chronology of Neoproterozoic granulite facies metasedimentary rock in northwestern Yangtze Block and its tectonic implications - Linfeng Feng; Haozheng Wang; Byung Choon Lee; Jinghao Fu; Yi Zhang; Heng Liu; Meimei Han; Bo Hu; Xiahong Cui; Mingguo Zhai (International Geology Review, 2026)

Seismic dynamic response and sensitivity analysis of high-speed railway catenary systems under multidirectional excitations and traveling wave effects - Jin Chen; Qing-Bing Wan; Hao-Lin Xin; Bo Fu; Deliang Ma (Bulletin of Earthquake Engineering, 2026)

Monoterpenoids from the roots of Paeonia lactiflora Pall. and their neuroprotective activity - Bo Fu; Yi-Qiang Zhang; Jin-Ling Zhang; Si-Yi Wang; Jia-Tong Wu; Juan Pan; Wei Guan; Zhi-Chao Hao; Qing-Shan Chen; Li-Li Zhang; Hai-Xue Kuang; Yan Liu (Natural Product Research, 2026)

HSPA1A-BAG5 chaperone complex promotes spermatogenesis by driving ubiquitination-mediated degradation of ATF2 - Peng Yi; Bo Peng; Ying Cao; Xianghong Fu (Tissue and Cell, 2026)

Polystyrene nanoplastics disrupt iron homeostasis by promoting FPN1 ubiquitination in GC-2spd(ts) cells - Xinru Cui; Yitong Shang; Liyang Ding; Zhen Zhang; Yu Deng; Tengjiao He; Bo Xu; Xufeng Fu; Xing Du; Hang Han (Toxicology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Chemical constituents from the stem of Nauclea officinalis and their anti-inflammatory activities - Bo Wen Wan; Ting Wang; Xiong Bo Zhu; Rui Hua Xu; Hao Fu Dai; Wen Li Mei; Fei Wu; Xiao Ying Peng; Sheng Zhuo Huang (Phytochemistry Letters, 2026)

Unveiling colloid-mediated mobilization of Cd/As/Cr by low-molecular-weight organic acids in high geological background soils - Qixian Fu; Zhe Liu; Lijuan Zeng; Zijuan Zhong; Jinfan Chen; Xiongkai Zheng; Han Ye; Xueqin Tao; Quan Chen; Bo Pan; Zhi Dang; Guining Lu (Journal of Hazardous Materials, 2026)

Recyclable hygroscopic hydrogels with dynamic networks enable efficient solar-driven atmospheric water harvesting - Fu-Yao Zhong; Chen-Xi Li; Lu-Bin Zhong; Chao-Yang Guo; George Zheng Chen; Bo Weng; Jun He; Yu-Ming Zheng (Journal of Environmental Chemical Engineering, 2026)

Comparative study on ignition mechanism and intrinsic combustion kinetics between coal and char - Zezheng Shi; Yang Liu; Yongxiao Jia; Jiye Tao; Kuangyu Li; Zhi Wang; Xinyu Wang; Yumin Chen; Bo Yu; Shisen Xu; Dongliang Xu; Xiangping Wang; et al. (Fuel, 2026)

Cryoprotective effect of natural deep eutectic solvent combined with sous-vide cooking treatment on the pre-maturation and freeze-thaw cycle of Penaeus vannamei - Jing-jing Fu; Jie Deng; Bo-yang Tan; Yi-shu Ni; Xiu-ping Dong; Si-min Zhang; Yue-wen Chen (Food Chemistry, 2026)

The Lhasa Terrane: A tale of two origins and its convergence at the Northern Margin of Gondwana - Chang-Sheng Yu; Mei-Fu Zhou; Ming Wang; Jian-Bo Zhou; Wen-Jun Hu (Earth-Science Reviews, 2026)

Molecular dynamics analysis of benzyl alcohol-assisted dyeing mechanisms in plasma-modified meta-aramid fibers - Xintao Yan; Kuang Wang; Feiyang Huang; Zhuangzhuang Sun; Jianli Liu; Yizheng Fu; Bo Zhu (Chemical Engineering Journal, 2026)

Cyclophosphamide-induced iron homeostasis imbalance triggers ovarian toxicity through ferroptosis of ovarian granulosa cells in a mitophagy crosstalk manner - Bo Xu; Xiaoqiang Luo; Tengjiao He; Yu Deng; Yitong Shang; Hang Han; Xufeng Fu (Chemico-Biological Interactions, 2026)

The synergy of active and passive satellite sensors for robust sea-fog detection: A two-stage machine-learning model with constraints from ICOADS - Luyu Yan; Xuehua Fan; Disong Fu; Hongrong Shi; Lin Chen; Bo Li; Zhuhui Jiang; Xiaoqiong Zhen; Xiaoguang Sun; Xiangao Xia (Atmospheric Research, 2026)

Characterization of groundwater discharge in an area of dense salt crust formation in the high-salinity South Huobuxun Lake (NW China) using isotopic and hydrogeochemical analyses - Xinming Song; Fu Liao; Guangcai Wang; Nuan Yang; Xianglong Chen; Bo Li (Hydrogeology Journal, 2026)

Water-saving Effect of Domestic and Industrial Water Pricing Policies Using Nonlinear Fixed-effect Models - Hongwei Cai; Yan Bo; Jin Fu; Jiadi Zou; Zhijian Yu; Wulahati Adalibieke; Jinxia Wang; Yazhen Gong; Feng Zhou (Chinese Geographical Science, 2026)

Data Fusion Framework for a High-Resolution Regional Dataset in the Western North Pacific - Lifu Fu; Chunling Zhang; Yijun Ge; Bo Shu; Ruoxiao Zhou (Journal of Marine Science and Engineering, 2026)
Based on the large volume of observational data obtained from Argo and several satellites, an increasing number of datasets are being developed and applied to oceanographic research. However, there are still problems such as sparse subsurface observations, insufficient parameters, and weak pertinence. This study provides a basic framework for high-resolution data fusion that focuses on the multi-source observations in the Western North Pacific. Multi-source observations from satellites, Argo floats, and historical in situ profiles are fused using a statistical model and a gradient-dependent optimal interpolation method. A daily gridded dataset with a 0.25° horizontal resolution is developed, which includes temperature, salinity, and currents. The results show that the correlation coefficients between the observations and the inverted profiles of temperature and salinity are about 0.99 and 0.94, respectively, with mean root mean square errors of about 1.27 °C and 0.13, respectively. In the Northwest Pacific Ocean, the most suitable parameter settings are a search radius of 1.5° in longitude and latitude, correlation scale constant of 0.25°, and relative observation error of 2. Consequently, the average RMSEs of the fused temperature and salinity fields are 0.43°C and 0.056, respectively. Compared with other reanalysis datasets, the product constructed in this study retains more high-frequency ocean signals, and its temperature error relative to XBT observations is also the smallest. Furthermore, the dataset effectively depicts the characteristics of marine dynamic processes such as the Kuroshio paths and mesoscale eddies.

Two new compounds from the roots of Paeonia lactiflora Pall. and their anti-inflammatory effects - Bo Fu; Jin-Ling Zhang; Jia-Tong Wu; Si-Yi Wang; Yi-Qiang Zhang; Juan Pan; Wei Guan; Zhi-Chao Hao; Hai-Xue Kuang; Qing-shan Chen; Li-Li Zhang; Bing-You Yang; et al. (Natural Product Research, 2026)

Principle analysis and device development of a novel technology for preventing lockset failure and cable bolt ejection - Housheng Jia; Zhiming Zhang; Yanxi Gao; Mengxiong Fu; Guoying Wang; Chao Li; Bo Peng; Wenyuan Jiang (Tunnelling and Underground Space Technology, 2026)

Identification of novel genes involved in pediatric congenital heart disease using trio-based whole genome sequencing - Bo Wang; Mo Li; Wei Zhou; Huiwen Chen; Ying Xiang; Guocheng Shi; Guoling You; Luan Chen; Yesheng Zhang; Xiaoqing Zhang; Yunqian Gao; Lulu Li; et al. (Science Bulletin, 2026)

Extreme load assessment and pitch control strategy for floating wind turbines considering the coupled effects of typhoon stage evolution and yaw error - Xiang Wang; Xu Liang; Peng You; Baoxuan Wang; Yue Chen; Fu Li; Bo Ye; Xianhui Zhu (Ocean Engineering, 2026)

Comparative evaluation of urine, whole blood, and serum as biological matrices for human biomonitoring of neonicotinoid insecticides and metabolites - Yuli Lin; Junye Bian; Kai Lin; Yiming Ge; Chiqun Shan; Bo Fu; Weizhong Chen; Tao Chen; Qinru Xiao; Bingjun Lu; Qunlin Xiao; Shaoyou Lu (Journal of Hazardous Materials, 2026)

Natural and anthropogenic controls on rare earth elements in groundwater: Indicative significance for distinguishing agricultural and urban-industrial impacts - Hang Meng; Guangcai Wang; Fu Liao; Hairu Mao; Bo Li; Fengxia Liu; Xianglong Chen; Hongyu Zhang; Zhiyuan Qiao (Journal of Hazardous Materials, 2026)

Flavor characterization of Chenxiang-type baijiu-Daoguang nianwu aged in wooden Jiuhai with different vintages integrating GC-E-nose, GC-IMS, GC-MS-O, ROAV and chemometrics approaches - Na Wang; Xiangyang Zhang; Li Xue; Zhen Zhang; Li Fu; Xuejiao Ren; Hui Zhang; Bo Zhang; Xiaoyu Jiang; Lili Zhang; Mei Wang (Food Research International, 2026)

Synergistic inhibition of advanced glycation end products and enhancement of flavor by the combination of oligomeric proanthocyanidins and glycated yeast proteins - Jing-jing Fu; Bo-wen Ru; Qi-cheng Zhang; Yu-jun Wu; Hai-yang Feng; Lian-ping Zheng; Yue-wen Chen (Food Research International, 2026)

Decoding the flavor formation mechanism of the functional microbial community in koji-mediated fish sauce - Jin-Xiu Xu; Xin Zhang; Bai-Feng Fu; Zhao-Rui Li; Min-Bo Li; Zhen-Yu Wang; Xian-Bing Xu; Shu-Zhen Cheng; Ming Du (Food Bioscience, 2026)

A pine cone-inspired adaptive hydrogel for sustainable, pH-regulated lithium extraction from brine - Hui-Wen Huo; Qi-Jun Zhang; Peng Wu; Fu-Yao Zhong; Chao-Yang Guo; Bo Weng; Lu-Bin Zhong; Yu-Ming Zheng (Chemical Engineering Journal, 2026)

Multi-level metabolic engineering for efficient ergothioneine production in yeast using a Pleurotus ostreatus-derived pathway - Zhongjuan Di; Yanjun Huo; Yuejun Fu; Bo Li; Yingping Zhuang (Chemical Engineering Journal, 2026)

Calcium selenide as a sacrificial electron donor boosting iron redox cycling for organic pollutant removal via transformation into elemental selenium - Haigang Fu; Shuang Meng; Jingyu Nie; Xinyun Zhang; Zihao Zhang; Yongjian Wang; Jing Zhang; Chuanshu He; Peng Zhou; Bo Lai (Chemical Engineering Journal, 2026)

NAD+ depletion transdifferentiates the gastric stem cells to intestinal goblet cells in patient-derived gastric organoids - Bin Liu; Xiaoyang Zhang; Xia Xue; Fazhan Li; Feifei Ren; Ihtisham Bukhari; Baitong Hu; Xiangdong Sun; Bo Zhang; Yong Yu; Quan Zheng; Wanqing Wu; et al. (Chemical Engineering Journal, 2026)

Influence of puerarin upon mouse hippocampal neurons involved in corticosterone-induced dysfunction - Bo Jiang; Fenyu Fu; Shiqiang Yu; Yinbo Wang; Lei Chen; Zhilong Xiu (In Vitro Cellular & Developmental Biology - Animal, 2026)

Open spatial relation extraction about geological objects with dependency graph network - Deping Chu; Lele Fu; Bo Wan; Fang Fang; Shunping Zhou (Earth Science Informatics, 2026)

Revisiting the Peripheral Nerve Injury and Regeneration - Zhen-Gang Liu; Yun-Long Zou; Min-Xin Zhang; Fan Yang; Peng-Fu Li; Bo-Yin Zhang (NeuroMolecular Medicine, 2026)

The Protective Role of Selenium Against Thyroid Injury in Pigs: Involvement of PINK1/Parkin-Mediated Mitophagy and Apoptosis Regulation - Xuehan Jiang; Yishan Yin; Yi Fang; Hongxue Yang; Hongyu Fu; Bo Li; Xiaoxiao Chen; Bendong Shi; Jingzeng Cai; Ziwei Zhang (Biological Trace Element Research, 2026)

Research on the Support Mechanism of Tunnel Anchor Bolt Based on Physical Model Experiments and Continuous–Discontinuous Theory - Mingyi Wang; Shaobo Chai; Bo Hu; Chen Xu; Jiaming Wu; Yongqiang Zhou; Xiaodong Fu (Rock Mechanics and Rock Engineering, 2026)

Influence of fines content on shear strength and fabric evolution of unbound aggregate base: An experiment and simulation study - Bo Li; Zhengcao Du; Zhenzheng Liu; Jianbing Ma; Zhaoxiang Li; Weiguang Ma; Yunpeng Zhang; Maoyi Fu; Yongping Hu (Transportation Geotechnics, 2026)

Eocene topography differentiation between the western and eastern North China Craton: Insights from multi-method chronometry in the northern Taihangshan Mountains - Li-Xia Feng; Ping-Ping Li; Zeng-Zhen Wang; Rong Ren; Lin Wu; Bo Zheng; Bo Liu; Jian-Qing Ji; Bao-Fu Han (Tectonophysics, 2026)

Novel self-centering damper for seismic resilience: development, modeling, and validation - Beco Chenadaire Lekeufack; Bo Fu; Mabor Achol Samuel (Soil Dynamics and Earthquake Engineering, 2026)

Development of a sporopollenin-hydrogel-Cu2O composite for dye removal: Addressing the dual challenges of agglomeration and ‌embedding of metal nanoparticles in hydrogel-based catalysts - Ying Liu; Jiao Jiao; Qing-Yan Gai; Yi-Bo Qiu; Hong-Yan Zhao; Xiao-Qing Wang; Yu-Jie Fu (Journal of Environmental Sciences, 2026)

Effect of perovskite A-site disorder on its activity in solid-state CO2 electrolysis - Shuo Liu; Lin-Bo Liu; Biao Ouyang; Yan Li; Qinglin Pan; Yifei Sun; Xian-Zhu Fu; Jing-Li Luo; Subiao Liu (Chemical Engineering Journal, 2026)

Synchronous enhancement of radical and non-radical pathways in Fenton-like reaction mediated by CuCo bimetallic heterostructure - Jing Zhang; Yating Fu; Ye Liu; Yi Ren; Xingxing An; Bo Lai (Chemical Engineering Journal, 2026)

Histidine-induced metal coordination distortion enhanced peroxymonosulfate activation for sulfonamides elimination: Emphasising the primacy of electron transfer - Huanhuan Wang; Geng Chen; Zhenhua Wang; Jingshang Xiao; Quanbin Zhang; Huifu Ji; Gang Xue; Bo Fu; Yunjie Wu; Wanzhang Wang (Chemical Engineering Journal, 2026)

Electrochemical aptamer sensor based on nanocomposites composite material for rapid on-site detection of enrofloxacin in aquaculture - Bo Long; Qi Liu; Yizhuan Li; Qiongqiong Xing; Chuxiong Lan; Rui You; Liying Deng; Fangfang Qu; Meng An; Yingchun Fu; Shenghang Zhang; Dapeng Ye; et al. (Chemical Engineering Journal, 2026)

Bisphenols and parabens in soils and outdoor dust from a metropolitan city in the Guangdong–Hong Kong–Macao Greater Bay Area, China: concentrations and human exposure risk - Xulong Chen; Xiujuan Qi; Bingjun Lu; Yuli Lin; Bo Fu; Chiqun Shan; Xiangxuan Kong; Kai Lin; Tingting Zhu; Shaoyou Lu (Environmental Monitoring and Assessment, 2026)

Integrating Cost-Sensitive Ensemble Learning and Geoscience Big Data for Uranium Prospectivity Mapping in the Husab Uranium Deposit, Namibia - Yuan Li; Chen Fu; Yingxu Song; Jiahui Zhang; Yu Li; Bo Liu; Yingcong Huang; Dajun Li (Natural Resources Research, 2026)

Utilization of synthetic minority oversampling technique and transfer learning for improving rice and wheat LAI estimation - Ziheng Feng; Ke Wu; Bo Xu; Haiyan Cen; Yuan Zhang; Xiangtai Jiang; Hanyu Xue; Heguang Sun; Hao Yang; Haikuan Feng; Huiling Long; Xingang Xu; et al. (Computers and Electronics in Agriculture, 2026)

Research on application of modified low-carbon magnesium oxysulfate cement for grouting reinforcement in crushed limestone tunnels - Junfu Fu; Junru Zhang; Ziyan Fan; Bin Li; Huayun Li; Jimeng Feng; Bo Wang; Xiping Ma (Tunnelling and Underground Space Technology, 2026)

Impact of soil compaction and seasonal freeze-thaw cycles on the microstructural evolution and aggregate stability of Mollisol - Boxiang Zhang; Bo Liu; Shuang Li; Juan Fu; Yanfeng Jia; Haoming Fan; Chengjiu Guo; Fangli Su; Renming Ma (Soil and Tillage Research, 2026)

Catalysis-inspired d-band center engineering enables hydrogen-suppressed zinc anodes for long-life aqueous zinc-ion batteries - Chunhui Gao; Zhenjing Jiang; Jie Chen; Kaining Zhang; Huijun Yang; Ruwei Chen; Hang Yang; Qingjin Fu; Zheng Li; Nana Xu; Mengran Wang; Bo Hong; et al. (Science Bulletin, 2026)

High-resolution elastic full-waveform inversion using dual-channel CNN and Kolmogorov–Arnold network - Faxuan Wu; Yang Li; Zhenwu Fu; Bo Han; Yong Chen (Journal of Applied Geophysics, 2026)

Deterioration characteristics of red beds lithological interface under water-rock interaction and its influence on tunnel deformation - Jingkai Qu; Yiguo Xue; Fanmeng Kong; Cuiying Zhou; Jianbing Peng; Su Yan; Zhen Liu; Zhuang Ruan; Mingdong Zang; Kang Fu; Bo Wang; Minghao Jia; et al. (International Journal of Rock Mechanics and Mining Sciences, 2026)

Microbial biosynthesis of fruit-like aroma compounds: Strategies and challenges toward sustainable food flavor production - Yufeng Wang; Junfeng Wu; Nan Wang; Bohai Zhang; Jianxin Dong; Yating Liu; Mingqin Zhao; Bo Fu (Food Research International, 2026)

Dynamic remodeling of intramuscular structural proteins and its impact on abalone muscle quality during post-mortem cold storage - Hua Liu; Tian-Bo Zhang; Fu-Hao Zhang; Le-Chang Sun; Duanquan Lin; Tengchuan Jin; Ling-Jing Zhang; Jia-Yin Huang; Min-Jie Cao; Yu-Lei Chen (Food Chemistry, 2026)

Pre-rainfall vapor pressure deficit stress and sunshine reduction govern sub-seasonal rainfall effects on China’s rice yield - Feng Zhou; Guanghan Tang; Chengjie Wang; Yue Qin; Bo Fu; Jin Fu (European Journal of Agronomy, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

Hydraulic retention time extension and multi-point reflux promote full-scale partial mainstream anaerobic ammonium oxidation (Anammox) at low temperatures - Yang-Guang Xia; Jun-Hong Zhou; Xiao-Li Yang; Wen-Bo Liang; Yu-Jia Fu (Chemical Engineering Journal, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Epidemiology of Isoparorchis eurytremus (Trematoda: Isoparorchiidae) Infection in Southern Catfish (Silurus meridionalis; Siluriformes: Siluridae): A Case Study in the Dongting Lake, China - Dong Liu; Xiangrong Liu; Mingjun Yan; Naige Fu; Wei Wan; Gang Xu; Qianqian Ku; Xin Yang; Bo Hong; Chongrui Wang; Dongsheng Ou; Xiping Yuan (Fishes, 2026)
Parasitic infections pose a significant threat to the wild population of Southern catfish (Silurus meridionalis) in Dongting Lake, yet the specific pathogen identity and epidemiological drivers remain unclear. This study combined morphological assessment, 28S rDNA molecular identification, and Generalized Linear Models (GLM) to elucidate the infection dynamics and pathogenicity of trematodes. Molecular analysis confirmed the pathogen as Isoparorchis eurytremus. GLM analysis revealed that apparent spatiotemporal variations in infection were actually sampling bias in fish host size structure; the total length was identified as the decisive predictor of infection risk. The infection probability followed a sigmoid growth pattern with a median infection length (L50) of 70.4 cm, a phenomenon attributed to the host’s ontogenetic diet shift from insectivory to obligate piscivory. Anatomical observations indicated that the infection induced systemic pathology; beyond severe fibrosis and mechanical damage to the swim bladder, varying degrees of parenchymal lesions were evident in the liver, spleen, and kidney. These findings indicate that I. eurytremus infection in S. meridionalis is a size-dependent, accumulative process maintaining a homogenous high pressure across the lake ecosystem, necessitating a shift in perspective from localized lesions to systemic disease management.

Zedoarondiol inhibits monocyte adhesion and expression of VCAM and ICAM in endothelial cells induced by oxidative stress - Bei-li Xie; Yu-long Bie; Bo-ce Song; Ming-wang Liu; Lin Yang; Jiangang Liu; Da-Zhuo Shi; Fu-Hai Zhao (Natural Product Research, 2026)

Multimodal MRI reveals hypothalamic structural-functional alterations associated with bone mineral density loss in postmenopausal women - Xiyong Dai; Zhijie Gao; Lei Gao; Chengwei Fu; Shanshan Wu; Zhaoxian Yan; Ling-Feng Zeng; Yue Zhang; Bo Liu (Brain Imaging and Behavior, 2026)

Arsenic species in crayfish from the Yangtze River basin, China: Levels composition and health risk assessment - Xinjie Li; Bo Fu; Kai Lin; Jiayin Huang; Sisi Yu; Wenchao Zhu; Yuli Lin; Chiqun Shan; Mingqin Zhong; Shaoyou Lu (Aquaculture, 2026)

Silencing of SOX4 prevents endothelial injury from ox-LDL stimulation by inhibiting NF-κB pathway and ferroptosis - Le-Wei He; Pan Hou; Wen-Bo Fu (Tissue and Cell, 2026)

Occurrence and sources of organic contaminants of emerging concern in indoor dust: A global perspective - Wei Du; Ruijing Hu; Nan Fu; Min Wu; Yang Liu; Yuanchen Chen; Guofeng Shen; Nan Lin; Bo Pan; Shu Tao (Journal of Hazardous Materials, 2026)

Occurrence, distribution, and potential risk of per- and polyfluoroalkyl substances in soil, outdoor dust, and atmospheric particles in the electronic industrial agglomeration zone in South China - Hanying Zheng; Xulong Chen; Bingjun Lu; Pei Luo; Bei Wang; Chiqun Shan; Bo Fu; Yuli Lin; Muchen Yin; Jiayi Xu; Xiangxuan Kong; Tingting Zhu; et al. (Environmental Pollution, 2026)

Occurrence, drivers, and risk assessment of non-antibiotic pharmaceuticals in urban sewer systems - Fan Meng; Shaojing Sun; Jialu Cheng; Ziyi Wang; Changshun Wang; Jinpan Jiang; Lu Lu; Jingchao Li; Yajie Tian; Lixin Ma; Bo Li; Xiaoyu Feng; et al. (Environmental Pollution, 2026)

Experimental and numerical investigation on seismic performance of seawater sea-sand coral aggregate concrete filled UHPC tubular columns - Chengdong Lu; Dingkuan He; Bo Shan; Peicheng Qin; Tianyu Li; Bin Huang; Xinlin Fu; Gang Liu (Engineering Structures, 2026)

Energy-saving and fire/water-resistant recyclable aerogel coatings for thermal-insulating polyurethane foam - Cong-Mei Lin; Xue-Lian Chen; Fu-Rong Zeng; Li-Xiao Hao; Yu-Shi Wen; Bing-Ru Zhang; Bo-Wen Liu; Lin Zhang; Hai-Bo Zhao (Chemical Engineering Journal, 2026)

Molecularly imprinted polymers-based magnetic CoFe oxides nanozyme for the removal of Staphylococcus aureus and label-free quantitative detection - Jing Liu; Ran Chen; Jing-Wen Chen; Shao-Bo Li; Yue-Jie Li; Yong-Fu Huang; Zhi-Bin Chen; Li Li (Chemical Engineering Journal, 2026)

Impact of carboxymethyl cellulose on the gelation and digestive characteristics of myofibrillar protein and its application for encapsulation of puerarin - Qiao-bo Zhang; Shi-Meng Liang; Yan-wei Yuan; Xue-xing Yin; Jing-jing Fu; Yue-wen Chen; Wen-qiang Cai (Carbohydrate Polymers, 2026)

Manganese cycle-mediated synchronous bacteria-algae/anammox coupled denitrification system under low-temperature conditions: Performance and mechanisms - Peng-fei Yu; Dian-lin Jiang; Ding Wang; Xing-guan Ma; Jun-Li; Li-yao Han; Ao Wang; Yu-bo Fu; Xing Jin (Bioresource Technology, 2026)

Data-Driven Insights and Prediction of Bauxite-Hosted Lithium Mineralization - Xiaokang Liang; Guotao Sun; Yong Fu; Bo Tang; Peiwen Chen; Zaiping Shi; Shijiang Yang; Guochen Zhou; Zhonghong Huang; Qiaolin Fu; Tianyi Liu (Natural Resources Research, 2026)

New Insights and Prospects for the Urban-Rural Fringe in the Context of Urban-Rural Integration - Bo Fu; Shuang Gang; Bing Xue (Chinese Geographical Science, 2026)

Community assembly governs microbial biogeography and ecosystem multifunctionality across Tibetan alpine grasslands - Xiao-Qian Yang; Jian-Guo Ma; Jian-Fei Yu; Fu-Sen Nan; Yuan-Qi Zhao; Xiao-Bo Wang (Applied Soil Ecology, 2026)

Enhancing oil-water separation via droplet coalescence regulated by particle self-rotation in swirling fields - Wei Zhao; Ao-song Wei; Shu Zhu; Tong Zhang; Peng-bo Fu; Jian-ping Li; Xue-jing Yang; Hua-lin Wang (Water Research, 2026)

Development of a potent protective felinized chimeric antibody C8A8 targeting feline and canine parvovirus - Yajie Sun; Chengqi Zhang; Jiajia Liu; Dingrui Guo; Shuangshuang Li; Liwen Xu; Bo Hu; Haifeng Zeng; Yawen Liu; Jianhai Fu; Zichuang Zhang; Wenyu Cao; et al. (Veterinary Microbiology, 2026)

Monoculm1 confers cold tolerance at the seedling stage in rice - Ruiqing Li; Chenfan Zheng; Binqiang Wang; Shang Dai; Yue Song; Huali Zhang; Zhiguo E; Bo Liu; Jiale Chen; Can Zhang; Haowei Fu; Ning Xu; et al. (Molecular Plant, 2026)

Quercetin alleviates Deoxynivalenol-induced myocardial fibrosis in chicken by regulating MCU-mediated mitochondrial calcium overload - Hong-yu Fu; Yi Fang; Jia Chen; Hongxue Yang; Xuehan Jiang; Yishan Yin; Bo Li; Xiaoxiao Chen; Jingzeng Cai; Ziwei Zhang (Journal of Hazardous Materials, 2026)

Sunlight-driven evolution of the aroma profile in fish sauce fermentation - Jin-Xiu Xu; Xin Zhang; Bai-Feng Fu; Zhao-Rui Li; Min-Bo Li; Zhen-Yu Wang; Xian-Bing Xu; Shu-Zhen Cheng; Ming Du (Food Bioscience, 2026)

Non-contact preservation of chilled chicken: extending shelf life and modulating microbial dynamics using solid spice essential oils and modified atmosphere packaging - Xue Li; Dongwen Fu; Shuai Hu; Jinqing Huang; Li Wang; Yao Zhang; Cailing Liu; Bo Dong; Guangxian Liu (Food Control, 2026)

Vanillin-derived bio-based Schiff base for simultaneously enhancing flame retardancy, crystallizability and UV-shielding of poly(L-lactic acid) - Mengmeng Wei; Leihua Jia; Dandan Fu; Zhenhua Shi; Masrina Mohd Nadzir; Junsheng Wang; Yipaerguli Yiminniyazi; Li Fan; Qiran Wang; Fude Liu; Bo Wang; Jinjun Yang (Chemical Engineering Journal, 2026)

Mechanical interlocking enhanced hybrid electrode for long-term epidermal biopotential monitoring in clinical applications - Xiaoqian Dong; Fu Fan; Lei Chen; Yu Zhou; Fangqun Cheng; Yinglong Duan; Ning Qin; Huan Cao; Xingxing Wang; Bo Feng; Jianfei Xie; Jian Zhou; et al. (Chemical Engineering Journal, 2026)

Corrigendum to “A carboxymethyl chitosan/trans-2-hexenal Schiff's base gel with controlled density using dynamic imine bonds: pH-controlled release and extended duration” [Carbohydrate Polymers 354 (2025) 123305] - Guang-shuo Zhou; Tao Zhang; Yan Jin; Guo-fu Zhang; Bo Kong; Da-yin Chen; Guo-xian Wang; Zi-shu Wang; Meng-ying Qi; Da-xia Zhang; Wei Mu; Nan Zou (Carbohydrate Polymers, 2026)

Ectomycorrhizal exploration types shape soil enzyme activity, decomposition, and nitrogen dynamics in subalpine forests - Lixia Wang; Haoying Gao; Shuangjia Fu; Huichao Li; Lin Xu; Li Zhang; Han Li; Chengming You; Sining Liu; Hongwei Xu; Jiao Li; Bo Tan; et al. (Plant and Soil, 2026)

The persistent threat of Niphades castanea to China’s chestnut across three major river basins - Bin Mao; Yue Fu; Ya-Bo Liu; Hui-Ling Yang; Yun-Li Xiao (New Forests, 2026)

Research on Risk Evaluation of Tunnel Water Inrush Based on Multi-source Geophysical Exploration Data Fusion of MLP-Transformer Model - Guang Huo; Huai-bing Wang; Jin-gang Zhang; Yi-guo Xue; Bo-yin Fu; Fan-meng Kong; Zongwei Yan (Applied Geophysics, 2025)

Corrigendum to “Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk” [Toxicology and Applied Pharmacology Volume 503, October 2025, 117465]. - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Aggregate size mediates the stability and temperature sensitivity of soil organic carbon in response to decadal biochar and straw amendments - Yalan Chen; Yakov Kuzyakov; Qiwen Ma; Zhangliu Du; Ke Sun; Keqing Xiao; Xinru Liang; Yang Li; Yunxian Zhang; Xianqiang Lai; Wei Fu; Bo Gao; et al. (Soil Biology and Biochemistry, 2025)

Phytochemical profiling of Bai traditional food: Eight previously undescribed meroterpenoids derivatives with cytotoxic potential from the flowers of Rhododendron pachypodum - Ying Wang; Jie Luan; Ji-Ai Wang; Xiu Chen; Fu-Cai Ren; Bing Chen; Jing Jia; Gao-Hong Zhang; Yong Li; Jiang-Bo He (Phytochemistry, 2025)

Water vapor sorption behavior of shale organic matter with various types and maturation - Jiajun Fu; Ke Xu; Yeping Ji; Xuezhe Wang; Yiquan Ma; Mehdi Ostadhassan; Zhejun Pan; Duo Wang; Bo Liu; Yubing Ke; Mengdi Sun (Journal of Hydrology, 2025)

Optimal matrix identification of parabens, triclosan and triclocarban for biomonitoring: Comparative analysis in urine, whole blood, serum, and plasma - Weizhong Chen; Yuli Lin; Kai Lin; Xiaoru Wu; Chiqun Shan; Bo Fu; Yiran Chen; Junye Bian; Xinjie Li; Xulong Chen; Tao Chen; Guangyu Sun; et al. (Journal of Hazardous Materials, 2025)

Structural dynamics and multifunctionality of zero-dimensional Sb-based halides: Unveiling anomalous thermal quenching and pressure-driven luminescence control - Daxi Pan; Liangyi Gu; Bo Wang; Xiaoshuang Li; Jingrui Zhang; Jiahong Li; Ruijing Fu; Youchao Kong; Qingguang Zeng (Journal of Environmental Chemical Engineering, 2025)

GRACE-derived spatiotemporal changes of terrestrial water storage in the major plateaus of China - Dong Wang; Bo-Hui Tang; Yingyun Li; Wei Fu; Zhitao Fu; Zhen Zhang; Zhongxi Ge (Global and Planetary Change, 2025)

Investigation of microstructural characteristics and methane desorption in coal using surfactant treatment - Chen Ming-yi; Pei Zi-ting; Hu Shi-bo; Su Wei-wei; Tian Fu-chao; Zhang Xue-jie (Fuel, 2025)

Covalent organic framework nanospheres for solid-phase extraction of pyrethroids from vegetables - Weixin Duan; Na Liu; Xuechun Fu; Na Wang; Bo Cui (Food Chemistry, 2025)

Soil and retaining wall responses induced by horizontal soil arching - Zhuofeng Li; Jiefei Fu; Shuangqin Li; Bo Yang; Peng Xia; Yunmin Chen (Computers and Geotechnics, 2025)

Green synthesis and functionalization of rice husk-derived SiO₂ nanoparticles for scale inhibition: A multiscale study combining experiments, molecular dynamics simulations, and quantum chemical calculations - Yuxiao Han; Shuyuan Deng; Jian Fu; Bo Wang; Jie Gao; Ming Nie; Qijun Wu; Yuehui She; Fan Zhang (Chemical Engineering Journal, 2025)

Controlled chain length production of ε-poly-l-lysine by Streptomyces albulus - Chenghao Fu; Wenjuan Dai; Aoxiang Liu; Yongxuan Liu; Qingshou Yao; Linghui Kong; Bo Yu; Xiuwen Wang; Jiayang Qin (Chemical Engineering Journal, 2025)

Ambient-dried polymer aerogel engineered via interparticle “stringing” towards ultrahigh robustness, flame retardancy and harsh-environment durability - Ting-Ting Li; Ting Wang; Chengxu Xu; Xue Gou; Xi-Ping Huang; Si-Yao Zhong; Zhi-Cheng Fu; Jinni Deng; Wenli An; Hai-Bo Zhao; Ming-Jun Chen (Chemical Engineering Journal, 2025)

Tailoring anchoring functionalities of self-assembled materials for efficient wide-bandgap perovskite solar cells - Zhong-En Shi; Yu-Fan Fu; Bo-Shun Peng; Ting-Chun Hung; Deebakkrishnan Ganesan; Rajendiran Balasaravanan; Shao-Huan Hong; Cheng-Liang Liu; Chun-Jen Su; Ming-Chou Chen; Chih-Ping Chen (Chemical Engineering Journal, 2025)

Floc-granule microbial symbiosis drives DNRA in anammox bacteria via cross-feeding for complete autotrophic nitrogen removal - Yulong Yang; Wen-Bo Nie; Xin Tan; Lili Li; Chenhui Yu; Shibo Fu; Ke-Di Peng; Yi Luo; Xiao Ran; Zhihong Zheng; Jin Xu; Jun Li; et al. (Chemical Engineering Journal, 2025)

Characterization of a novel biosurfactant from Alcanivorax dieselolei and its mechanism for enhanced oil recovery in low-permeability reservoirs - Shuyuan Deng; Bo Wang; Ruixue Qu; Yuxiao Han; Cenqian Zhang; Chenyue Wang; Jian Fu; Shanshan Sun; Hao Dong; Gongze Cao; Qing You; Yuehui She; et al. (Chemical Engineering Journal, 2025)

Pluvial flood warnings in a tidally influenced basin enhanced by rainfall–tide compound indicators: Taipei case study - Mei-Ying Lin; Wen-Yih Sun; Huei-Syuan Fu; Chih-Hsin Chang; Wei-Bo Chen; Chieh-Ju Wang; Hsuan-Wei Wang; Yi-Chiang Yu; Yen-Wei Li (Stochastic Environmental Research and Risk Assessment, 2025)

From heterogeneity to prognosis: understanding the complexity of tertiary lymphoid structures in tumors - Yingying Wang; Dongyan Zhang; Xueping Huang; Guohao Wu; Chuanbao Wang; Jun Li; Song Wang; Xinmiao Xian; Bo Fu; Keyi Li (Molecular Biology Reports, 2025)

EDIL3 induced by GLIS2 suppresses the anti-tumor activity of CD8+ T cells and expedites epithelial-mesenchymal transition in thyroid cancer - Xu Qian; Bo Fu; Shuangfu Peng; Meiling Xue; Zhaohui Zhu; Dan Yao (Journal of Molecular Histology, 2025)

Selective kernel convolution with global attention mechanism for multitask change detection in optical and SAR images - Tonggen Yang; Liang Huang; Bo-Hui Tang; Zhitao Fu; Zhen Zhang; Zhongxi Ge; Man Zhang; Siming Pu (Earth Science Informatics, 2025)

Polarization standard filtering enables multi-attribute tobacco grading by near-infrared spectroscopy - Xu Ye; Xinyi Chen; Jinglan Zhang; Mingyu Cheng; Bo Fu; Bin Ai (Analytica Chimica Acta, 2025)

Comparison of various machine learning algorithms for landslide susceptibility assessment: A case study of Meishan township, Zhejiang Province, China - Du Bo Wang; Fu-Wang Zhong; Xuan-Wang Zi (Applied Geophysics, 2025)

Wavelength-dependent photobiomodulation attenuates synovial inflammation in fibroblast-like synoviocytes and a collagenase-induced osteoarthritis model - Tianxiang Fan; Peng Xia; Safayet Ahmed; Yuen H. Tsang; Zhi Yao; Deli Wang; Ziyu Chen; Lixiang Xue; Dongquan Shi; Bo Wang; Chi Fai Cheung; Marco Y.C. Pang; et al. (Journal of Photochemistry and Photobiology B: Biology, 2025)

The impact of China's Clean Air Action and future strategies: Actions targeting regionally dominant sources - Xuelian Peng; Nan Fu; Jinze Wang; Yuanchen Chen; Kang Mao; Lu Zhang; Yiming Qin; Jianhuai Ye; Wei Du; Peng Zhang; Bo Pan; Shu Tao (Journal of Environmental Management, 2025)

Improved chemical and gastrointestinal stability of natural proanthocyanidins encapsulated in hydrolyzed soy protein-based nanoparticles - Hongling Fu; Hao Gong; Junjie Gao; Bohan An; Xue Chen; Bin Liu; Bo Lyu; Wendan Jing; Hansong Yu (Food Research International, 2025)

Machine learning-guided anti-photoaging peptides from Chinese giant salamander skin: Efficient preparation and mechanistic insights - Yongjie Zhou; Huijuan Zhang; Chunyue Zhao; Zixin Fu; Yuting Wang; Sam K.C. Chang; Yan Zhang; Hui Hong; Yongkang Luo; Bo Li; Yuqing Tan (Food Chemistry, 2025)

Regulation of peptide hydrophobicity by self-assembly of casein peptides with ferulic acid to potentially reduce peptide bitterness and improve in vitro digestive activity - Si-Yi Han; Hong-Fu Zhao; Bo-Kang Yu; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

3D printed-assisted fabrication of embedded porous solar evaporators for efficient photothermal evaporation - Zhu-Long Yu; Lei Xu; Cai-Hua Liu; Wen-Bo Guo; Ming-Lai Fu; Baoling Yuan (Desalination, 2025)

Synergistic effects of metal‑carbon composites in catalytic ozonation: Structure, catalytic pathway and application - Jing Zhang; Kexin Tian; Ye Liu; Yating Fu; Yi Ren; Bo Lai (Chemical Engineering Journal, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

Modified carboxymethyl cellulose for simultaneously enhancing fire-proofing, crystallizability, UV-barrier and hydrophilicity performances of bio-based poly(L-lactic acid) - Zhenhua Shi; Mengmeng Wei; Tong Gao; Dandan Fu; Masrina Mohd Nadzir; Junsheng Wang; Leihua Jia; Wenjiao Yuan; Bo Wang; Jinjun Yang (Chemical Engineering Journal, 2025)

Heterointerface engineering of novel 2 M phase WSe2 as co-catalysts for enhanced photocatalytic nitrogen fixation - Xinyu Wang; Kaidi Zhang; Bo Fu; Jian Tian (Chemical Engineering Journal, 2025)

The recovery mechanism of granular sludge fragmentation and re-granulation caused by long-term high-concentration organic matter erosion in the SAD process: performance, sludge evolution, and metagenomic sequencing - Peng-fei Yu; Ding Wang; Yu-bo Fu; Xing-guan Ma; Hao Zheng; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Xing Jin (Bioresource Technology, 2025)

Quantifying the contribution of different microenvironments to real-time PM2.5 exposure of rural and urban residents in southwest China - Pingshu Wang; Shaojun Lv; Nan Fu; Nan Lin; Ming Yang; Yunhang Jiang; Yuanchen Chen; Peng Zhang; Wei Du; Bo Pan (Building and Environment, 2025)

A nine-year statistical study on the thunderstorms generated amid Dabie vortex background - Xue Xiao; Shen-Ming Fu; Bo Wang; Chao-Ying Yang; Shu-Guang Ning; Shi-Jun Sun; Kun-Shuang Zhu; Jian-Hua Sun (Atmospheric Research, 2025)

Four new acylphloroglucinol glucoside derivatives from the leaves of Lysidice rhodostegia - Tian-Yuan Wu; Wei-Xuan Zheng; Xuan Zhou; Kai Zhao; Wei Wu; Li-Qin Zhan; Jin-Tao Fu; Qing Tang; Yu-Bo Zhang; Wen Li; Guo-Cai Wang (Natural Product Research, 2025)

The response of plant-derived lignin phenols accumulation to nutrient addition depends on soil depth in a subtropical plantation - Jin He; Dong Bu; Yuan-Huang Zeng; Shui-Bo Han; Wen-Qing Li; Fu-Sheng Chen; Ying-Ying Zong; Yu-Xin Huang; Yang Zhang; Xiang-Min Fang (Plant and Soil, 2025)

A chemometric approach for FTIR-Raman-LIBS tri-modal spectral fusion: Transformer-based accurate identification of recyclable polymers - Wenxia Xu; Zhuoqing Fu; Bo Tang; Jun Xu; Guodong Li (Analytica Chimica Acta, 2025)

Ameliorative effects of Clostridium butyricum metabolites on growth, oxidative stress, and intestinal health in bullfrogs fed high soybean meal diets - Xiongqi Wu; Shuiquan Fu; Yi Hu; Bo Zhu; Mengxi Yang; Jihong Dai (Aquaculture International, 2025)

Two new withanolides from Physalis minima L - Li-Jie Zhang; Mei-Lin Peng; Shi-Ying Xu; Fu-Rui Wang; Lin-Lin Yu; Qin-Feng Zhu; Shang-Gao Liao; Guo-Bo Xu (Natural Product Research, 2025)

Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Middle Campanian to Maastrichtian foraminifera and biomarkers: Seawater incursion events in the Songliao Basin, Northeast China - Ke-Ying Yue; Sha Li; Tian Jiang; Dang-Peng Xi; Bo-Wen Song; Yu Liang; Li-Xin Sun; Tian-Fu Zhang; Hai-Chun Zhang; Xiao-Qiao Wan; Bo Wang (Palaeoworld, 2025)

Genomic insights into the reticulate evolution of viviparous Phrynocephalus lizards on the Qinghai-Tibetan Plateau - Xianguang Guo; Zhongyi Yao; Bo Cai; Xiao Xiao; Qiwei Xu; Ying Chen; Lin Cui; Xia Qiu; Jinzhong Fu; Yin Qi; Weizhao Yang (Molecular Phylogenetics and Evolution, 2025)

Morphology and sulfur isotopes of pyrite in Chang73 shale: Indications for redox conditions and enrichment of organic matter and hydrocarbons - Bo Ma; Liming Ji; Qianshan Zhou; Ying Zhang; Shuang Fu; Yueye Xiao; Hao Sun (Marine and Petroleum Geology, 2025)

The influence of water flow disturbance form on the granulation of algae sludge: Granulation property, treatment effect and algae biological structure - Peng-fei Yu; Ao Wang; Hai-wen Sun; Ding Wang; Xing-guan Ma; Yu-jia Wang; Bo-mei Hu; Li-yao Han; Yu-bo Fu; Dian-lin Jiang; Shi-gang Tu (Journal of Water Process Engineering, 2025)

WB-assisted activation of periodate by Fe(III) for decontamination: Periodate concentration-dependent mechanistic shift - Yulu Xu; Yu Mei; Yanjun Li; Chenye Fu; Yuantai Li; Yuheng Zhong; Junxi Song; Gang Yang; Shihuai Deng; Xiaohui Lu; Jiali Peng; Bo Lai (Journal of Hazardous Materials, 2025)

Light-driven CO2 reduction for acetate production by coupling photocatalyst CdS with acetogenic bacteria Clostridium aceticum: An insight into the electron transfer pathway - Bo Fu; Wei Lin; Hui Zhao; Shijian Yang; Jingyi Han; Qihao Cao; He Liu; Hongbo Liu; Jieshu Qian (Journal of Environmental Chemical Engineering, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

High pollution and health risk of antibiotic resistance genes in rural domestic sewage in southeastern China: A study combining national-scale distribution and machine learning - Bingbing Feng; Juan Chen; Chao Wang; Peifang Wang; Han Gao; Bo Zhang; Jingjing Zhang; Shunqing Zhang; Jingjing Fu (Environmental Pollution, 2025)

Polyacrylic acid promotes anti-passivation and electron-donation of boronized nanoscale zero-valent iron during groundwater remediation - Zelong Zheng; Lihang Ma; Xiaobin Liao; Ming-Lai Fu; Baoling Yuan; Xiao-yan Li; Yi-bo Hu (Chemical Engineering Journal, 2025)

Quaternary ammonium iodide as a passivator for enhanced efficiency and stability in perovskite solar cells - Ji Cao; Lijie Wang; Hui Ma; Jianfei Fu; Wenxi Ji; Qiaoyun Chen; Zelong Zhang; Yi Zhou; Bo Song (Chemical Engineering Journal, 2025)

Antinode-centre near-infrared tandem OLEDs enabled by ultrathin emissive layers - Min Song; Zheng Ren; Sheng-Fu Wang; Xiao-Bo Shi; Wei-Zhi Liu; Zi-Qi Feng; Dong-Ying Zhou; Pi-Tai Chou; Liang-Sheng Liao (Chemical Engineering Journal, 2025)

Nitrilotriacetic acid-assisted activation of periodate by Fe(III) for organic pollutant degradation: the critical roles of high-valent iron species formation and coordination inhibition by phenolic contaminants - Xiaohui Lu; Yuantai Li; Shihuai Deng; Yanjun Li; Chenye Fu; Guochun Lv; Da Wang; Junxi Song; Hong Xiao; Jiali Peng; Bo Lai (Chemical Engineering Journal, 2025)

van der Waals heterojunction-based NO2 chemosensor via a synergistic halogen bond site - Wen Luo; Huan Liu; Zhen Zhu; Bo Wang; Wenxing Xu; Ximeng Luo; Chunhui Li; Yanyan Fu; Huizi Li; Huimin Cao; Wei Xu; Qingguo He; et al. (Chemical Engineering Journal, 2025)

Synthesis of expanded microcrystalline graphite/Mn0.4Zn0.6Fe2O4 composites for electromagnetic wave absorption - Mingzhe Liu; Bo Wang; Yujiang Wang; Binchuan Li; Daxue Fu; Yongfeng Chang; Jianshe Chen; Kuiren Liu; Qing Han; Xudong Lu; Cean Guo; Shicheng Wei (Chemical Engineering Journal, 2025)

Effect of Attribute Information of Recycled Water on Willingness to Accept: Evidence from an Event-Related Potential (ERP) Experiment - Hanliang Fu; Bo Dong; Zhifang Wu; Caixia Hou; Yanjun Ren (Water Resources Management, 2025)

Emerging role of RNA m6A modifications in laryngeal squamous cell carcinoma: insights into tumorigenesis and therapeutic potential - Guotong Zheng; Jing Bi; Yangyan Yan; Bo Yu; Yong Fu (Apoptosis, 2025)

Downregulation of Tra2α and Tra2β suppresses lipopolysaccharide-induced inflammation in macrophages by regulating MyD88 mRNA alternative splicing - Yu Fu; Luyao Zhang; Yanjing Wang; Bo Cheng; Weiye Shi; Peiyuan Chen; Jinyu Liu; Xiaolei Zhou; Yingze Wang (Molecular and Cellular Biochemistry, 2025)

Correction: Mapping the potential of biogas production for electricity generation from agricultural crop residues at the town scale in China - Zheng Yang; Hongqing Li; Bo Fu; Bing Xue; Vera Susanne Rotter (Environment, Development and Sustainability, 2025)

Diaporchalasin A, a new PDE4 inhibitory cytochalasin from Conus marmoreus -derived fungus Diaporthe sp. XMA007 - SiYi Liu; MengWei Qin; YuJia Shi; Jiaolin Bao; Bo Yi; Ying Fu (Natural Product Research, 2025)

Does resource recovery and utilization improve environmental and economic performance of rural wastewater treatment plants? A case study in Xiamen, China - Bo Fu; Jie Wu; Shaohua Chen; Junjie Cheng; Ziyu Zheng; Yurou Zhang; Xiangyu Lin; Lishan Xiao (Water Research, 2025)

Anti-inflammatory abietane-type diterpenoids from the roots of Salvia przewalskii - Yan-Fang Chen; Yu-Qing Lu; Wan-Yun Gao; Bo-Yi Fan; Fu-Cai Ren; Chuan-Pu Shen (Phytochemistry, 2025)

Vanadium-cobalt oxide nanoflower catalyst for efficient and stable overall water splitting in alkaline and seawater electrolytes - Yong-qi Tian; Song-lin Xu; Jia Li; Shuang-shuang Zhang; Bo-yao Zhang; Rong-da Zhao; Fu-fa Wu; De-peng Zhao (Next Research, 2025)

Study on intrinsic reaction kinetics of coal char gasification based on general surface activation function model - Jiye Tao; Zezheng Shi; Yang Liu; Yongxiao Jia; Zhi Wang; Xinyu Wang; Yumin Chen; Bo Yu; Shisen Xu; Dongliang Xu; Qingyan Fang; Peifang Fu; et al. (Fuel, 2025)

Quality characteristics and structure-function relationships of peanut proteins from different phase sources by aqueous enzymatic extraction - Xin Guo; Wen-ye Xie; Hui Hu; Feng-ying Gu; Fu-sheng Chen; Xing-feng Guo; Bo Jiao; Qiang Wang (Food Chemistry, 2025)

Mechanically treated natural mineral-modified biochar for triggering peroxymonosulfate oxidation of micropollutants: Unveiling the critical role of non-radical pathways and vacancy-mediated electron transfer - Huanhuan Wang; Geng Chen; Quanbin Zhang; Zhenhua Wang; Bo Fu; Huifu Ji; Yifan Liu; Yunjie Wu; Jingshang Xiao; Binqiang Tian (Chemical Engineering Journal, 2025)

Perovskite-socketed FeCoNiCu quaternary alloy nanoparticles for efficient CO2 reduction in solid oxide electrolyzer - Shuo Liu; Lin-Bo Liu; Ming Yang; Yan Li; Qinglin Pan; Yifei Sun; Xian-Zhu Fu; Subiao Liu; Jing-Li Luo (Chemical Engineering Journal, 2025)

Thermal transformation of metal-organic frameworks as Ca-Ni-Al bifunctional materials for efficient integrated CO2 capture and conversion - Xiaoju Xiang; Wenxing Yao; Bo Jin; Ruiyue Wang; Dongtao Fu; Hongxia Gao; Haibo Zhao; Zhiwu Liang (Chemical Engineering Journal, 2025)

Bioinspired neural network-enabled metre-scale attached ultraductile cementitious nanosensors with temperature-immune - Hua Fu; Penggang Wang; Heping Zheng; Bo Pang; Zuquan Jin; Xiaoyun Song; Li Tian; Zhenxing Du; Bukhari Mohd Nadeem; Peng Zhang; Zhengkai Hu (Chemical Engineering Journal, 2025)

Dual-defect engineering strategy induced polarization loss in trimetallic MOFs/MXene-derived nanocomposites for broadening microwave absorption bandwidth - Yuanzhao Hou; Binchuan Li; Kuiren Liu; Jianshe Chen; Yongfeng Chang; Bo Wang; Shicheng Wei; Xiaocai He; Da Li; Chul B. Park; Daxue Fu; Qing Han (Chemical Engineering Journal, 2025)

Evolution of fire activity in arid Central Asia since ∼12.9 ka: Transitioning from natural to anthropogenic forces - Wensheng Zhang; Guoqiang Ding; Yong Zhang; Yuecong Li; Bing Li; Chao Lu; Bo Tan; Aijun Sun; Yang Fu; Chengbang An (CATENA, 2025)

Quorum-sensing Inhibitory Activity of Xanthones from Hypericum Curvisepalum N. Robson Against Chromobacterium Violaceum - Hong Zeng; Qiu-Ying He; Sheng-Qiang Yang; Xiao-Lian Wei; Jia-Zi Luo; Jing-Kai Zhou; Rong-Bing Fu; Li-Ping Teng; Zhong-Bo Zhou (Current Microbiology, 2025)

Effective diclofenac degradation via intrinsic Mn(III)-Mn(II) cycle in the permanganate-manganese dioxide system - Zelong Zheng; Lianjuan Lin; Yi-bo Hu; Xiaobin Liao; Ming-Lai Fu; Baoling Yuan (Journal of Environmental Chemical Engineering, 2025)

Multi-omics study reveals a light-dependent regulatory network of flavonoid biosynthesis in lettuce (Lactuca sativa L.) - Yuting Xiang; Shuxin Zheng; Hsihua Wang; Bang Chen; Rao Fu; Tao Huang; Li Zhang; Bo Song; Yuejian Li; Qichang Yang; Xiao Yang; Yang Zhang (Science China Life Sciences, 2025)

Mapping the potential of biogas production for electricity generation from agricultural crop residues at the town scale in China - Zheng Yang; Hongqing Li; Bo Fu; Bing Xue; Vera Susanne Rotter (Environment, Development and Sustainability, 2025)
The application of anaerobic digestion technology to crop residues plays a vital role in advancing sustainable agricultural development. In China, townships act as key regulators, essential for evaluating the energy potential of waste and implementing agricultural waste recycling policies. However, data at the township level often suffers from issues such as incomplete collection, inconsistent quality, and omissions. To address these challenges, we employed a multi-source data approach—including official statistics, field surveys, remote sensing imagery, and laboratory experiments—to ensure comprehensive and reliable data coverage. This study utilizes four distinct models: Biochemical Methane Potential, a simplified Anaerobic Digestion Model No. 1, Gradient Boosting, and Random Forest to calculate biogas production potential from crop residues. By integrating these models with Geographic Information Systems, we delineate the potential for electricity generation from biogas production at the township level throughout China. Despite variations in the input data across different models, the maximum output discrepancy is limited to 13.4% (i.e., the maximum relative deviation between each model’s output and the mean output for each crop), indicating minor differences. This finding underscores the flexibility in model selection based on the availability of data. Moreover, our analysis reveals that local biomass straw residue can fulfill around 11% of residential electricity demands. This research introduces an innovative and comprehensive methodology that integrates multiple predictive models with Geographic Information Systems (GIS) to assess the energy potential of crop residues for biogas production at the township scale, thereby providing a robust framework to inform energy policy development and management strategies.

Numerical study of unmanned surface vessel's dynamic characteristics in rough sea conditions - Weijian Liu; Huanhuan Feng; Bo-Fu Wang; Yuhong Dong (Ocean Engineering, 2025)

Analysis of intrinsic effects of compound curing agents on small molecule metabolites and microbial communities in Xuanwei ham based on metabolomics and high-throughput sequencing - Zhijie Zheng; Wenxi Fu; Guiying Wang; Bo Li; Wen Xun; Nannan Zhou; Chunfang Yang; Ruwei Ren; Shuai Tang; Yanfei Du; Jiayan Tan; Dahai Gu; et al. (Meat Science, 2025)

Unveiling the mechanism of fermentation induced antioxidant activity enhancement in asparagus juice: Metabolomic and transcriptomic insights into the functional role of Lactiplantibacillus plantarum JGS 49 - Jinqing Huang; Li Wang; Xue Li; Yao Zhang; Bo Dong; Shuai Hu; Cailing Liu; Dongwen Fu; Lecheng Shen; Guangxian Liu (Food Bioscience, 2025)

pH-responsive drug-targeted delivery system: Dual-drug loading hollow mesoporous silica for synergistic therapy bacterial enteritis of Micropterus salmoides - Yuan-shuai Fu; Yue Lin; Wen-jun Zhong; Xing-yu Wang; Xi-ke Li; Yun-ao Li; Sheng-bo Ye; Wen-juan Li; Yong-heng Zhu (Chemical Engineering Journal, 2025)

Bioinspired structural laminates with superior ice-repellence and damage resistance for aviation applications - Mingdi Shi; You Pan; Haixiao Cao; Yongxin Guo; Xue Sun; Yuan Fu; Yihang Wu; Yufei Luo; Yangyu Lu; Zhenting Wu; Liang Jiang; Bo Li; et al. (Chemical Engineering Journal, 2025)

Forest conversion and root trenching reshape microbial functions regulating root litter decomposition and soil carbon dynamics - Lixia Wang; Shuangjia Fu; Haoying Gao; Huichao Li; Yang Liu; Lin Xu; Li Zhang; Han Li; Chengming You; Sining Liu; Hongwei Xu; Bo Tan; et al. (Applied Soil Ecology, 2025)

Biochar mitigates greenhouse gas emissions from bulk soil in wheat-corn rotation system by inhibiting biochemical decomposition - Debo He; Rui Yang; Yan Fu; Dongni Hu; Han Ma; Xiaoguo Wang; Zhixin Dong; Bo Zhu (Agriculture, Ecosystems & Environment, 2025)

Chitosan Nano-Selenium Supplementation Improves Production Performance, Egg Quality, and Selenium Deposition in Aging Laying Hens - Gang Shu; Xin Yi; Lei Yang; Jingyi Chen; Kang Fu; Haohuan Li; Funeng Xu; Wei Zhang; Hualing Fu; Bo Jing; Felix Kwame Amevor; Yingjie Wang; et al. (Biological Trace Element Research, 2025)

Effluent organic matter facilitates anaerobic methane oxidation coupled with nitrous oxide reduction in river sediments - Chenhui Yu; Qiang He; Wen-Bo Nie; Tanglong Zhang; Hao Wu; Yulong Yang; Shibo Fu; Xin Tan; Yi Chen (Water Research, 2025)

Selective salt separation and resource recovery via nanofiltration in coal-to-ethylene glycol wastewater - Zheng-Jun Fu; Bo-Zhi Chen; Kai Yu; Jian-Guo Hu; Pengli Chen; Hui-Qin Zhang; Mei-Ling Liu; Shi-Peng Sun (Journal of Water Process Engineering, 2025)

Unveiling the deep-sea microplastic Odyssey: Characteristics, distribution, and ecological implications in Pacific Ocean sediments - Hua Deng; Yutao Fu; Lei Su; Daohua Chen; Xiguang Deng; Bo Hu; Yuye Chen; Yinan Deng (Journal of Hazardous Materials, 2025)

Superior properties of biochar contribute to soil carbon sequestration and climate change mitigation - Debo He; Rui Yang; Yan Fu; Bo Zhu (Journal of Environmental Chemical Engineering, 2025)

Controlling the morphology of CdS deposited on nickel foam for concurrent 4-nitrophenol reduction and electricity generation - Ting Du; Zelong Zheng; Lihang Ma; Yanyang Xu; Xiaobin Liao; Baoling Yuan; Ming-Lai Fu; Yi-bo Hu (Journal of Environmental Chemical Engineering, 2025)

Rigid polyelectrolyte multilayer membrane with ultrahigh permeance and excellent dye/salt separation performance - Na Zhang; Fanglu Fu; Wen Bo; Hussein Baqiah; Li Zhao; Wenbo Lu; Yadi Cai; Jiahui Tian; Tingting Yan; Saisai Li; Shuyun Zheng; Qiang Li (Journal of Environmental Chemical Engineering, 2025)

Control of sedimentary and diagenetic processes on the reservoir heterogeneity: A case study of the cretaceous carbonate reservoir in an onshore oilfield, Abu Dhabi - Yuting Peng; Yingxiao Fu; Hangyu Liu; Kaibo Shi; Bo Liu; Rubing Han; Xili Deng (Journal of African Earth Sciences, 2025)

Inorganic arsenic in aquatic products in Shenzhen, China from 2018 to 2024: Levels, temporal variation and health risk assessment - Bo Fu; Kai Lin; Sisi Yu; Yiming Ge; Xinjie Li; Wenchao Zhu; Lei Tan; Rui Wang; Jixi Ou; Shaoyou Lu (Food and Chemical Toxicology, 2025)

Wide-bandgap perovskite solar cells with > 1.34 V Voc for all-perovskite tandems - Yunfei Li; Nannan Sun; Bo Feng; Wen Li; Zhengbo Cui; Wenxiao Zhang; Sheng Fu; Xiaodong Li; Junfeng Fang (Chemical Engineering Journal, 2025)

Deep eutectic solvents for ginsenoside extraction and inhibition of ginsenoside hydrolysis in Panax notoginseng leaves: methodology and mechanistic insights - Jia-Yue Liu; Shi-Yao Hua; Li-Juan Ma; Xin Tao; Wen-Yu Fu; Jian-Bo Wan (Chemical Engineering Journal, 2025)

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

Spatial Variability and Influencing Factors of Soil Organic Carbon, Soil Total Nitrogen and C:N Ratio in Chinese Hickory Plantations of Southeastern China - Ying He; Bo Wu; Chaoxian Wang; Yuyou Zhi; Yajie Shi; Weijun Fu; Yong Zhang (Journal of Soil Science and Plant Nutrition, 2025)

Plant and microbial communities follow fast-to-slow strategies in response to grazing in an arid rangeland - Jian-Guo Ma; Jian-Fei Yu; Xiao-Bo Wang; Fu-Jiang Hou (Agriculture, Ecosystems & Environment, 2025)

Neoarchean accretionary and collisional tectonics in the southern North China Craton: Implications for crustal growth and plate tectonic styles - Bo Huang; Timothy Kusky; Dong Fu (Precambrian Research, 2025)

Numerical investigation to contribution of peripheral skirt and frame on undrained capacity of framed-tripod hexagonal bucket foundation in clay - Bo Liu; Jinrun Wang; Dengfeng Fu (Ocean Engineering, 2025)

PRDX1 affects acrylamide-induced neural damage through the PTEN/AKT signaling pathway - Dong-Xue Fu; Ya-Ting Lei; Hai-Bo Guo; Ting Chen; Xiang-Ying Gao; Xiao-Li Wang; Xiang Huang; Ling-Ling Song; Sheng-Yuan Wang; Qin-Xue Dai (NeuroToxicology, 2025)

Conductive characterization of shale reservoir induced by pore fluids: A case study of longmaxi formation in Southern Sichuan region - Yanran Li; Bo Liu; Zhiming Hu; Changhong Cai; Qingxiu Zhang; Jingshu Guo; Shuti Zeng; Fu Li (Fuel, 2025)

Preparation and characterization of microcapsules for tuna oil by maillard reaction products of whey protein isolate and Arabic gum via complex coacervation - Kun-Long Wang; Bo-Kang Yu; Hong-Fu Zhao; Ye-Xuan Liu; Chun-Ying Wu; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

Exceptional capacitive energy storage in CaTiO3-based ceramics featuring laminate nanodomains - Weishen Liu; Bo Fu; Jingji Zhang; Xiang Ma; Yuming Mao; Quan Zong; Zhejie Zhu; Haoran Yuan; Yun Zhou; Wangfeng Bai (Chemical Engineering Journal, 2025)

Mechanochemical treatment boosted microwave-assisted sulfonation of softwood lignin for the fabrication of dye dispersant - Xu Fu; Ling-Ping Xiao; Bo-Wen Meng; Wen-Jie Li; Run-Cang Sun (Chemical Engineering Journal, 2025)

High-entropy (FeMnMoNi)Se2 nanoflower structure with multi-active sites for urea-assisted hydrogen generation - Yumo Fu; Hao Liu; Bo Gao; Jianjia Mu; Guoqing Guan; Zhongbao Feng (Chemical Engineering Journal, 2025)

Three-step crosslinking dependent self-bending transformation of a nano-spherical mineralized collagen laden 4D printed sodium alginate scaffold for bone regeneration - Song Lv; Xiaojie Lian; Haonan Feng; Bo Yang; Zehua Liu; Tong Fu; Liqin Zhao; Di Huang (Carbohydrate Polymers, 2025)

Thermoacoustoelasticity for Elastic Wave Propagation in Preheated and Prestressed Solid Rocks - Jian Yang; Li-Yun Fu; Tongcheng Han; Wubing Deng; Bo-Ye Fu (Rock Mechanics and Rock Engineering, 2025)

Development and evaluation of an electrical impedance tomography (EIT) sensor for real-time monitoring of hemolysis dynamics - Piao Peng; Yue Fu; Bo Che; Xuan Li; Lei Liu; Jing Sun; Teng Luo; Linhong Deng (Analytica Chimica Acta, 2025)

Chemical constituents of Pedicularis rex C. B. Clarke and their hepatoprotective activities - Yang Fei-Yu; Liu Huai-Qin; Fu-Rui Wang; Zhang Li-Jie; Liao Xing-Jiang; Guo-Bo Xu; Qin-Feng Zhu; Shang-Gao Liao (Natural Product Research, 2025)

Physiological and molecular evidence for phycobilisome degradation in maintaining carbon and nitrogen balance of cyanobacteria - Zhen Luo; Shuangqing Li; Muhammad Zain Ul Arifeen; Fei‑xue Fu; Huayang Gao; Taoran Sun; Lingmei Liu; Xumei Sun; Xinwei Wang; Hai-Bo Jiang (Marine Life Science & Technology, 2025)
Phycobilisomes (PBS), the primary light-harvesting complexes in cyanobacteria, are degraded under nitrogen starvation to provide nitrogen for cell growth. This study reveals that carbon supply is a critical prerequisite for PBS degradation under nitrogen deficiency in Synechococcus sp. PCC 7002. Even under nitrogen-deficient conditions, PBS degradation is inhibited in the absence of sufficient carbon. We demonstrate that both the nblAB -mediated PBS-degradation pathway and the ccmLMNK operon-mediated CO 2 -concentrating mechanism are essential for PBS degradation. Furthermore, our findings highlight the critical role of PBS degradation in cyanobacterial adaptation to high C/N conditions. Mutant strains (Mut- nblA and Mut- nblB) deficient in PBS degradation exhibited impaired adaptation to high C/N conditions, as evidenced by their inability to thrive in high NaHCO 3 (nitrogen-free) or CO 2 (low-nitrogen) environments. While these mutants displayed a greener phenotype under high C/N conditions compared to the wild type, they exhibited extensive cellular damage, and significant downregulation of photosynthesis-related genes. These results provide novel insights into the carbon-dependent regulation of PBS degradation and its essential role in cyanobacterial C/N balance, highlighting its significance for their adaptation to fluctuating environmental conditions.

Adsorption characteristics of sulfate reducing bacteria Clostridium sp. on lignite surface - Huan He; Zi Yang Zhou; Di Zhan; Yong Zhang; Wen Cheng Xia; Bo Fu; Feng Juan Lan; Xiu Xiang Tao; Zai Xing Huang (Environmental Science and Pollution Research, 2025)

Genome skimming for improved phylogenetics of Taiwanese phasmids (Insecta: Phasmatodea) - Bo-Cheng Wang; Ming-Luen Jeng; Jing-Fu Tsai; Li-Wei Wu (Molecular Phylogenetics and Evolution, 2025)

3D hierarchical porous hydrogel polymer electrolytes for flexible quasi-solid-state supercapacitors - Haoran Wang; Zhaoxia Hou; Yue Wang; Haibo Long; Depeng Zhang; Zhongchao Fu; Nan Wu; Zihui Zhai; Bo Wang (Chemical Engineering Journal, 2025)

High-performance epoxy thermosets with excellent low dielectric, flame-retardant and antibacterial properties based on bio-based derived active ester curing agents - Hui Yang; Guoming Yuan; Zhijun Liu; Yanhan Tao; Bo Yang; Kun Wu; Jun Shi; Yi Fu (Chemical Engineering Journal, 2025)

A carboxymethyl chitosan /trans-2-hexenal Schiff's base gel with controlled density using dynamic imine bonds: pH-controlled release and extended duration - Guang-shuo Zhou; Tao Zhang; Yan Jin; Guo-fu Zhang; Bo Kong; Da-yin Chen; Guo-xian Wang; Zi-shu Wang; Meng-ying Qi; Da-xia Zhang; Wei Mu; Nan Zou (Carbohydrate Polymers, 2025)

Hybrid crosslinking cellulose nanofibers-reinforced zwitterionic poly (ionic liquid) organohydrogel with high-stretchable, anti-freezing, anti-drying as strain sensor application - Dong Fu; Linhui Xing; Yang Xie; Peng Li; Fan Yang; Xin Sui; Jiaying Liu; Jialong Chi; Bo Huang; Jun Shen (Carbohydrate Polymers, 2025)

Chitosan cryogels incorporated with phytic acid-modified UiO-66-NH2 for enhanced flame-retardant performance - Chenfei Wang; Bing Yu; Tong Zhao; Fan Yang; Muhua Chen; Xinbao Zhu; Zhengchun Cai; Bo Fu (Carbohydrate Polymers, 2025)

Correction to: Metanephric mesenchyme-derived Foxd1+ mesangial precursor cells alleviate mesangial proliferative glomerulonephritis - Meiling Jin; Zhong Yin; Kai Wei; Yuansheng Xie; Xueyuan Bai; Bo Fu; Zhe Feng; Qinggang Li; Xiangmei Chen (Journal of Molecular Medicine, 2025)

N-doped carbon nanotubes encapsulated Ni3ZnC0.7 nanoparticles catalyst for peroxymonosulfate activation: Heterojunction structure and N-doping enhance electron transfer capability - Qihao Sun; Huiyuan Deng; Na Zhao; Junjie You; Zhicheng Pan; Bo Xing; Yuling Ye; Bo Lai; Xinye Yang; Xinjie Wang; Yunhui Lu; Jian Li; et al. (Chemosphere, 2025)

Numerical investigation on seismic performance of drilled flange connection for steel frames - Hui Xu; Yujia Zhang; Peng Yan; Lei Zhang; Yan Liu; Yafei Chen; Bo Fu; Yu Zhou (Soil Dynamics and Earthquake Engineering, 2025)

Tanshinone IIA mitigates postoperative cognitive dysfunction in aged rats by inhibiting hippocampal inflammation and ferroptosis: Role of Nrf2/SLC7A11/GPX4 axis activation - Yan Yang; Bo Wang; Yichen Jiang; Wan Fu (NeuroToxicology, 2025)

Activation of persulfates on carbon nanotubes for water decontamination: Is the non-radical process consistently considered across different pH levels? - Jiali Peng; Lun Li; Shihuai Deng; Hongyu Zhou; Yanjun Li; Chenye Fu; Long Lin; Yue Yuan; Wei Wei; Guochun Lv; Gang Yang; Xiaohui Lu; et al. (Journal of Hazardous Materials, 2025)

Genetic analyses reveal wildfire particulates as environmental pollutants rather than nutrient sources for corals - Ke Liu; Bo Qin; Ruoxing Hao; Xiaoyan Chen; Yu Zhou; Wenqian Zhang; Yichen Fu; Kefu Yu (Journal of Hazardous Materials, 2025)

Distinguishing the self-ignition and ignition temperatures of coal based on Semenov’s thermal explosion theory - Yang Liu; Zezheng Shi; Yongxiao Jia; Zhaoshuai Chen; Bo Yu; Kuangyu Li; Zhi Wang; Xinyu Wang; Yumin Chen; Peifang Fu; Huaichun Zhou (Fuel, 2025)

Modeling Li isotope fractionation during the coal-combustion process and evaluating its capacity as an environmental tracer - Jing Chen; Yilin Xiao; Jack Geary Murphy; Dong-Bo Tan; Yang-Yang Wang; Biao Fu; Guijian Liu; Ru-Wei Wang; Xiaoxia Wang; Feng-Tai Tong (Chemical Geology, 2025)

The effect of soil depth on stoichiometry was greater than that of elevation in Abies georgei var. Smithii forest in Southeastern Tibet, China - Si-jie Zhu; Jiang-rong Li; Bo Zhang; Fang-wei Fu; Liang-na Guo (Acta Oecologica, 2025)

A multitemporal remote sensing thick cloud removal network based on implicit reconstruction - Ke Zhang; Han Nie; Weitong Li; Jianxin Wang; Bo-Hui Tang; Leiguang Wang; Zhitao Fu (International Journal of Remote Sensing, 2025)

Straw incorporating in shallow soil layer improves field productivity by impacting soil hydrothermal conditions and maize reproductive allocation in semiarid east African Plateau - Sylvia Ngaira Indoshi; Wesly Kiprotich Cheruiyot; Muhammad Maqsood Ur Rehman; Fu-Jian Mei; Qing-Hui Wen; Alex Ndolo Munyasya; Kiprotich Koskei; David Mwehia Mburu; Aggrey Bernard Nyende; Levis Kavagi; Delphine Nyanchera Gisacho; Eliyas Feyisa Sori; et al. (Soil and Tillage Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Quantitative analyses for wave energy evolution and dissipation processes under the gap resonance between two rectangular boxes - Xin-yu Wang; Yong Liu; Domenico D. Meringolo; Lin Lu; Fu Wang; Shao-dong Gong; Zi-bo Xia (Ocean Engineering, 2025)

Anisotropic acoustoelastic effective-medium model for stress-dependent elastic moduli of fractured rocks - Bo-Ye Fu; Li-Yun Fu (International Journal of Rock Mechanics and Mining Sciences, 2025)

Pi-efficient wheat cultivars screened by using both functional marker CAPS-799 and field experiment - Jinfeng Wang; Zedong Chen; Huanting Shi; Chuang Lou; Kaixia Fu; Yaxin Wang; Bo Yu; Tiancai Guo; Yonghua Wang; Pengfei Wang; Guozhang Kang (Field Crops Research, 2025)

Wastewater-based monitoring of antipyretics use during COVID-19 outbreak in China and its associated ecological risks - Chao Yu; Jianhe Zhang; Xiaofang Fu; Bo Zhou; Jianwen Huang; Jun Qin; Xiqing Li (Environmental Research, 2025)

Unraveling the role of oxygen vacancies in enhancing the SO2-resistance of α-MnO2 towards elemental mercury removal - Qian Yu; Fei Lai; Shiwei Sheng; Yujia Wang; Bo Yuan; Dong Fu (Chemical Engineering Journal, 2025)

A systematic review on heavy metals in indoor air: Occurrence, spatial variation, and health risk - Ni Liang; Zekun Li; Jie Sun; Nan Fu; Guoliang Zhong; Xianbiao Lin; Kang Mao; Peng Zhang; Zhaofeng Chang; Dong Yang; Wei Du; Guofeng Shen; et al. (Building and Environment, 2025)

Hydrochemical characteristics and evolution of geothermal waters in western Yunnan, China based on self-organizing map and hydrogeochemical simulation - Bo Li; Guangcai Wang; Fei Liu; Zheming Shi; Qingmin Kong; Shouchuan Zhang; Xin Yan; Fu Liao; Liang Guo; Chenglong Liu (Applied Geochemistry, 2025)

Broad‐Scale Meta‐Analysis of Drivers Mediating Adverse Impacts of Flow Regulation on Riparian Vegetation - Xiaolei Su; María Dolores Bejarano; Roland Jansson; Francesca Pilotto; Judith M. Sarneel; Feng Lin; Yi Wang; Fu Cai; Shan Wu; Bo Zeng (Global Change Biology, 2025)
Over two‐thirds of global rivers are subjected to flow regulation. Although it is widely recognized that flow regulation can adversely affect riparian vegetation—a critical component of river ecosystems—the specific roles of various drivers remain poorly understood. To address this gap, we conducted a broad‐scale meta‐analysis, aiming to elucidate how different factors mediate the adverse impacts of flow regulation on riparian vegetation. This meta‐analysis encompassed 59 papers, spanning 278 dams constructed on 146 rivers. We extracted data on four key indices of riparian vegetation: species richness and abundance of all riparian species, and those indices exclusively for non‐native species. Indices were compared between regulated and free‐flowing or pre‐damming rivers to quantify the impact of flow regulation. Our meta‐analysis revealed a moderate but significant reduction in the richness and abundance of all riparian species under flow regulation, coupled with a strong increase in the abundance of non‐native species. Riparian vegetation in arid and continental climate regions experienced stronger negative impacts than those in tropical and temperate climates. Furthermore, the adverse effects on riparian vegetation were more pronounced downstream of dams than upstream. Considering climate region, study identity, and relative position to the dam as random variables, it became evident that years since flow regulation emerged as the most important factor influencing species richness. Over time, richness gradually recovered from initially low levels. However, this recovery was slowed by increasing flow regulation intensity (percentage of annual runoff stored). Additionally, the impact was more evident in larger rivers. To support regulated river management, we recommend prioritizing the protection of riparian vegetation in arid and continental climates, with emphasis on areas downstream of dams, limiting flow regulation intensity, particularly in larger rivers, and monitoring non‐native species to prevent disproportionate spread.

QTL mapping and candidate gene identification for lower temperature tolerance and growth traits using whole genome re-sequencing in Argopecten scallops - Fu-Kai Wang; Pei-Can Zhu; Xiao-Tong Zhang; Kai Yu; Chun-De Wang; Bo Liu (Aquaculture, 2025)

An enhancer–promoter-transcription factor module orchestrates plant immune homeostasis by constraining camalexin biosynthesis - Ying Zhang; Meng Tang; Yi Zhang; Qinglin Cheng; Lijiang Liu; Wei Chen; Jiatao Xie; Jiasen Cheng; Yanping Fu; Bo Li; Daohong Jiang; Xiao Yu (Molecular Plant, 2025)

Can biodegradable film replace polyethylene film to obtain similar mulching effects on soil functions and maize productivity in irrigation region? A three-year experimental appraisal - Xiao-Bin Xiong; Peng-Yang Wang; Ze-Ying Zhao; Jing Wang; Shu-Tong Liu; Fu-Jian Mei; Wen-Ying Wang; Yi-Bo Wang; Xiang-Wen Fang; Ying Zhu; Jin-Lin Zhang; Ning Wang; et al. (Journal of Cleaner Production, 2025)

Experimental study on pressure drop and ice blockage characteristics of ice slurry flow in big-diameter pipes - Bo Yang; Daoke Tang; Weixing Yuan; Xiling Zhao; Lin Fu (International Journal of Refrigeration, 2025)

Microbiome changes and characteristics under nutrient injection for enhanced oil production at Daqing oilfield - Zi-Yue Fu; Wen-Tao Chen; Gui-Na Qi; Zhao-wei Hou; Yi-Fan Liu; Li-Bin Shou; Lei Zhou; Shi-Zhong Yang; Xiao-Lin Wu; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2025)

Robust and efficient synchronization for structural health monitoring data with arbitrary time lags - Shenghui Fu; Jie Wu; Qilin Zhang; Bo Xie (Engineering Structures, 2025)

Regularization by double complementary priors for full waveform inversion - Hongyu Qi; Zhenwu Fu; Yang Li; Bo Han; Longsuo Li (Computers & Geosciences, 2025)

Development of “environmentally friendly” super Escherichia coli strains that can completely biodegrade toluene - Yu Wang; Cen Qian; Yong-Dong Deng; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Yuan-Zhang Sun; Hong-Juan Han; Wen-Hui Zhang; Hao Zhang; et al. (Chemical Engineering Journal, 2025)

Nanoscale coordination polymer-coated microneedle patches against bacterial biofilm infection via hypoxia-enhanced copper ion interference therapy - Xinwei Fu; Shan Du; Jie Liang; Bo Wang; Yingqi Liu; Yunlong Yu; Liqun Xu; Peng Xue; Bin Wang; Yuejun Kang (Chemical Engineering Journal, 2025)

In-situ packing self-intumescent aerogel particles in rigid polyurethane foam towards thermal insulation, flame retardance and smoke suppression - Ning Yu; Ting Wang; Cheng-Xu Xu; Xue Gou; Ying-Jiao Zhan; Wenli An; Zhi-Cheng Fu; Jinni Deng; Hai-Bo Zhao; Ming-Jun Chen (Chemical Engineering Journal, 2025)

A domain-decomposition-based parallel approach for 3D geological modeling using radial basis functions interpolation on GPUs - Hong Li; Huizhu Ni; Jinming Fu; Bo Wan; Deping Chu; Fang Fang; Run Wang; Guoxi Ma; Xin Zhou (Earth Science Informatics, 2025)

Joint Retrieval of PM2.5 Concentration and Aerosol Optical Depth over China Using Multi-Task Learning on FY-4A AGRI - Bo Li; Disong Fu; Ling Yang; Xuehua Fan; Dazhi Yang; Hongrong Shi; Xiang’ao Xia (Advances in Atmospheric Sciences, 2025)

Life cycle assessment of hydrogenotrophic denitrification in membrane aerated biofilm reactors for sustainable wastewater treatment - Rui Li; Ming-yi Lu; Rong-bo Guo; Haoran Duan; Bing-jie Ni; Shan-fei Fu (Water Research, 2024)

Effects of microplastics separate exposure and co-exposure to 17β-estradiol on the productive performance of juvenile female Chinese mitten crab (Eriocheir sinensis) - Yang Fu; Jian Zhang; Yilong Cui; Bo Li; Siming Huo; Jiayu Du; Yanfei Li (Science of The Total Environment, 2024)

Manganese(III) dominants the mobilization of phosphorus in reducing sediments: Evidence from Aha reservoir, Southwest China - Quan Chen; Jing-fu Wang; Meng-qiang Zhu; Hai-bo Qin; Peng Liao; Zhi-tong Lu; Peng-cheng Ju; Jing-an Chen (Science of The Total Environment, 2024)

Introduction to special issue LED 2023 - Naomi Porat; Frank Preusser; Bo Li; Christophe Falgueres; Fu Xiao; Georgina King; Jakob Wallinga; Julie Durcan (Quaternary Geochronology, 2024)

An improved convolutional architecture for quantitative characterization of pore networks in fine-grained rocks using FIB-SEM - Bo Liu; Qamar Yasin; Mengdi Sun; Atif Ismail; David A. Wood; Xin Tian; Baiquan Yan; Li Fu (International Journal of Coal Geology, 2024)

Real-time monitoring of activated sludge flocs via enhanced mask region-based Convolutional Neural networks - Tie-Fu Xu; Cai-Ling He; Guo-Tao Wang; Bo-Wen Li; Yu Tao (Environmental Research, 2024)

Carbonate-mediated Mars-van Krevelen mechanism on CuxO/CeO2 catalysts for boosting CO oxidation - Xingwen Cha; Jinxin He; Yiqin Fu; Bo Jiang; Sajid Ali; Songbo Chen; Guowu Zhan (Chemical Engineering Journal, 2024)

Konjac glucomannan exerts regulatory effects on macrophages and its applications in biomedical engineering - Xi Pan; Qida Zong; Chun Liu; Huiying Wu; Bo Fu; Ye Wang; Wei Sun; Yinglei Zhai (Carbohydrate Polymers, 2024)

Chemical composition, odor characteristics and risk value analysis of odorants in particleboards - Fang Yang; Xianwu Zou; Liming Zhu; Bin Lv; Yuejin Fu; Bo Liu; Lina Tang; Qian Chen (Atmospheric Pollution Research, 2024)

Decoding PTEN: from biological functions to signaling pathways in tumors - Xueping Huang; Dongyan Zhang; Di Zhang; Jianran Guo; Guohao Gu; Yingying Wang; Guohao Wu; Chuanbao Wang; Bo Fu; Keyi Li (Molecular Biology Reports, 2024)

A liquefied long-runout loess landslide triggered by the Jishishan Ms6.2 earthquake on 18 December 2023 in Qinghai, China - Fawu Wang; Youqian Feng; Ye Chen; Bo Zhang; Zijin Fu; Hao Ma; Shengzhe Cao (Landslides, 2024)

Correlations and stoichiometric characteristics of C, N, and P contents in Juniperus saltuaria plants, litter, and soil in the Sygera Mountains, southeastern Xizang, China - Liangna Guo; Jiangrong Li; Fangwei Fu; Bo Zhang; Sijie Zhu; Yuzhuo Liu; Jieting Li; Ganggang Chen; Yibo Zhang (Journal of Mountain Science, 2024)

Diversity of biological activities of crude venom extracted from five species of South China Sea anemones - Panmin He; Ming Li; Jinxing Fu; Yanling Liao; Bo Yi; Bingmiao Gao (Frontiers in Marine Science, 2024)
Developing novel, efficient, and safe peptide drugs from sea anemones has aroused great interest in countries around the world today. Sea anemones contain complex protein and peptide toxins, which determine the diversity of their biological activities. In this study, a variety of activities were assessed for crude venom extracted from five species of South China Sea anemones, including hemolytic, enzyme inhibition, anticancer, insecticidal, analgesic and lethal activities. The most toxic sea anemone was found to be Heteractis magnifica , which has high lethal activity in mice with an LD 50 of 11.0 mg/kg. The crude venom of H. magnifica also exhibited a range of the most potent activities, including hemolytic, trypsin inhibitory, cytotoxic activity against U251 and A549 cells, insecticidal and analgesic activities. In addition, the crude venom of Stichodactyla haddoni was the most effective inhibitor of pepsin, and the crude venom of Heteractis crispa was extremely strong toxicity to HepG2 cells. These findings are of great significance for exploring the potential and application of South China Sea anemone resources, and are expected to provide new directions and possibilities for the development of novel anticancer drugs, analgesics and biopesticides.

The critical role of electron donating rate of pyrogenic carbon in mediating the degradation of phenols in the aquatic environment - Liang Zeng; Sizhe Yang; Quan Chen; Wang Fu; Min Wu; Patryk Oleszczuk; Bo Pan; Baoshan Xing (Water Research, 2024)

Rapid and extensive SARS-CoV-2 Omicron variant infection wave revealed by wastewater surveillance in Shenzhen following the lifting of a strict COVID-19 strategy - Yinghui Li; Chen Du; Ziquan Lv; Fuxiang Wang; Liping Zhou; Yuejing Peng; Wending Li; Yulin Fu; Jiangteng Song; Chunyan Jia; Xin Zhang; Mujun Liu; et al. (Science of The Total Environment, 2024)

TBiSeg: A transformer-based network with bi-level routing attention for inland waterway segmentation - Chuanmao Fu; Meng Li; Bo Zhang; Hongbo Wang (Ocean Engineering, 2024)

A numerical analysis of wave type and steepness effects on cylindrical buoy dynamic characteristics - Weijian Liu; Bo-Fu Wang; Jinlong Zhang; Yuhong Dong (Ocean Engineering, 2024)

Influences of released humic acids during thermal hydrolysis on sludge anaerobic digestion: New insights from the molecular weight of humic acids - Yaya Sun; Hongbo Liu; Jiaxin Wen; Hang Xiao; Mingze Shi; Xinlei Lu; Kai Shen; Xuedong Zhang; Bo Fu; Minhua Cui; Yajie Li; Salma Tabassum; et al. (Journal of Environmental Management, 2024)

The effect of structural changes on the activity of peroxidase with different initial state under high-pressure freezing - Zhanhong Liang; Yuanshan Yu; Bo Zou; Manqin Fu; Tenggen Hu; Xiaomeng Yin; Jin Wang; Yujuan Xu; Lina Cheng (Food Chemistry, 2024)

Blood mercury mediates the associations between fish consumption and serum uric acid levels among Chinese adults: A nationally representative study - Changzi Wu; Bing Wu; Yingli Qu; Hui Fu; Yue Chen; Yifu Lu; Saisai Ji; Liang Ding; Zheng Li; Qi Sun; Miao Zhang; Xu Zhang; et al. (Environmental Research, 2024)

The toxic effects and mechanisms of maternal exposure to Bisphenol F during gestation and lactation on lungs in female offspring mice - Jiayu Du; Siming Huo; Bo Li; Xuliang Zhang; Jian Zhang; Yang Fu; Bing Shao; Yanfei Li; Miao Song (Environmental Pollution, 2024)

Valence electronic engineering of hollow-nanocube-structured CoFeNi-layered double hydroxides for highly efficient oxygen evolution - Lu Liu; Lingxing Zan; Yunchuan Tu; Hongling Zhang; Dan Zhu; Zhe Li; Jiawen Zheng; Zhuangzhuang Zhang; Yu Sun; Qiang Weng; Jian Li; Qingbo Wei; et al. (Chemical Engineering Journal, 2024)

Dual zinco-phobic/-philic ferroelectric nanorods coated mesh for stable Zn anode - Jingwen Ma; Weishen Liu; Bo Fu; Jingji Zhang; Quan Zong; Huiwei Du; Tao Hong; Huanan Yu; Yongchun Ye; Jiangying Wang; Haijiao Xie (Chemical Engineering Journal, 2024)

Evaluation of the Regulation and Response of Ocean Heat Content to Typhoons in the Northwest Pacific Based on GDCSM_Argo - Han Su; Chunling Zhang; Bo Shu; Lifu Fu (Journal of Marine Science and Engineering, 2024)
The Northwest Pacific is a source of strong typhoons accompanied by significantly changing ocean heat content (OHC). Based on the GDCSM_Argo dataset, all typhoons within twenty years are considered to explore the regulation of OHC between 0 and 2000 m with typhoons in this study. The results show a weak correlation between OHC and typhoons but a strong correlation between ocean heat content uptake anomaly (OHUA) and typhoons by wavelet, lag/lead, and EOF analyses. The energy reserve effect by the OHUA on typhoon generation is most significant at a 3-month lag. The OHUA above 300 m primarily influences typhoons’ temporal and spatial characteristics. On the other hand, typhoons enhance vertical transmission of OHC through entrainment. A modified version of the Richardson number (Rohc) is used for the characterization of the hydrostatic stability between ocean layers. The entrainment is particularly strong in the Northwest Pacific north of 20° N, where Rohc is between −0.2 and 0. The OHC below the mixed layer also responds to typhoon disturbances but transports less heat vertically than the near-surface layers. Our results suggest that GDCSM_Argo provides reliable data support for the study of the relationship between OHC and typhoons.

Integrated transcriptomic and metabolomic analysis reveals the underlying mechanisms for male reproductive toxicity of polystyrene nanoplastics in mouse spermatocyte-derived GC-2spd(ts) cells - Hang Han; Zhen Zhang; Bo Xu; Liyang Ding; Hong Yang; Tiantian He; Xing Du; Xiuying Pei; Xufeng Fu (Toxicology in Vitro, 2024)

Aflatoxin B1 as a complicit in intestinal damage caused by Eimeria ovinoidalis in lambs: Novel insights to reveal parasite-gut battle - Pan Chen; Wen-li Ding; Bo-wen Xu; Mujeeb Ur Rehman; Kai-li Liu; Yan-feng He; Sen-yang Li; Fu-chun Jian; Shu-cheng(淑成) Huang(黄) (Science of The Total Environment, 2024)

Experimental study on the elastic response characteristics of a rotating body under an oblique water impact load - Shao-Bo Li; Fu-Ren Ming; Tong-Shuai Peng; Yu-Tong Sui (Ocean Engineering, 2024)

Research advances in detection of food adulteration and application of MALDI-TOF MS: A review - Danliangmin Song; Kai Dong; Shiyu Liu; Shiqian Fu; Feng Zhao; Chaoxin Man; Yujun Jiang; Kuangyu Zhao; Bo Qu; Xinyan Yang (Food Chemistry, 2024)

Characterization and immune role of class B scavenger receptor member 1 in spotted sea bass (Lateolabrax maculatus) - Yichen Fu; Chao Zhao; Changhong Lin; Bo Zhang; Lulu Yan; Bo Zhang; Pengfei Wang; Lihua Qiu (Fish & Shellfish Immunology, 2024)

Surface-controlled oxygen vacancy-rich Bi/BiVO4 Schottky junction for highly selective and active photocatalytic nitrogen fixation - Guanghua Xia; Yue Meng; Qiang Fu; Zhiling Huang; Bo Xie; Zheming Ni; Shengjie Xia (Chemical Engineering Journal, 2024)

Performance and mechanism investigation of Cu loading and S vacancy synergistic promotion of MoS2 catalyzed low-temperature water gas shift reaction: Experimental and theoretical calculations - Qiang Fu; Zhiling Huang; Yue Meng; Bo Xie; Zheming Ni; Shengjie Xia (Chemical Engineering Journal, 2024)

Self-condensation for enhancing the hydrophilicity of covalent organic polymers and photocatalytic hydrogen generation with unprecedented apparent quantum yield up to 500 nm - Islam M.A. Mekhemer; Ahmed M. Elewa; Mohamed M. Elsenety; Maha Mohamed Samy; Mohamed Gamal Mohamed; Ahmed Fouad Musa; Tse-Fu Huang; Tzu-Chien Wei; Shiao-Wei Kuo; Bo-Han Chen; Shang-Da Yang; Ho-Hsiu Chou (Chemical Engineering Journal, 2024)

Bayesian inversion of HFC-134a emissions in southern China from a new AGAGE site: Results from an observing system simulation experiment - Juan Li; Jianxiong Sheng; Lei Zhu; Bo Yao; Jing Wu; Dongchuan Pu; Lei Shu; Song Liu; Xicheng Li; Yuyang Chen; Xiaoxing Zuo; Yali Li; et al. (Atmospheric Environment, 2024)

Characteristics and ozone formation potentials of volatile organic compounds in a heavy industrial urban agglomeration of Northeast China - Yue Zhang; Bo You; Yijing Shang; Qiuyang Bao; Yanli Zhang; Xiaobing Pang; Li Guo; Jing Fu; Weiwei Chen (Air Quality, Atmosphere & Health, 2024)

Quantifying heavy metal and radionuclide contamination in fish and water proximal to a uranium tailings facility: A Linshui River basin investigation, China - Yan Jin; Bo Fu; Xiaofeng Wang (Journal of Trace Elements in Medicine and Biology, 2024)

Ancestral sequence reconstruction of the prokaryotic three-domain laccases for efficiently degrading polyethylene - Bo Zeng; Yishan Fu; Jiacai Ye; Penghui Yang; Shixiu Cui; Wenxuan Qiu; Yangyang Li; Taoxu Wu; Haiyun Zhang; Yachan Wang; Guocheng Du; Song Liu (Journal of Hazardous Materials, 2024)

Integrated metal carbonate thermal decomposition with in-situ CO2 conversion: Review and perspective - Bo Jin; Dongtao Fu; Xiaoju Xiang; Haibo Zhao; Haiyan Zhang; Daofeng Mei; Zhiwu Liang (Gas Science and Engineering, 2024)

Regulating the broadband near-infrared emission of Eu2+-doped Ca3Sc2Si3O12 phosphors through constructing defect for diversified applications - Chao Jiang; Quan Liu; Kaiyang Li; Yubo Feng; Yingkai Fu; Yue Li; Yicheng Zhang; Xu Qian; Bo Wei; Peng Du (Chemical Engineering Journal, 2024)

New approach for raw biogas: Production of single cell protein by sulfide-tolerant methane-oxidizing bacteria consortia - Hai-Ming Huang; Zhi-Xin Xue; Yu-Feng Jiang; Rui Li; Rong-Bo Guo; Xiao-Lei Fan; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Corrigendum to “2′-O-galloylhyperin attenuates LPS-induced acute lung injury via upregulation antioxidation and inhibition of inflammatory responses in vivo” [Chem. Biol. Interact. 304 (1 May 2019) 20–27] - Sun-Dong Zhang; Peng Wang; Jing Zhang; Wei Wang; Li-Ping Yao; Cheng-Bo Gu; Thomas Efferth; Yu-Jie Fu (Chemico-Biological Interactions, 2024)

Liriodendrin stimulates proliferation and milk protein synthesis of mammary epithelial cells via the PI3K-DDX18 signaling - Youwen Qiu; Mingming Fu; Minghui Zhang; Bo Qu; Zhen Zhen (In Vitro Cellular & Developmental Biology - Animal, 2024)

Coupling coordination analysis and obstacle factors of water-energy-environment-economy in the Yellow River Basin - Bo Pang; Xiaoxing Li; Yao Fu (Journal of Cleaner Production, 2024)

Boron and nitrogen hydrothermal co-doped sludge biochar towards efficiently activate peroxymonosulfate for sulfamethoxazole degradation - Huanhuan Wang; Quanbin Zhang; Huifu Ji; Youqi Zhang; Bo Fu; Yunjie Wu; Yongzhen Ding (Journal of Cleaner Production, 2024)

Impact of thermal ultrasound on enzyme inactivation and flavor improvement of sea cucumber hydrolysates - Yi-chao Cheng; Dan-li Jin; Wen-tao Yu; Bo-yang Tan; Jing-jing Fu; Yue-wen Chen (Food Chemistry, 2024)

Shear-induced permeability evolution of natural fractures in granite: Implications for stimulation of EGS reservoirs - Xuefeng Li; Fengshou Zhang; Nailing Xiu; Dingwei Weng; Bo Cai; Haifeng Fu (Engineering Geology, 2024)

Regulatory mechanisms of biochar alleviating ammonia inhibition to methanogenesis during long-term operation of anaerobic membrane bioreactor treating swine wastewater - Bo Zhang; Gaojun Wang; Xiang Zhang; Peng Fu; Lu Chen; Yizhi Chen; Qian Li; Rong Chen (Chemical Engineering Journal, 2024)

Both Short-term and Long-term Ozone Pollution Alters the Chemical Composition of rice Grain - Guoyou Zhang; Xiaoya Pan; Yaxin Hu; Rong Cao; Qinan Hu; Rao Fu; Risalat Hamdulla; Bo Shang (Bulletin of Environmental Contamination and Toxicology, 2024)

Molecular mechanism of a coastal cyanobacterium Synechococcus sp. PCC 7002 adapting to changing phosphate concentrations - Qiao-Wei Sun; Yu Gao; Jordan Wang; Fei-xue Fu; Cheng-Wen Yong; Shuang-Qing Li; Hai-Long Huang; Wei-Zhong Chen; Xin-Wei Wang; Hai-Bo Jiang (Marine Life Science & Technology, 2024)
Phosphorus concentration on the surface of seawater varies greatly with different environments, especially in coastal. The molecular mechanism by which cyanobacteria adapt to fluctuating phosphorus bioavailability is still unclear. In this study, transcriptomes and gene knockouts were used to investigate the adaptive molecular mechanism of a model coastal cyanobacterium Synechococcus sp. PCC 7002 during periods of phosphorus starvation and phosphorus recovery (adding sufficient phosphorus after phosphorus starvation). The findings indicated that phosphorus deficiency affected the photosynthesis, ribosome synthesis, and bacterial motility pathways, which recommenced after phosphorus was resupplied. Even more, most of the metabolic pathways of cyanobacteria were enhanced after phosphorus recovery compared to the control which was kept in continuous phosphorus replete conditions. Based on transcriptome, 54 genes potentially related to phosphorus-deficiency adaptation were selected and knocked out individually or in combination. It was found that five mutants showed weak growth phenotype under phosphorus deficiency, indicating the importance of the genes ( A0076 , A0549-50 , A1094 , A1320 , A1895 ) in the adaptation of phosphorus deficiency. Three mutants were found to grow better than the wild type under phosphorus deficiency, suggesting that the products of these genes ( A0079 , A0340 , A2284–86 ) might influence the adaptation to phosphorus deficiency. Bioinformatics analysis revealed that cyanobacteria exposed to highly fluctuating phosphorus concentrations have more sophisticated phosphorus acquisition strategies. These results elucidated that Synechococcus sp. PCC 7002 have variable phosphorus response mechanisms to adapt to fluctuating phosphorus concentration, providing a novel perspective of how cyanobacteria may respond to the complex and dynamic environments.

Correction to: Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao‑Bo Li; Yan‑Xun Han; Zi‑Yue Fu; Yu‑Chen Zhang; Min Fan; Shu‑Jia Sang; Xi‑Xi Chen; Bing‑Yu Liang; Yu‑Chen Liu; Peng‑Cheng Lu; Hua‑Wei Li; Hai‑Feng Pan; et al. (Environmental Science and Pollution Research, 2024)

Study on vibration effects of high-speed train operation on viaduct and subgrade-viaduct transition sections in loess area - Jin Chen; Xiaopeng Suo; Yixuan Li; Zhenjia Xu; Zhiren Hu; Yuewen Ma; Haonan Li; Bo Fu (Soil Dynamics and Earthquake Engineering, 2024)

Modelling the dynamic gas/particle partitioning process of semi-volatile organic compounds emitted from point sources: Quantitative analysis and impact assessment - Fu-Jie Zhu; Li-Fu Wang; Long-Ze Qu; Wan-Li Ma; Geng-Bo Ren; Ben-Hang Li; Xiao-Dong Ma (Science of The Total Environment, 2024)

Lanthanum-modified pyroaurite as a geoengineering tool to simultaneously sink Microcystis cyanobacteria and immobilize phosphorus in eutrophic water - Zhaoyang Shen; Mengjie Zhou; Yanyang Zhang; Xudong Sun; Bo Kong; Wanyi Fu; Zhichao Yang; Chao Shan; Bingcai Pan (Science of The Total Environment, 2024)

Tomato NAC transcription factor NOR-like1 positively regulates tomato fruit softening - Zhen-Zhen Peng; Hong-Li Li; Gang-Shuai Liu; Xiao Su; Xiaodan Zhao; Donald Grierson; Lan-Ting Xiang; Jian-Lin He; Gui-Qin Qu; Hong-Liang Zhu; Ben-Zhong Zhu; Yun-Bo Luo; et al. (Postharvest Biology and Technology, 2024)

Nanobubbles improve peroxymonosulfate-based advanced oxidation: High efficiency, low toxicity/cost, and novel collaborative mechanism - Jun Bo Zhang; Jia Jie Zou; Chaomeng Dai; Jiajun Hu; Xueji You; Min-tian Gao; Jixiang Li; Rongbing Fu; Yalei Zhang; Kah Hon Leong; Xing Song Xu (Journal of Hazardous Materials, 2024)

The complete degradation of 1,2-dichloroethane in Escherichia coli by metabolic engineering - Yong-Dong Deng; Wen-Hui Zhang; Zhi-Hao Zuo; Hao Zhang; Jing Xu; Jian-Jie Gao; Bo Wang; Zhen-Jun Li; Xiao-Yan Fu; Li-Juan Wang; Yu Wang; Yong-Sheng Tian; et al. (Journal of Hazardous Materials, 2024)

Effects of saturated fluids on petrophysical properties of hot dry rock at high temperatures: An experimental study - Qiuyan Wang; Daobing Wang; Wei Fu; Chen Zheng; Dongliang Sun; Bo Yu (Geothermics, 2024)

Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao-Bo Li; Yan-Xun Han; Zi-Yue Fu; Yu-Chen Zhang; Min Fan; Shu-Jia Sang; Xi-Xi Chen; Bing-Yu Liang; Yu-Chen Liu; Peng-Cheng Lu; Hua-Wei Li; Hai-Feng Pan; et al. (Environmental Science and Pollution Research, 2024)
Air pollution can cause disease and has become a major global environmental problem. It is currently believed that air pollution may be related to the progression of SSNHL. As a rapidly developing city in recent years, Hefei has serious air pollution. In order to explore the correlation between meteorological variables and SSNHL admissions, we conducted this study. This study investigated the short-term associations between SSNHL patients admitted to the hospital and Hefei climatic variables. The daily data on SSNHL-related hospital admissions and meteorological variables containing mean temperature (T-mean; °C), diurnal temperature range (DTR; °C), atmospheric pressure (AP; Hp), and relative humidity (RH; %), from 2014 to 2021 (2558 days), were collected. A time-series analysis integrating distributed lag non-linear models and generalized linear models was used. PubMed, Embase, Cochrane Library, and Web of Science databases were searched. Literature published up to August 2023 was reviewed to explore the potential impact mechanisms of meteorological factors on SSNHL. The mechanisms were determined in detail, focusing on wind speed, air pressure, temperature, humidity, and air pollutants. Using a median of 50.00% as a baseline, the effect of exceedingly low T-mean in the single-day hysteresis effect model began at a lag of 8 days (RR = 1.032, 95% CI: 1.001 ~ 1.064). High DTR affected the admission rate for SSNHL on lag 0 day. The significance of the effect was the greatest on that day (RR = 1.054, 95% CI: 1.007 ~ 1.104) and then gradually decreased. High and exceedingly high RH affected the admission rate SSNHL on lag 0 day, and these effects lasted for 8 and 7 days, respectively. There were significant associations between all grades of AP and SSNHL. This is the first study to assess the effect of meteorological variables on SSNHL-related admissions in China using a time-series approach. Long-term exposures to high DTR, RH values, low T-mean values, and all AP grades enhance the incidence of SSNHL in residents. Limiting exposure to extremes of ambient temperature and humidity may reduce the number of SSNHL-related hospital visits in the region. It is advisable to maintain a suitable living environment temperature and avoid extreme temperature fluctuations and high humidity. During periods of high air pollution, it is recommended to stay indoors and refrain from outdoor exercise.

Effects of dietary lipid and protein levels on metamorphosis, growth, metabolism and gut microbiota of tadpole (Lithobates catesbeianus) - Bo Zhu; Lei Zhong; Chuang Shao; Wenjie Xu; Shuhui Xiang; Shuiquan Fu; Yi Hu (Aquaculture, 2024)

Chronic enhanced nitrogen deposition and elevated precipitation jointly benefit soil microbial community in a temperate forest - An Yang; Bo Song; Weixin Zhang; Tianning Zhang; Xiaowei Li; Hongtao Wang; Dong Zhu; Jie Zhao; Shenglei Fu (Soil Biology and Biochemistry, 2024)

A general pattern of plant traits and their relationships with environmental factors and microbial life-history strategies - Jian-Guo Ma; Xiao-Bo Wang; Fu-Jiang Hou (Science of The Total Environment, 2024)

Seasonal characterization of chemical and optical properties of water-soluble organic aerosol in Beijing - Bo You; Zhiqiang Zhang; Aodong Du; Yan Li; Jiaxing Sun; Zhijie Li; Chun Chen; Wei Zhou; Weiqi Xu; Lu Lei; Pingqing Fu; Shengjie Hou; et al. (Science of The Total Environment, 2024)

Turbulent transports in the flow around a rectangular cylinder with different aspect ratios - Jiang-hua Li; Bo-fu Wang; Xiang Qiu; Quan Zhou; Shi-xiao Fu; Yu-lu Liu (Ocean Engineering, 2024)

Pickering extremulsion rich in lipophilic phytochemicals: Preparation, characterization and application - Xu Han; Cong-Jia Duan; Zi-Fei Wei; Jian Xu; Cheng-Dong Nie; Yuan-Hang Chang; Bo-wen Zhai; Yu-Jie Fu (Journal of Food Engineering, 2024)

Novel MOF-derived Fe/CoNHDC-400@GF cathode with improved in-situ catalytic degradation of chloroquine phosphate during heterogeneous electro-Fenton process - Bo Fu; Zihao Yan; Zhirong Sun (Journal of Environmental Chemical Engineering, 2024)

A microfiber biosensor for detection of AKT protein in human embryonic kidney cell lysate based on the vernier effect - Zhichao Zhang; Zhen Tian; Yicun Yao; BingwuYang; Jingao Zhang; Haili Ma; Kuiru Wang; Binbin Yan; Xinzhu Sang; Chongxiu Yu; Bo Fu; Jinhui Yuan; et al. (Chemical Engineering Journal, 2024)

Assessing the inundation risk of cultural heritages along the southwestern coast of Taiwan: present and future - Wen-Ray Su; Yu-Hua Chen; Huei-Shuin Fu; Tzu-Yin Chang; Wei-Bo Chen (Regional Environmental Change, 2024)

Molecular Mechanism of Yangshen Maidong Decoction in the Treatment of Chronic Heart Failure based on Network Pharmacology, Molecular Docking, and Molecular Dynamics Simulations - Wei Cheng; Bo-Feng Zhang; Na Chen; Qun Liu; Xin Ma; Xiao Fu; Min Xu (Cell Biochemistry and Biophysics, 2024)

E3 Ubiquitin Ligase ASB14 Inhibits Cardiomyocyte Proliferation by Regulating MAPRE2 Ubiquitination - Yanpeng Yang; Dongpu Ma; Bo Liu; Xu Sun; Wei Fu; Feifei Lv; Chunguang Qiu (Cell Biochemistry and Biophysics, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Anthropogenic-induced ecological risks on marine ecosystems indicated by characterizing emerging pollutants in Pearl River Estuary, China - He Liu; Bo Zhao; Meng Jin; Rui Wang; Zirong Ding; Xiong Wang; Wenjie Xu; Qianghua Chen; Rizhu Tao; Jianping Fu; Danping Xie (Science of The Total Environment, 2024)

The role of superoxide anion to Cr(VI) reduction by pine biochar - Wang Fu; Min Wu; Quan Chen; Yundie Liang; Hongbo Peng; Liang Zeng; Bo Pan (Journal of Hazardous Materials, 2024)

An overview of the Qiangtang Basin: Geology, hydrocarbon resources and the role of the Tethyan evolution - Jian Wang; Xiugen Fu; Hengye Wei; Bo Zheng; Zhongwei Wang; Lijun Shen; Ahmed Mansour (Journal of Asian Earth Sciences, 2024)

Sulphur evolution in acidic and alkaline geothermal water related to magma in the Rehai geothermal field in the southeastern Tibet Plateau based on stable hydrogen, oxygen, sulphur isotopes - Bo Li; Qingmin Kong; Fu Liao; Guangcai Wang; Fei Liu; Liang Guo; Chenglong Liu; Zheming Shi (Geothermics, 2024)

Probing into the radiative mechanisms and drivers influencing urban heat-cold islands and urban pollution islands during heavy-haze events in a cold megacity of Northeast China - Stephen Dauda Yabo; Lu Lu; Lixin Ma; Bo Li; Donglei Fu; Fan Meng; Jinpan Jiang; Xie Shengjin; Wei Zhang; Hong Qi (Atmospheric Research, 2024)

A thermal–mechanical coupled DEM model for deep shale reservoir: the effects of temperature and anisotropy - Ziyang Zhou; Fengshou Zhang; Haifeng Fu; Nailing Xiu; Baoshan Guan; Bo Cai (Rock Mechanics and Rock Engineering, 2024)

Green manure substitution for potassium fertilizer promotes agro-ecosystem multifunctionality via triggering interactions among soil, plant and rhizosphere microbiome - Qing Zeng; Mei Yin; Li-Bo Fu; Brajesh K. Singh; Si-Yi Liu; Hua Chen; An-Hui Ge; Li-Li Han; Li-Mei Zhang (Plant and Soil, 2024)

Impact of a clustered rainfall-induced geo-hydrological disaster on densely populated gully villages in Fuyang District, Hangzhou City, Zhejiang Province, China on 22 July 2023 - Fawu Wang; Bo Zhang; Qing Lü; Hao Ma; Ye Chen; Zijin Fu; Jianyi Wu (Landslides, 2024)

Long-chain acyl-CoA synthetase 4-mediated mitochondrial fatty acid metabolism and dendritic cell antigen presentation - Yan Li; Wenlong Fu; JinYing Xiang; Yinying Ren; Yuehan Li; Mi Zhou; Jinyue Yu; Zhengxiu Luo; Enmei Liu; Zhou Fu; Bo Liu; Fengxia Ding (Inflammation Research, 2024)

Proteomics Sequencing Reveals the Role of TGF-β Signaling Pathway in the Peripheral Blood of Offspring Rats Exposed to Fluoride - Fang-fang Yu; Shui-yuan Yu; Lei-zhen Duan; Shuo Yang; Xiang-bo Hou; Yu-hui Du; Ming-hui Gao; Juan Zuo; Lei Sun; Xiao-li Fu; Zhi-yuan Li; Hui Huang; et al. (Biological Trace Element Research, 2024)

CO2 sequestration in microbial electrolytic cell-anaerobic digestion system combined with mineral carbonation for sludge hydrolysate treatment - Wanying He; He Liu; Bo Fu; Chongjun Chen; Chao Zhang; Jing Li (Waste Management, 2024)

The hepatotoxicity of hexafluoropropylene oxide trimer acid caused by apoptosis via endoplasmic reticulum-mitochondrial crosstalk - Jiayu Du; Xuliang Zhang; Bo Li; Siming Huo; Jian Zhang; Yang Fu; Miao Song; Bing Shao; Yanfei Li (Science of The Total Environment, 2024)

Responses in reef-building corals to wildfire emissions: Heterotrophic plasticity and calcification - Bo Qin; Kefu Yu; Yichen Fu; Yu Zhou; Yanliu Wu; Wenqian Zhang; Xiaoyan Chen (Science of The Total Environment, 2024)

Screening of toluene absorbents based on molecular simulation and experimental investigation on novel compound solvents - Li Wang; Kefan Chao; Zekai Jin; Muhua Chen; Xinbao Zhu; Gang Zhang; Bo Fu (Process Safety and Environmental Protection, 2024)

Optimization of alkaline hydrothermal treatment for humic acids production from corn straw digestate using the response surface methodology - Shuai-Ze Han; Bo-Tao Zhang; Man-Qian Wang; Rong-Bo Guo; Shan-Fei Fu (Journal of Environmental Chemical Engineering, 2024)

Efficient trimethoprim removal via cooperation of radical and non-radical pathways in UV/peroxymonosulfate: Kinetics, mechanisms and disinfection by-products-associated risks - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Juan Wang; Yu-Qiong Gao; Dong-Su Bi; Bo Wang; Xing-Yan Mu; Xiao-Jun Hu (Journal of Environmental Chemical Engineering, 2024)

Crystal mush rejuvenation in the formation of Triassic dacites in Mengku, SE Tibetan Plateau - Feng Cong; Fu-Yuan Wu; Wen-Chang Li; Zai-Bo Sun; Xiao-Chi Liu; De-Feng He; Wei-Qiang Ji; Fang-Yang Hu; Shao-Hua Zhang; Xiao-Ming Huang (Journal of Asian Earth Sciences, 2024)

Silurian–Devonian construction of active continental margin in the southwestern Paleo-Asian Ocean witnesses the modification of fluvial system by early land plants - Yan Xu; Bo Liu; Yuyang Liu; Bao-Fu Han; Hao Sun; Chaoqiang Chen; Min Qin (Gondwana Research, 2024)

A review of combined fouling on high-pressure membranes in municipal wastewater reuse: Behaviors, mechanisms, and pretreatment mitigation strategies - Xiao-Yang Liu; Yu-Bo Chen; Jie Fu; Xianzheng Zhu; Long-Yi Lv; Li Sun; Guang-Ming Zhang; Zhi-Jun Ren (Chemical Engineering Journal, 2024)

Concentrated fireworks display-induced changes in aerosol vertical characteristics and atmospheric pollutant emissions - Lingjian Duanmu; Weiwei Chen; Li Guo; Jing Fu; Bo You; Hongwu Yang; Tianshu Zhang (Atmospheric Environment, 2024)

Comprehensive analysis of MAPK gene family in upland cotton (Gossypium hirsutum) and functional characterization of GhMPK31 in regulating defense response to insect infestation - Fuqiu Wang; Sijia Liang; Guanying Wang; Qiongqiong Wang; Zhongping Xu; Bo Li; Chunyang Fu; Yibo Fan; Tianyu Hu; Muna Alariqi; Amjad Hussain; Jinglin Cao; et al. (Plant Cell Reports, 2024)
Key message The transcriptomic, phenotypic and metabolomic analysis of transgenic plants overexpressing GhMPK31 in upland cotton revealed the regulation of H 2 O 2 burst and the synthesis of defensive metabolites by GhMPK31 . Abstract Mitogen-activated protein kinases (MAPKs) are a crucial class of protein kinases, which play an essential role in various biological processes in plants. Upland cotton ( G. hirsutum ) is the most widely cultivated cotton species with high economic value. To gain a better understanding of the role of the MAPK gene family, we conducted a comprehensive analysis of the MAPK gene family in cotton. In this study, a total of 55 GhMPK genes were identified from the whole genome of G. hirsutum . Through an investigation of the expression patterns under diverse stress conditions, we discovered that the majority of GhMPK family members demonstrated robust responses to abiotic stress, pathogen stress and pest stress. Furthermore, the overexpression of GhMPK31 in cotton leaves led to a hypersensitive response (HR)-like cell death phenotype and impaired the defense capability of cotton against herbivorous insects. Transcriptome and metabolomics data analysis showed that overexpression of GhMPK31 enhanced the expression of H 2 O 2 -related genes and reduced the accumulation of defensive related metabolites. The direct evidence of GhMPK31 interacting with GhRBOHB (H 2 O 2 -generating protein) were found by Y2H, BiFC, and LCI. Therefore, we propose that the increase of H 2 O 2 content caused by overexpression of GhMPK31 resulted in HR-like cell death in cotton leaves while reducing the accumulation of defensive metabolites, ultimately leading to a decrease in the defense ability of cotton against herbivorous insects. This study provides valuable insights into the function of MAPK genes in plant resistance to herbivorous insects.

Functions and targets of miRNAs in pharmacological and toxicological effects of major components of Tripterygium wilfordii Hook F - Wei Pan; Bo Yang; Dongxiu He; Linxi Chen; Chengxiao Fu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Nrf2-mediated ferroptosis of spermatogenic cells involved in male reproductive toxicity induced by polystyrene nanoplastics in mice - Xufeng Fu; Hang Han; Hong Yang; Bo Xu; Wenjie Dai; Ling Liu; Tiantian He; Xing Du; Xiuying Pei (Journal of Zhejiang University-SCIENCE B, 2024)

Study on regeneration characteristics of granular activated carbon using ultrasonic and thermal methods - Kaizheng Shi; Zhang Xu; Yong Wang; Weisong Fu; Bo Chen (Environmental Science and Pollution Research, 2024)

Porous hydrochar loaded nZVI as an efficient catalyst to activate persulfate for phenol degradation: Performance and mechanism - Bo Cao; Jianhua Qu; Wenhui Bian; Qiqi Hu; Xinyan Fu; Guangshan Zhang; Yuezhi Zhang; Yue Tao; Zhao Jiang; Ying Zhang (Journal of Cleaner Production, 2024)

An evaluation model for in-situ bioremediation technology of petroleum hydrocarbon contaminated soil - Tao Chen; Yafu Zhang; Bo Fu; Wenbiao Huang (Environmental Pollution, 2024)

TransROTA: A code for solving collisionality-extended Braginskii's closure formalism for toroidally-rotating plasmas with nonlinear successive overrelaxation - Cheonho Bae; Yifei Jin; Bo Lyu; Jia Fu; Fudi Wang; Hongming Zhang (Computer Physics Communications, 2024)

Contrasting range changes of Bergenia (Saxifragaceae) species under future climate change in the Himalaya and Hengduan Mountains Region - Li Qiu; Qing-Li Fu; Hans Jacquemyn; Kevin S. Burgess; Jia-Jing Cheng; Zhi-Qiong Mo; Xiao-Dong Tang; Bo-Yun Yang; Shao-Lin Tan (Theoretical and Applied Climatology, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Curcumin inhibits the development of colorectal cancer via regulating the USP4/LAMP3 pathway - Hai Wei; Xianzhe Li; Fu Liu; Yuan Li; Bin Luo; Xin Huang; Hang Chen; Bo Wen; Pei Ma (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Knockdown of SIK3 in the CA1 Region can Reduce Seizure Susceptibility in Mice by Inhibiting Decreases in GABAAR α1 Expression - Zhen-Fu Jiang; Li-Na Xuan; Xiao-Wan Sun; Shao-Bo Liu; Jian Yin (Molecular Neurobiology, 2024)

Effects of terrestrial input on heavy metals in Zhanjiang Bay, a typical subtropical bay in the South China Sea - Demeng Peng; Jibiao Zhang; Chuping Fan; Bo Zhu; Miaojian Fu; Peng Zhang (Marine Pollution Bulletin, 2024)

Numerical simulation method and deterioration analysis of load-bearing performance of tunnel linings containing cold joints in plain concrete - Huang-Shi Deng; He-Lin Fu; Yi-Min Wu; Yi-Bo Zhao; Hai-Dong Yi (Tunnelling and Underground Space Technology, 2024)

The differences in plant invasion in two types of shorelines under flow regulation of the Three Gorges Reservoir - Yi Wen; Xiaolei Su; Fu Cai; Rongyan Qian; María Dolores Bejarano; Shan Wu; Qin Yang; Xudong Liu; Bo Zeng (Science of The Total Environment, 2024)

Diisoprenyl-cyclohexene-type meroterpenoids from a mangrove endophytic fungus Aspergillus sp. GXNU-Y65 and their anti-nonalcoholic steatohepatitis activity in AML12 cells - Feng Qin; Li Luo; Yu-Chen Liu; Xiang-Long Bo; Fu-Rong Wu; Fan-Fan Wang; Mei-Jing Tan; You-Quan Wei; Xiao-Bing Dou; Cai Yi Wang; Xi-Shan Huang; Heng-Shan Wang (Phytochemistry, 2024)

Two new monoterpenoids from the roots of Paeonia lactiflora and their neuroprotective activities - Bo Fu; Jin-Ling Zhang; Xin Meng; Jia-Tong Wu; Yan Liu; Yu-Qing Wang; Yi-Qiang Zhang; Juan Pan; Wei Guan; Rui-Feng Fan; Anam Naseem; Hai-Xue Kuang; et al. (Phytochemistry Letters, 2024)

Iron oxyhydroxide catalyzes production of artificial humic substances from waste biomass - Xinyu Chen; Bo Yang; Hao Zhou; Patrycja Boguta; Xinying Fu; Andrei Ivanets; Alexander A. Ratko; Tatyana Kouznetsova; Yongqi Liu; Xiaoyan He; Dongmei Zhao; Xintai Su (Journal of Environmental Management, 2024)

Comparing the mechanisms of syntrophic volatile fatty acids oxidation and methanogenesis recovery from ammonia stress in regular and biochar-assisted anaerobic digestion: Different roads lead to the same goal - Gaojun Wang; Peng Fu; Yan Su; Bo Zhang; Mengyuan Zhang; Qian Li; Jianfeng Zhang; Yu-You Li; Rong Chen (Journal of Environmental Management, 2024)

Acoustoelastic DZ-MT model for stress-dependent elastic moduli of fractured rocks - Bo-Ye Fu; Li-Yun Fu (International Journal of Rock Mechanics and Mining Sciences, 2024)

Automatic pore structure analysis in organic-rich shale using FIB-SEM and attention U-Net - Qamar Yasin; Bo Liu; Mengdi Sun; Ghulam Mohyuddin Sohail; Atif Ismail; Mariusz Majdanski; Naser Golsanami; Yan Ma; Xiaofei Fu (Fuel, 2024)

Preparation and characterization of micro-arc oxidation biological coatings on magnesium alloys containing graphene oxide - Jing Wang; Zhanghua Fu; Hao Liu; Wei Zhao; Bo Zhu; Jinhe Dou; Huijun Yu; Chuanzhong Chen (Chemical Engineering Journal, 2024)

Biogas upgrading by biotrickling filter: Effects of temperature and packing materials - Jie-Hua Huang; Xiao-Lei Fan; Rui Li; Meng-Ting Sun; Hua Zou; Yi-Feng Zhang; Rong-Bo Guo; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Eco-friendly and stable triclosan removal from groundwater using peroxyacetic acid activated with biochar produced from saccharification residues - Wang Kai Tong; Chaomeng Dai; Chenyan Jia; Jiajun Hu; Min-tian Gao; Jixiang Li; Jun Bo Zhang; Han Tang; Yucang Liang; Wei Teng; Zhi Li; Shuguang Liu; et al. (Chemical Engineering Journal, 2024)

Superior toughness Anticorrosion-Bioactive integrated multilayer coating with excellent adhesion for biodegradable Magnesium-Based stents - Jiayi Zhang; Zhen Xiang; Xingrong Ren; Bo Zhang; Daihua Fu; Yunbing Wang (Chemical Engineering Journal, 2024)

Long-term impact of nano zero-valent iron on methanogenic activity, microbial community structure, and transcription activity in anaerobic wastewater treatment system - Runhua Su; Huimin Fu; Lili Ding; Bo Fu; Su He; Haijun Ma; Haidong Hu; Hongqiang Ren (Bioresource Technology, 2024)

Petrogenesis and tectonic implications of the Silurian adakitic granitoids in the eastern segment of the Qilian Orogenic Belt, Northwest China - Jiao-Long Zhao; Xiao-Jun Huang; Pei-Qing Hu; Zhen-Xi Yang; Ying Fan; Er-Teng Wang; Fu-Bo Yang; Jing-Yu Zhang (Acta Geochimica, 2024)

Rare earth element behaviors of groundwater in overlying aquifers under the influence of coal mining in northern Ordos Basin, China - Fengxia Liu; Guangcai Wang; Bo Li; Chenyu Wang; Shen Qu; Fu Liao (Environmental Science and Pollution Research, 2024)

Distribution Characteristics and Factors Controlling Different Phosphorus Fractions in the Soils and Sediments of an Inland Lagoon - Kun Yuan; Rui Wang; Bo He; Guowei Fu; Yanwei Song; Lixin Pei; Shichao Fan; Fangyi Gao (Journal of Marine Science and Engineering, 2024)
Lagoons, significant coastal wetlands, stand out for their vital role in the cycles and transformations of phosphorus. However, the relationship between the spatial distributions of various phosphorus forms in the soil and sediments of lagoon areas remains unclear. This study investigated the phosphorus fractions and distribution patterns in the soil and sediments from Shimei Inland Sea, Hainan Province, China, and identified the factors controlling phosphorus distribution and its relationship with lagoon eutrophication. The results revealed significant enrichment of inorganic phosphorus (IP) in the Shimei Inland Sea (64.1–679.0 mg/kg) and offshore areas (56–627.2 mg/kg), while organic phosphorus (OP) was relatively concentrated in land (60–744.3 mg/kg), suggesting that the productivity of the terrestrial ecosystem controlled the OP content and IP formed from the mineralization of OP was more likely to leach into the water and combine with minerals. Total phosphorus (TP) content was negatively affected by pH, and organic matter, cation exchange capacity and iron/aluminum oxides showed significant positive correlations with TP content. These findings highlighted the coupled impact of soil and sediment physicochemical properties on phosphorus enrichment and transformation, providing theoretical support for the ecological restoration of ecosystems in tropical coastal wetlands.

Global predictions of topsoil organic carbon stocks under changing climate in the 21st century - Bo Chen; Qikai Lu; Lifei Wei; Wenqiang Fu; Zeyang Wei; Shuang Tian (Science of The Total Environment, 2024)

Differences in soil microbial community structure and assembly processes under warming and cooling conditions in an alpine forest ecosystem - Fangwei Fu; Yueyao Li; Bo Zhang; Sijie Zhu; Liangna Guo; Jieting Li; Yibo Zhang; Jiangrong Li (Science of The Total Environment, 2024)

Self-assembled Fe3O4-NH2 @g-C3N4 composite for magnetic solid-phase extraction of benzophenones in sea water and lake water coupled with LC-MS/MS determination - Man-Man Wang; Zi-Ling Li; Han Wu; Ke-Yan Chen; Fan Guo; Gui-Fu Zuo; Yu He; Xue-Bo Yin (Journal of Hazardous Materials, 2024)

Identification and analysis of microplastics in human lower limb joints - Zhuo Li; Yifan Zheng; Zulipikaer Maimaiti; Jun Fu; Fan Yang; Zhi-Yuan Li; Yanli Shi; Li-Bo Hao; Ji-Ying Chen; Chi Xu (Journal of Hazardous Materials, 2024)

Overlooked encounter process that affects physical behaviors of stabilized nanoscale zero-valent iron during in situ groundwater remediation - Yujie Xie; Miaoyue Zhang; Lihang Ma; Ting Du; Dan Zhou; Ming-Lai Fu; Baoling Yuan; Xiao-yan Li; Yi-bo Hu (Journal of Hazardous Materials, 2024)

Plasma-catalyzed combined dynamic wave scrubbing: A novel method for highly efficient removal of multiple pollutants from flue gas at low temperatures - Wei Xie; Tao Zhu; Bo Yuan; Shunjiang Fu; Zhishan Mao; Zefu Ye; Zhujun Zhu; Xing Zhang (Journal of Hazardous Materials, 2024)

Mechanistic insights into synergistic facilitation of copper/zinc ions and dewatered swine manure-derived biochar on anaerobic digestion of swine wastewater - Gaojun Wang; Changxi Sun; Peng Fu; Bo Zhang; Jinglin Zhu; Qian Li; Jianfeng Zhang; Rong Chen (Environmental Research, 2024)

Enhancing flame retardancy, mechanical durability, and anti-aging property of polyurethane foam via novel cyclic phosphonate - Zhi-Cheng Fu; Fa-Yang Bu; Zhe-Peng Li; Ting Wang; Jin-Ni Deng; Hai-Bo Zhao; Sheng-Chao Huang; Yu-Zhong Wang; Ming-Jun Chen (Chemical Engineering Journal, 2024)

Solar-driven biomass chemical looping gasification using Fe3O4 for syngas and high-purity hydrogen production - Dequan Xu; Bo Wang; Xian Li; Yoke Wang Cheng; Wenming Fu; Yanjun Dai; Chi-Hwa Wang (Chemical Engineering Journal, 2024)

4-Hydroxybenzenesulfonic acid triggers rapid preparation of phenolic aerogel composites by ambient pressure drying - Xi Zhao; Lin Chen; Peng-Gang Su; Lin-Xi Xiao; Hai-Bo Zhao; Teng Fu; Xiu-Li Wang; Yu-Zhong Wang (Chemical Engineering Journal, 2024)

A multitemporal snow-covered remote sensing image matching method considering global and contextual features - Jian Zhang; Zhitao Fu; Shaochen Zhang; Ruihong Li; Bo-Hui Tang (International Journal of Remote Sensing, 2023)

Targeted degradation of naphthalene by peroxymonosulfate activation using molecularly imprinted biochar - Xueji You; Chaomeng Dai; Zeyu Wang; Yanping Duan; Jun Bo Zhang; Xiaoying Lai; Jiajun Hu; Jixiang Li; Maisideke Maimaitijiang; Yalei Zhang; Shuguang Liu; Rongbing Fu (Chemosphere, 2023)

Free radical formation via BDE-209 thermolysis in the precalciner of a cement kiln: Simulation and DFT study - Jinzhong Yang; Bo-Tao Zhang; Lu Tian; Qingqi Die; Fei Wang; Haihui Fu; Yufei Yang; Qifei Huang (Science of The Total Environment, 2023)

Monazite and titanite U Pb ages of granitoids from the North Qinling Terrane: Implications for the subduction of the Shangdan Ocean and accretionary processes - Zheng-wei Qin; Wolfgang Siebel; Jian-ming Fu; Hao Wang; Bo Bao; Yu-shuai Yu; Liang Shan; You-yue Lu; Yuan-Bao Wu (Lithos, 2023)

Enhanced degradation of Bisphenol AF by Fe/Zn modified biochar/ferrate(VI): Performance and enhancement mechanism - Yu Zhang; Qun Wang; Xiongtao Wang; Renxuan Xiong; Die Fu; Chuanshu He; Bo Lai; Jun Ma (Journal of Environmental Chemical Engineering, 2023)

Ultrasonic–microwave synergistic supramolecular solvent liquid–liquid microextraction of trace biogenic amines in fish and beer based on solidification of floating organic droplet - Furong Jin; Xinyue Yin; Yang Wan; Jiukai Zhang; Jindi Wang; Xiangbo Fu; Tianxin Fu; Buwei Liu; Yongshi Chen; Bo Tian; Zhibiao Feng (Food Chemistry, 2023)

Oxidation and side-chain modifications decrease gastrointestinal digestibility and transport of proteins from salted bighead carp fillets after frozen storage - Song Gao; Zixin Fu; Longteng Zhang; Bo Li; Yuqing Tan; Hui Hong; Yongkang Luo (Food Chemistry, 2023)

Effects of external environment on promoter methylation of PIK3R5 and related pathway regulation in steroid-induced femoral head necrosis - Wentao Qin; Mingyang Jiang; Shenyi Lu; Yang Hu; Fu Gan; Weijun Fang; Dongxu Chen; Zhandong Bo (Environmental Research, 2023)

Multifunctional 0D@2D (Mox-Mn)Sy-NPs@MXene hybrid electrode with high rate-capability and ultra-long cycling life for Li-ion battery and all Molybdenum-MXene-based 1.9 (V) asymmetric supercapacitor - Ghuzanfar Saeed; Asrar Alam; Shufeng Bo; Jun Su; Min Chang Kim; Liguo Zhang; Youngjoong Choi; Shrikant Sadavar; Hao Fu; Ho Seok Park; Kwang Ho Kim (Chemical Engineering Journal, 2023)

Graphene nanonetwork embedded with polyaniline nanoparticles as anode of Li-ion battery - Haiyang Fu; Bo Gao; Yuan Qiao; Wenhui Zhu; Zhuang Liu; Gaoyu Wei; Zhongbao Feng; Ali Reza Kamali (Chemical Engineering Journal, 2023)

A Reactive Transport Model Considering the Bioavailability of PAHs Based on Lagrangian Reactive Particle-Tracking Method - Tao Chen; Wenbiao Huang; Yafu Zhang; Yanli Dong; Bo Fu; Haiyan Li (Water, Air, & Soil Pollution, 2023)

Study on Macroscopic Mechanical Behavior and Meso-failure Evolution of Gabbro of Different Particle Sizes - Haifeng Ding; Xiaodong Fu; Qian Sheng; Jian Chen; Chengzeng Yan; Kaiwei Tian; Bo Hu (Rock Mechanics and Rock Engineering, 2023)

Modeling of errors resulting from vehicle motions for CHZII mobile gravimeter and its performance verification during marine surveys - Hai-bo Tu; Jian-gang He; Ming Hu; Xing-hui Liang; Lei-jun Liu; Qin-qin Dong; Sun-jun Liu; Hui Zhang; Yong-tao Fu; Jun-jian Lang; Heng Sun; Lin-tao Liu (Applied Geophysics, 2023)

Observations on the embryonic development of the mud crab, Scylla paramamosain - Li-Kun Xu; Ke-Yi Ma; Feng-Ying Zhang; Wei Wang; Ling-Bo Ma; Zhong-Wen Jin; Ming Zhao; Wei Chen; Yin Fu; Chun-Yan Ma; Zhi-Qiang Liu (Frontiers in Marine Science, 2023)
To investigate the embryonic development of the mud crab Scylla paramamosain , we analyzed three critical parameters: egg color of, embryo morphology (through conventional and laser scanning confocal microscopy), and the distribution of cell divisions. During embryonic development, the egg color exhibited a progressive transition, shifting from orange to reddish-orange, then to brown, before ultimately darkening to black. Each embryo displayed a spherical shape, measuring approximately 280 μm in diameter, characterized by a smooth surface devoid of any depressions. The embryonic cell division was in the form of mixed oogenesis, comprised of complete division in the early stage, spiral oogenesis in the middle stage and surface division in the late stage. It is noteworthy that the blastopore appeared at the position where the transparent area and cell aggregation just appeared under the microscope, and the blastomere was a characteristic of the embryo entering the gastrulation stage. After entering the gastrulation stage, the cells aggregated towards the blastopore and formed two symmetrical cell clusters, which formed a V-shape with the void of the classic blastopore. When the transparent region occupied approximately 1/5 of the embryo ’ s volume, the embryo entered the nauplius stage, and the thoracic and abdominal armor, as well as the optic lobe and abdominal limb primordia, could be clearly distinguished. The appearance of the compound eye pigment band indicated the stage of compound eye pigment formation. At this time, the transparent area accounted for 1/4 of the embryo and a large number of ganglia appeared. The change of the compound eye pigment band from red to black was also one of the reasons for the blackening of the egg color of the crabs. The data obtained through this study have potential applications in the determination of embryonic development status and obtaining of high-quality seeds for S. paramamosain culture.

Numerical simulation of flow instability induced by a fixed cylinder placed near a plane wall in oscillating flow - Zi-Fang Li; Jiang-Hua Li; Jian-Zhao Wu; Kai-Leong Chong; Bo-Fu Wang; Quan Zhou; Yu-Lu Liu (Ocean Engineering, 2023)

Rate-dependent strength and crack damage thresholds of rocks at intermediate strain rate - Haibo Li; Liwang Liu; Shuaiyang Fu; Bo Liu; Xiaofeng Li (International Journal of Rock Mechanics and Mining Sciences, 2023)

Carbonate lithium isotope systematics indicate cooling triggered mass extinction during the Frasnian-Famennian transition - Yang-Yang Wang; Kun Liang; Yilin Xiao; Bo Chen; Erhao Shan; Tingyu Yang; Meng Zhang; He Sun; Hai-Ou Gu; Fengtai Tong; Lulu Fu; Dong-Yong Li; et al. (Global and Planetary Change, 2023)

The latest advances on soy sauce research in the past decade: Emphasis on the advances in China - Xianli Gao; Xue Zhao; Feng Hu; Jiangyan Fu; Zhankai Zhang; Zhan Liu; Bo Wang; Ronghai He; Haile Ma; Chi-Tang Ho (Food Research International, 2023)

Identification of pancreatic lipase inhibitors from Eucommia ulmoides tea by affinity-ultrafiltration combined UPLC-Orbitrap MS and in vitro validation - Han Huang; Ming-Hao Han; Qi Gu; Jian-Dong Wang; Heng Zhao; Bo-Wen Zhai; Si-Ming Nie; Zhi-Guo Liu; Yu-Jie Fu (Food Chemistry, 2023)

A novel oleogel based on porous microgel from egg white - Buwei Liu; Lina Sun; Furong Jin; Yang Wan; Xiue Han; Tianxin Fu; Yongjia Guan; Zhixin Xie; Long Cheng; Bo Tian; Zhibiao Feng (Food Hydrocolloids, 2023)

Structural and gelling properties of whey proteins influenced by various acids: Experimental and computational approaches - Linlin Zhang; Zhuo Zhang; Stephen R. Euston; Bo Li; Erhu Li; Caixia Fu; Guodong Chen (Food Hydrocolloids, 2023)

Learning-Based personal models for joint optimization of thermal comfort and energy consumption in flexible workplaces - Min Deng; Bo Fu; Carol C. Menassa; Vineet R. Kamat (Energy and Buildings, 2023)

Multistage plate subduction controls intraplate volcanism and cratonic lithospheric thinning in Northeast Asia - Zhi Wang; Lijun Liu; Yi Fu; Liang Zhao; Jian Lin; Zhenmin Jin; Bo Zheng (Earth-Science Reviews, 2023)

Amino acids as in-situ electron donors drive medium chain fatty acids production from sludge acidogenic fermentation liquid by electro-fermentation enhancement - Ping Wu; Peng Ding; Qi-hao Cao; Chao Zhang; Bo Fu; Hong-bo Liu; Chong-jun Chen; He Liu (Chemical Engineering Journal, 2023)

Stabilization of capsanthin in physically-connected hydrogels: Rheology property, self-recovering performance and syringe/screw-3D printing - Hongxia Wang; Chaoyang Wu; Juncheng Zhu; Yang Cheng; Yuxin Yang; Shihao Qiao; Bo Jiao; Liang Ma; Yu Fu; Hai Chen; Hongjie Dai; Yuhao Zhang (Carbohydrate Polymers, 2023)

Biochar facilitates methanogens evolution by enhancing extracellular electron transfer to boost anaerobic digestion of swine manure under ammonia stress - Gaojun Wang; Peng Fu; Bo Zhang; Ji Zhang; Qiuyi Huang; Gaofei Yao; Qian Li; Mawuli Dzakpasu; Jianfeng Zhang; Yu-You Li; Rong Chen (Bioresource Technology, 2023)

Leopard predation on wild Sichuan snub-nosed monkeys - Bin Yang; James R. Anderson; Ni-Na Gou; Jun Luo; Bo Hong; Wei-Wei Fu; Yong-Feng Chen; Wei-Feng Wang; Bao-Jia Cao; Shi-Yu Chen; Kai-Feng Wang; Bao-Guo Li (Primates, 2023)

Risk assessment of geological disasters in Beichuan County after the Wenchuan earthquake based on ArcGIS - Fu-gang Xu; Yi-heng Ou; Feng Wang; Bo-wen Wei; Ruokun-Nie (Bulletin of Engineering Geology and the Environment, 2023)

A novel “Turn-on” fluorometric assays triggered reaction for β-glucosidase activity based on quercetin derived silicon nanoparticles and its potential use for cell imaging - Yves Iradukunda; Jing-Yan Kang; Xiao-bo Zhao; Stanislas Nsanzamahoro; Xiao-Kang Fu; Jia Liu; Yu-Zhu Ding; Wei Ha; Yan-Ping Shi (Analytica Chimica Acta, 2023)

Nanopore Structure and Multifractal Characteristics of Continental Shale Oil Reservoir: A Case Study from Ziliujing Shales in the Sichuan Basin - Youzhi Wang; Wei Li; Xiandong Wang; Zhiguo Wang; Weiqi Ma; Yanping Zhu; Mengdi Sun; Bo Liu; Lijuan Cheng; Xiaofei Fu (Journal of Marine Science and Engineering, 2023)
Thermal maturity of the shales from the Ziliujing Formation of the Jurassic age in the Sichuan Basin is in the hydrocarbon generation window, which makes it a candidate for shale oil and gas development. The meso- and macropore characteristics and heterogeneity of shales are important factors affecting the occurrence and development of oil and gas. However, the meso- and macropores of the Ziliujing shales have not been systematically studied. Thus, the mineral compositions and total organic carbon (TOC) of samples from this formation, as well as its pore structure, are analyzed by low-temperature N2 adsorption technique. Moreover, the heterogeneity of the pores was determined by multifractal analysis. The results show that the Ziliujing shales can be classified into three types according to the distributions of mineral compositions of carbonate and mixed and argillaceous shales. Results revealed that the smallest meso- and macropore volume (PV), the smallest specific surface area (SSA), and the largest average pore diameter (APD) occur in the carbonate shales. However, the largest PV and SSA and the smallest APD are observed in the argillaceous shales. The porosity of carbonate shales is mainly concentrated between 5 nm and 30 nm. Compared with carbonate shales, the porosity with pore sizes less than 30 nm of mixed and argillaceous shales shows a rapid increase. Furthermore, inorganic minerals are the main factors affecting the pore distributions, while TOC shows a weak effect. Herein, clay minerals significantly increase the mesopore volume and the pore number with a size of less than 30 nm. The Dq-q curves reveal that the meso- and macropore distributions of Ziliujing shales show multifractal behavior, but the multifractal characteristics of pores of various shales are distinctly different. The information dimension D1, the Hurst exponent H, and the width of the right side D0–D10 are key indicators to distinguish the local variations within the pore structure of different types of shales. The carbonate shales have the largest multifractal spectra width and the smallest D1 and H, while the opposite trend is found for the argillaceous shales. Clay minerals reduce the heterogeneity of the meso- and macropore distributions and increase the pore connectivity. Nevertheless, the carbonate minerals exhibit a reverse trend. Finally, it was found that TOC does not impact pore complexity as much. Collectively, this study supports our understanding of the occurrence of shale oil within various reservoir facies, thereby providing a guideline for future explorations in the Ziliujing Formation of the Jurassic age in the Sichuan Basin.

Graphene oxide nanosheets immobilised on honeycomb pore structure of pomelo peel for enhanced removal of methylene blue - Zhuang Liu; Bo Gao; Haoyuan Han; Haiyang Fu (Environmental Geochemistry and Health, 2023)

Resource utilization of rice straw to prepare biochar as peroxymonosulfate activator for naphthalene removal: Performances, mechanisms, environmental impact and applicability in groundwater - Jun Bo Zhang; Chaomeng Dai; Zeyu Wang; Xueji You; Yanping Duan; Xiaoying Lai; Rongbing Fu; Yalei Zhang; Maisideke Maimaitijiang; Kah Hon Leong; Yaojen Tu; Zhi Li (Water Research, 2023)

Interfacial mechanism and inactivation efficiency of bacteriophage MS2 by ozone in high turbidity and algal-laden water resource - Lu Wang; Yi-bo Hu; Xiaochao Bi; V. Vasanthakumar; Zhiyong Zhang; Ming-Lai Fu; Wenjie Sun; Baoling Yuan (Journal of Water Process Engineering, 2023)

Construction of facet orientation-supported Z-scheme heterojunction of BiVO4 (110)-Fe2O3 and its photocatalytic degradation of tetracycline - Qiang Fu; Yue Meng; Yiyang Yao; Hui Shen; Bo Xie; Zheming Ni; Shengjie Xia (Journal of Environmental Chemical Engineering, 2023)

Nitrogen self-doped chitosan carbon aerogel integrating with CoAl-LDH for ultra-efficient sulfamethoxazole degradation based on PS-AOPs: From batch to continuous process - Manjun Fu; Bo Chai; Xiaohu Zhang; Ya Sun; Guozhi Fan; Guangsen Song (Journal of Environmental Chemical Engineering, 2023)

Influences of humic acids released during sludge thermal hydrolysis on anaerobic digestion: New insights from enzymatic perspectives - Fang Huang; Hongbo Liu; Jiaxin Wen; Shan Huang; Zhiyong Zheng; Xuedong Zhang; Bo Fu; Yajie Li; Aijie Wang; He Liu (Chemical Engineering Journal, 2023)

Semiconductors modified gourd-shaped hollow PtNi and their directional electron and mass transfer effects - Fu-Fei Pu; Yu-Xuan Xiao; Xiong Yang; Fei Yu; Lei Xia; Jiang-Bo Chen; Lu Wu; Jing-Jing Xie; Wen-Ying Zhao; Yu Liu; Li-Ying Wang; Jie Ying; et al. (Chemical Engineering Journal, 2023)

Triplet chromophoric dissolved organic matter regulating the phototransformation and toxicity of imidacloprid in paddy water - Yu Zeng; Qinglong Fu; Dionysios D. Dionysiou; Mingyang Zhang; Mabo Li; Bo Ye; Ning Chen; Juan Gao; Yujun Wang; Dongmei Zhou; Guodong Fang (Chemical Engineering Journal, 2023)

Geochronology and petrogenesis of the early Silurian Zeluo mafic-ultramafic intrusion, eastern Tibet: implications for the tectonic setting and evolution of the eastern Proto-Tethys Ocean - Hang Zhou; Wenxiao Zhou; Ernest Chi Fru; Thomas C. Sheldrick; Haiquan Li; Bo Huang; Dong Fu; Yadong Xu (International Geology Review, 2023)

Effects of size and surface charge on the sedimentation of nanoplastics in freshwater - Honglu Zhu; Xiaolei Fan; Hua Zou; Rong-Bo Guo; Shan-Fei Fu (Chemosphere, 2023)

TIPS: A three-dimensional phenotypic measurement system for individual maize tassel based on TreeQSM - Bo Xu; Xiangyuan Wan; Hao Yang; Haikuan Feng; Yuanyuan Fu; Haiyan Cen; Binbin Wang; Zhoufeng Zhang; Siyuan Li; Chunjiang Zhao; Guijun Yang (Computers and Electronics in Agriculture, 2023)

A non-toxic recombinant Clostridium septicum α toxin induces protective immunity in mice and rabbits - Jige Du; Irene Meki; Qianlin Li; Ying Liu; Zhen Zhu; Chenfan Pan; Yingju Xia; Lizhi Fu; Liu Yang; Suhui Zhang; Chunsheng Yin; Yufeng Luo; et al. (Toxicon, 2023)

Simulation of Rayleigh convection during dichloromethane absorption by water using lattice Boltzmann method - Ruixue Xiao; Kefan Chao; Ju Liu; Li Wang; Muhua Chen; Xinbao Zhu; Bo Fu (Process Safety and Environmental Protection, 2023)

Exploring the trade-offs among hydropower benefits, environmental flow, and surface water temperature in a large reservoir under deep uncertainty - Longfan Wang; Bo Xu; Chi Zhang; Xiaoxian Chen; Yi Zheng; Jingjie Zhang; Guangtao Fu (Journal of Hydrology, 2023)

Phase-mediated mercury removal from water using multilayered molybdenum disulfide: The key role of redox mechanism - Jia Sun; Junjun Pei; Zhiyuan Qiu; Jing Guo; Bo Li; Kaixing Fu; Kai Yin; Shenglian Luo (Journal of Cleaner Production, 2023)

Detrital zircon U Pb dating and geochemistry of the Paleogene-Neogene sediments in the Qaidam Basin (China): Implications for provenance and tectonics - Yetong Wang; Guoqiang Sun; Shangshang Bo; Shuang Fu; David Cruset; Juan Diego Martín-Martín; Hui Guo; Irene Cantarero; Vinyet Baqués; Guojun Chen; Shuncun Zhang; Anna Travé (Global and Planetary Change, 2023)

Experimental investigation of circulating fluidized bed combustion of dry powders of coal slime - Bin Liang; Haolong Bai; Bo Tan; Liangliang Fu; Dingrong Bai (Fuel, 2023)

The complexes of soybean protein isolate and procyanidin B2 have synergistic hypolipidemic activity at the cellular level by activating the AMPKα pathway - Lei Ji; Hongling Fu; Yi Wang; Jiaxin Li; Xiaoqing Yang; Hao Gong; Xiangze Meng; Wendan Jing; Weichang Dai; Youbao Li; Bo Lyu; Hansong Yu (Food Chemistry, 2023)

Structure, physicochemical and functional properties of plant-based SPI films from different soybean varieties deficient in β-conglycinin subunits - Jiaxin Li; Khalid Amin; Hongling Fu; Lei Ji; Yi Wang; Hao Gong; Hansong Yu; Bo Lyu; Xiaoqing Yang (Food Packaging and Shelf Life, 2023)

Climatic effect from oyster reef restoration in Spartina alterniflora invaded intertidal mudflat: From the perspective of CH4 and N2O production - Wenjing Fu; Xiaoke Pang; Yifan Zhao; Chenglong Han; Yufei Liu; Xue Yu; Jianfeng Feng; Jing Fang; Bo Zhang; Xueqiang Lu (Estuarine, Coastal and Shelf Science, 2023)

Experiment study on reactive powder concrete beams using spirals reinforcement under torsion - Xia Cao; Yong-peng Quan; Yi-cheng Ren; Feng Fu; Qi-zhi Jin; Da-bo He; Yan Zheng (Engineering Structures, 2023)

Assessment of the FIO-CPS v2.0 in predicting 2-meter air temperature over China - Qiuying Fu; Zhenya Song; Zhongkai Bo; Ying Bao; Chan Joo Jang; Yajuan Song (Dynamics of Atmospheres and Oceans, 2023)

Structural analysis of shield machine cutting monopile using p-y curve based finite element method - Ting Li; Bo Liu; Yanhui Han; Chunqing Fu; Yanding Sun (Computers and Geotechnics, 2023)

Hierarchically polar structures induced superb energy storage properties for relaxor Bi0.5Na0.5TiO3-based ceramics - Hao Wang; Shengyang Wu; Bo Fu; Jingji Zhang; Huiwei Du; Quan Zong; Jiangying Wang; Zhongbin Pan; Wangfeng Bai; Peng Zheng (Chemical Engineering Journal, 2023)

Declines in nutrient losses from China’s rice paddies jointly driven by fertilizer application and extreme rainfall - Jin Fu; Chengjie Wang; Wulahati Adalibieke; Yiwei Jian; Yan Bo; Xiaoqing Cui; Feng Zhou (Agriculture, Ecosystems & Environment, 2023)

Early-Middle Devonian adakitic magmatism generated by slab retreat in southern West Junggar, NW China: implications for tectonic correlation with central and East Kazakhstan - Rong Ren; Bo Liu; Bao-Fu Han; Shu-Wei Guan (International Geology Review, 2023)

Numerical investigation of suppressing thermal runaway propagation in a lithium-ion battery pack using thermal insulators - Junhui Gong; Bo Liu; Haochen Lian; Jingyi Liu; Hui Fu; Yuxuan Miao; Jialong Liu (Process Safety and Environmental Protection, 2023)

Design, synthesis and biological activity of novel triketone herbicides containing natural product fragments - Zi-Bin Jiang; Shuang Gao; Wei Hu; Bo-Ren Sheng; Juan Shi; Fei Ye; Ying Fu (Pesticide Biochemistry and Physiology, 2023)

Nanomechanical and chemical variations of inertinite and vitrinite within lacustrine shale during oil generation - Yifei Gao; Bo Liu; Xiaofei Fu; Shansi Tian; Boyang Wang; Liu Wang; Thomas Gentzis; Mehdi Ostadhassan (Marine and Petroleum Geology, 2023)

Cenozoic basement-involved rifting of the northern South China Sea margin - Yanhui Suo; Sanzhong Li; Guangrong Peng; Xiaodong Du; Jie Zhou; Pengcheng Wang; Guangzeng Wang; Ian Somerville; Yixiao Diao; Zhongqiang Liu; Xinjian Fu; Bo Liu; et al. (Gondwana Research, 2023)

A study on the analysis of dynamical transmission behavior and mining key monitoring stations in PM and O3 networks in the Beijing-Tianjin-Hebei region of China - Xiaofei Shi; Bo Li; Donglei Fu; Jiao Bai; Stephen Dauda Yabo; Kun Wang; Xiaoxiao Gao; Jie Ding; Hong Qi (Environmental Research, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

The role of GLUT2 in glucose metabolism in multiple organs and tissues - Bo Sun; Hui Chen; Jisu Xue; Peiwu Li; Xu Fu (Molecular Biology Reports, 2023)
The glucose transporter family has an important role in the initial stage of glucose metabolism; Glucose transporters 2 (GLUTs, encoded by the solute carrier family 2, SLC2A genes) is the major glucose transporter in β-cells of pancreatic islets and hepatocytes but is also expressed in the small intestine, kidneys, and central nervous system; GLUT2 has a relatively low affinity to glucose. Under physiological conditions, GLUT2 transports glucose into cells and allows the glucose concentration to reach balance on the bilateral sides of the cellular membrane; Variation of GLUT2 is associated with various endocrine and metabolic disorders; In this study, we discussed the role of GLUT2 in participating in glucose metabolism and regulation in multiple organs and tissues and its effects on maintaining glucose homeostasis.

Effect of hexavalent chromium exposure on the reproductive status and biomarker responses of female Geloina erosa - Hongling Mu; Gongsi Wang; Bo Huang; Xiangchao Fu; Sui Cheng; Jiao Wen (Ecotoxicology, 2023)

Nitrogen species and microbial community coevolution along groundwater flowpath in the southwest of Poyang Lake area, China - Xianglong Chen; Guangcai Wang; Yizhi Sheng; Fu Liao; Hairu Mao; Bo Li; Hongyu Zhang; Zhiyuan Qiao; Jiahui He; Yingxue Liu; Yilun Lin; Ying Yang (Chemosphere, 2023)

Effect of humic acid-modified attapulgite on polycyclic aromatic hydrocarbon adsorption and release from paddy soil into the overlying water in a rice-crab coculture paddy ecosystem and the underlying process - Nan Sun; Jin Liu; Bo-Wei Qi; Li-Li Lu; Hui-Ling Du; Shuang Li; Chang-Qing Li; Si-Wen Jiang; Zi-Jian Wang; An-Pei Yang; Guang-Lei Zhu; Tian-Yi Wang; et al. (Chemosphere, 2023)

Bifunctional reduced graphene oxide/polyelectrolyte/NiFe layered double hydroxide composites for efficient catalyzed dephosphorylation and 4-nitrophenol reduction - Zijun Xie; Bo Sun; Hongying Lin; Meng Fu; Yi Zhang; Zequn Ma; Xiangming Li (Journal of Water Process Engineering, 2023)

Occurrence, distribution, and risk assessment of quinolone antibiotics in municipal sewage sludges throughout China - Fan Meng; Shaojing Sun; Jialu Geng; Lixin Ma; Jinpan Jiang; Bo Li; Stephen Dauda Yabo; Lu Lu; Donglei Fu; Jimin Shen; Hong Qi (Journal of Hazardous Materials, 2023)

Uncovering quality changes of salted bighead carp fillets during frozen storage: The potential role of time-dependent protein denaturation and oxidation - Song Gao; Yueyue Liu; Zixin Fu; Huijuan Zhang; Longteng Zhang; Bo Li; Yuqing Tan; Hui Hong; Yongkang Luo (Food Chemistry, 2023)

Polymorphism analysis of major histocompatibility complex (MHC) DQB gene in the Asiatic black bear (Ursus thibetanus) - Yutian Jia; Qiang Fu; Bo Li; Yanchun Xu; Ahmad Tariq (Mammal Research, 2023)

Performance evaluation of the UV activated chlorite process on trimethoprim: Degradation efficiency, energy consumption and disinfection by-products formation - Wen-Kai Ye; Fu-Xiang Tian; Chen Chen; Jing Ye; Fu-wen Liu; Bo Wang; Xiao-Jun Hu; Bin Xu (Chemosphere, 2023)

Influence on the levels of PAHs and methylated PAHs in surface soil from pollution control in China: Evidence in 2019 data compared with 2005 and 2012 data - Fu-Jie Zhu; Zi-Feng Zhang; Li-Yan Liu; Hong Yao; Hong-Liang Jia; Zhi Zhang; Song Cui; Bo Meng; Gang Cao; Peng-Hao Su; Xiao-Xuan Mao; Bao-Long Li; et al. (Science of The Total Environment, 2023)

Complete biodegradation of the oldest organic herbicide 2,4-Dichlorophenoxyacetic acid by engineering Escherichia coli - Yu Wang; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Hong-Juan Han; Li-Juan Wang; Wen-Hui Zhang; Yong-Dong Deng; Cen Qian; Zhi-Hao Zuo; et al. (Journal of Hazardous Materials, 2023)

Gestational cadmium exposure disrupts fetal liver development via repressing estrogen biosynthesis in placental trophoblasts - Yi-Ting Fu; Jin Zhang; Wei-Bo Liu; Yu-Feng Zhang; Shuang Zhang; Lu-Lu Tan; Qing Lin; Kong-Wen Ou-Yang; Yong-Wei Xiong; Wei Chang; Hao Li; Jun-Ying Yu; et al. (Food and Chemical Toxicology, 2023)

A micromechanical investigation of sand–rubber mixtures using the discrete element method - Ru Fu; Bo Yang; Xinli Hu; Bo Zhou; Matthew Richard Coop (Engineering Geology, 2023)

Microscopic Analysis of Natural Fracture Properties in Organic-Rich Continental Shale Oil Reservoirs: A Case Study from the Lower Jurassic in the Sichuan Basin, China - Xuefeng Bai; Saipeng Huang; Xiandong Wang; Zhiguo Wang; Youzhi Wang; Weiqi Ma; Yanping Zhu; Mengdi Sun; Bo Liu; Xiaofei Fu; Lijuan Cheng; Likai Cui; et al. (Journal of Marine Science and Engineering, 2023)
Natural fractures are of paramount importance in storing carbon in shale oil reservoirs, where ultra-low porosity and permeability necessitate their essentiality for enhanced oil recovery. Therefore, comprehensively clarifying the characteristics of natural fractures in shale oil reservoirs is imperative. This paper focuses on investigating the microscopic features of natural fractures in organic-rich continental shale oil reservoirs that are commonly found in the Lower Jurassic strata of the Sichuan Basin, employing them as a representative example. Multiple methods were utilized, including mechanical testing, Kaiser testing, multi-scale CT scanning (at 2 mm, 25 mm, and 100 mm scales), and a numerical simulation of fluid seepage in fracture models. The results revealed that the in situ stress of the target seam displays the characteristic of σH > σv > σh, with σv and σh being particularly similar. The relatively high lateral stress coefficient (ranging from 1.020 to 1.037) indicates that the horizontal stresses are higher than the average level. Although the 2 mm CT scan provides a more detailed view of fractures and connected pores, it primarily exhibited more pore information due to the high resolution, which may not fully unveil additional information about the fractures. Thus, the 25 mm shale core is a better option for studying natural fractures. The tortuosity of the different fractures indicated that the morphology of larger fractures is more likely to remain stable, while small-scale fractures tend to exhibit diverse shapes. The simulations demonstrated that the stress sensitivity of fracture permeability is approximately comparable across different fracture scales. Therefore, our research can enhance the understanding of the properties of natural fractures, facilitate predicting favorable areas for shale oil exploration, and aid in evaluating the carbon storage potential of shale oil reservoirs.

Global ocean reanalysis CORA2 and its inter comparison with a set of other reanalysis products - Hongli Fu; Bo Dan; Zhigang Gao; Xinrong Wu; Guofang Chao; Lianxin Zhang; Yinquan Zhang; Kexiu Liu; Xiaoshuang Zhang; Wei Li (Frontiers in Marine Science, 2023)
We present the China Ocean ReAnalysis version 2 (CORA2) in this paper. We compare CORA2 with its predecessor, CORA1, and with other ocean reanalysis products created between 2004 and 2019 [GLORYS12v1 (Global Ocean reanalysis and Simulation), HYCOM (HYbrid Coordinate Ocean Model), GREP (Global ocean Reanalysis Ensemble Product), SODA3 (Simple Ocean Data Assimilation, version 3), and ECCO4 (Estimating the Circulation and Climate of the Ocean, version 4)], to demonstrate its improvements and reliability. In addition to providing tide and sea ice signals, the accuracy and eddy kinetic energy (EKE) of CORA2 are also improved owing to an enhanced resolution of 9 km and updated data assimilation scheme compared with CORA1. Error analysis shows that the root-mean-square error (RMSE) of CORA2 sea-surface temperature (SST) remains around 0.3°C, which is comparable to that of GREP and smaller than those of the other products studied. The subsurface temperature (salinity) RMSE of CORA2, at 0.87°C (0.15 psu), is comparable to that of SODA3, smaller than that of ECCO4, and larger than those of GLORYS12v1, HYCOM, and GREP. CORA2 and GLORYS12v1 can better represent sub-monthly-scale variations in subsurface temperature and salinity than the other products. Although the correlation coefficient of sea-level anomaly (SLA) in CORA2 does not exceed 0.8 in the whole region, as those of GREP and GLORYS12v1 do, it is more effective than ECCO4 and SODA3 in the Indian Ocean and Pacific Ocean. CORA2 can reproduce the variations in steric sea level and ocean heat content (OHC) on the multiple timescales as the other products. The linear trend of the steric sea level of CORA2 is closer to that of GREP than that of the other products, and the long-term warming trends of global OHC in the high-resolution CORA2 and GLORYS12v1 are greater than those in the low-resolution EN4 and GREP. Although CORA2 shows overall poorer performance in the Atlantic Ocean, it still achieves good results from 2009 onward. We plan to further improve CORA2 by assimilating the best available observation data using the incremental analysis update (IAU) procedure and improving the SLA assimilation method.

Investigation of CH4 and porous media addition on thermal and working performance in premixed H2/air combustion for micro thermophotovoltaic - Bo Xie; Qingguo Peng; Zhiwei Shi; Jia Wei; Zhuang Kang; Depeng Wei; Xinghua Tian; Guang Fu (Fuel, 2023)

The development process of plant-based meat alternatives: Raw material formulations and processing strategies - Yi Wang; Bo Lyu; Hongling Fu; Jiaxin Li; Lei Ji; Hao Gong; Ruining Zhang; Jingsheng Liu; Hansong Yu (Food Research International, 2023)

The effects of pulsed electric fields treatment on the structure and physicochemical properties of dialdehyde starch - Ying Li; Jin-Hua Wang; Yu Han; Fu-Hao Yue; Xin-An Zeng; Bo-Ru Chen; Man-Qin Zeng; Meng-Wai Woo; Zhong Han (Food Chemistry, 2023)

Di-(2-ethylhexyl) phthalate impairs angiogenesis and hematopoiesis via suppressing VEGF signaling in zebrafish - Yang-Xi Hu; Bo-Wen Hu; Ya-Sha Chen; Hong-Min You; Mei-Rong Bai; Lu-Jun Zhang; Zhi-Fu Guo; Chun Liang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Metatranscriptomic insights into the microbial electrosynthesis of acetate by Fe2+/Ni2+ addition - Jie Zhang; He Liu; Yan Zhang; Bo Fu; Chao Zhang; Min-Hua Cui; Ping Wu; Zi-Wei Guan (World Journal of Microbiology and Biotechnology, 2023)

Improving short-term streamflow forecasting by flow mode clustering - Shuqi Liu; Xinzhi Zhou; Bo Li; Xin He; Yuexin Zhang; Yi Fu (Stochastic Environmental Research and Risk Assessment, 2023)

Chemiluminescence Immunoassay Method of Urinary Liver Fatty-acid-binding Protein as a Promising Candidate for Kidney Disease - Lisong Niu; Lanya Li; Jinshan Li; Zhitian Chen; Jiayuan Lin; Bo Zhang; Xiaoling Fu (Journal of Fluorescence, 2023)

Outcomes between endoscopic-assisted minimally invasive surgery and conventional craniotomy in spontaneous intracerebral hemorrhage - Yi-Ying Hsieh; Bo-An Chen; Kuan-Hao Fu; Yi-Hsien Kuo; Ying-Yun Chen; Jiun-Lin Yan; Pin-Yuan Chen (Neurophysiology, 2023)

Apoptosis-related long non-coding RNA LINC5438 of Bombyx mori promotes the proliferation of BmNPV - Peng Chen; Min Cai; Yu-Jie Feng; Cong Li; Zhan-Qi Dong; Wen-Fu Xiao; Liang Tang; Yan Zhu; Ting Tian; Bo-Yuan Deng; Min-Hui Pan; Cheng Lu (Pesticide Biochemistry and Physiology, 2023)

Efficient removal of doxycycline using Schwertmannite as a heterogeneous Fenton-like catalyst over a wide pH range - Yu Tian; Fenwu Liu; Bo Sun; Zhenye Tong; Peng Fu; Jingzhi Zhang; Wenlong Bi; Shaozu Xu; Guangpeng Pei (Journal of Environmental Chemical Engineering, 2023)

Constitutive model for Ya’an mudstone based on mesoscopic breakage mechanism - Yun-yong He; Cong Chen; Fu-ming Wang; Cheng-chao Guo; Bo Xiang; Di Yu; En-long Liu; Chun Ding (Journal of Mountain Science, 2023)

Zircon SHRIMP U–Pb geochronology, geochemistry, and geological significance of dacite in the Zhesang gold district, southeast Yunnan Province, China - Bo Wang; Jiasheng Wang; Jinlong Li; Hao Fu; Yuehua Ma; Bin Ye (Acta Geochimica, 2023)

Synergistic interactions of fine particles and radiative effects in modulating urban heat islands during winter haze event in a cold megacity of Northeast China - Stephen Dauda Yabo; Donglei Fu; Bo Li; Lixin Ma; Xiaofei Shi; Lu Lu; Xie Shengjin; Fan Meng; Jinpan Jiang; Wei Zhang; Hong Qi (Environmental Science and Pollution Research, 2023)

Deciphering the role and mechanism of nano zero-valent iron on medium chain fatty acids production from CO2 via chain elongation in microbial electrosynthesis - Ping Wu; Jie Zhang; Jing Li; Yan Zhang; Bo Fu; Ming-Yi Xu; Yi-Feng Zhang; He Liu (Science of The Total Environment, 2023)

Spatial variability of source contributions to nitrate in regional groundwater based on the positive matrix factorization and Bayesian model - Hairu Mao; Guangcai Wang; Fu Liao; Zheming Shi; Hongyu Zhang; Xianglong Chen; Zhiyuan Qiao; Bo Li; Yunfei Bai (Journal of Hazardous Materials, 2023)

Egg-yolk-derived carbon dots@albumin bio-nanocomposite as multifunctional coating and its application in quality maintenance of fresh litchi fruit during storage - Xianjie Su; Hetong Lin; Bofei Fu; Shanshan Mei; Mengshi Lin; Hongbin Chen; Zongping Zheng; Hangyu Bo; Da-Peng Yang; Yifen Lin (Food Chemistry, 2023)

Why did air quality experience little improvement during the COVID-19 lockdown in megacities, northeast China? - Donglei Fu; Xiaofei Shi; Jinxiang Zuo; Stephen Dauda Yabo; Jixiang Li; Bo Li; Haizhi Li; Lu Lu; Bo Tang; Hong Qi; Jianmin Ma (Environmental Research, 2023)

FAS-mediated circRNA-miRNA-mRNA Crosstalk Network Regulates Immune Cell Infiltration in Cerebral Infarction - Ke Ying; Juan Chen; Zhenhui Fu; Bo Ren (Journal of Molecular Neuroscience, 2023)

Acute Aluminum Sulfate Triggers Inflammation and Oxidative Stress, Inducing Tissue Damage in the Kidney of the Chick - Bo Chen; Lina Chen; Zhiqing Yang; Qiang Fu; Xinran Li; Changyu Cao (Biological Trace Element Research, 2023)

Selenium Deficiency Caused Fibrosis as an Oxidative Stress-induced Inflammatory Injury in the Lungs of Mice - Yu-xin Fu; Yi-bo Wang; Qing-wei Bu; Meng-yao Guo (Biological Trace Element Research, 2023)

How anaerobic sludge microbiome respond to different concentrations of nitrite, nitrate, and ammonium ions: a comparative analysis - Runhua Su; Lina Zhou; Lili Ding; Bo Fu; Huimin Fu; Yanan Shuang; Lin Ye; Haidong Hu; Haijun Ma; Hongqiang Ren (Environmental Science and Pollution Research, 2023)

CiRS-187 regulates BMPR2 expression by targeting miR-187 in bovine cumulus cells treated with BMP15 and GDF9 - Yao Fu; Jia-Bao Zhang; Dong-Xu Han; Hao-Qi Wang; Jian-Bo Liu; Yue Xiao; Hao Jiang; Yan Gao; Bao Yuan (Theriogenology, 2023)

Detection of polycyclic aromatic hydrocarbons using a high performance-single particle aerosol mass spectrometer - Yao Zhang; Chenglei Pei; Jinwen Zhang; Chunlei Cheng; Xiufeng Lian; Mubai Chen; Bo Huang; Zhong Fu; Zhen Zhou; Mei Li (Journal of Environmental Sciences, 2023)

Analysis of lunar wrinkle ridges regarding the maximum displacement–length scaling relationship and relevant geological factors - Chenfan Li; Bo Li; Xiaohui Fu; Le Qiao; Zongcheng Ling; Jianguo Yan; Shaojie Qu; Shengbo Chen (Icarus, 2023)

Bioaccumulation and emission of organophosphate esters in plants affecting the atmosphere's phosphorus cycle - Shengxing Long; Paul B. Hamilton; Bo Fu; Jing Xu; Luchao Han; Xinhao Suo; Yuqin Lai; Guofeng Shen; Fuliu Xu; Bengang Li (Environmental Pollution, 2023)

The tempo of back-arc basin evolution: Insights from the early Paleozoic Proto-Tethyan North Qilian orogenic belt, northeastern Tibet - Dong Fu; Bo Huang; Simon A. Wilde; Tim E. Johnson; Ali Polat; Brian F. Windley; Zhaochu Hu; Zhipeng Zhou; Timothy M. Kusky (Earth and Planetary Science Letters, 2023)

Thiophene-based conjugated ultra-micropore rigid polymers for selective xenon capture - Zijun Yan; Yu Luo; Bo Chen; Fenglei Wang; Lang Chen; Zining Wang; Pengwei Zhao; Jinyang Kang; Zhihai Fu; Yongdong Jin; Yuanhua Wang; Chuanqin Xia (Chemical Engineering Journal, 2023)

Geraniin targeting CaMKK2 inhibits lipid accumulation in 3T3-L1 adipocytes by suppressing lipogenesis - Ji Li; Xuedong Wang; Xiangyu Meng; Xin Zhou; Han Huang; Yi Feng; Yujie Fu; Xinxin Liu; Bo Yu (Chemico-Biological Interactions, 2023)

Numerical and experimental investigation on hydraulic fracturing for offshore wind turbine rock-socketed pile foundation construction - Bo-nan Zhang; Dun-fu Zhang; Bo Zhang; Bo Han (Marine Georesources & Geotechnology, 2023)

Genome sequence and comparative analysis of fungal antagonistic strain Bacillus velezensis LJBV19 - Bo Wang; Bohan Yang; Hang Peng; Jiang Lu; Peining Fu (Folia Microbiologica, 2023)

Multi-source Data-driven Identification of Urban Functional Areas: A Case of Shenyang, China - Bing Xue; Xiao Xiao; Jingzhong Li; Bingyu Zhao; Bo Fu (Chinese Geographical Science, 2023)

Phosphorus availability mediates plant–plant interaction and field productivity in maize-grass pea intercropping system: Field experiment and its global validation - Shuang-Guo Zhu; Hong-Yan Tao; Wen-Bo Li; Rui Zhou; Yan-Wen Gui; Li Zhu; Xiao-Lin Zhang; Wei Wang; Bao-Zhong Wang; Fu-Jian Mei; Hao Zhu; You-Cai Xiong (Agricultural Systems, 2023)

Pathology, Enzyme Activity and Immune Responses after Cryptocaryon irritans Infection of Golden Pompano Trachinotus ovatus (Linnaeus 1758) - Hua-Yang Guo; Wen-Fu Li; Ke-Cheng Zhu; Bao-Suo Liu; Nan Zhang; Bo Liu; Jing-Wen Yang; Dian-Chang Zhang (Journal of Marine Science and Engineering, 2023)
Golden pompano (Trachinotus ovatus) has become an economically important fish in China in the past decade. However, Cryptocaryon irritans, a parasitic ciliate, causes considerable economic losses in the mariculture of T. ovatus. To characterize the pathogenesis of C. irritans in T. ovatus, the pathological properties, immune-related enzyme activity and expression of the NEMO gene was analysed. The results from the histological sections showed that there was considerable metamorphosis and hyperplasia in the parasitized sites (skin) with leukocyte aggregation and mucous cell increases after C. irritans infection. Moreover, the activities of four enzymes, that is, alkaline phosphatase (AKP), acid phosphatase (ACP), superoxide dismutase (SOD) and lysozyme (LZM), were significantly increased in different tissues after C. irritans infection. Furthermore, the ORF of T. ovatus NF-kappa-B essential modulator (ToNEMO) measures 1650 bp, encoding 548 amino acids. The ToNEMO transcripts were universally expressed in all examined tissues, with higher levels being observed in the immune-relevant and central nervous tissues. The mRNA levels of ToNEMO after C. irritans infection were significantly increased in the gill, skin, liver, spleen and head kidney. These results suggested that ToNEMO might be involved in immune responses and helped to elucidate the physiological response after the C. irritans infection of fish.

Dasatinib causes keratinocyte apoptosis via inhibiting high mobility group Box 1-mediated mitophagy - Zizheng Gao; Yuhuai Hu; Huangxi Fu; Feng Jiang; Hao Yan; Xiaochun Yang; Bo Yang; Qiaojun He; Peihua Luo; Zhifei Xu (Toxicology Letters, 2023)

Assessment of contaminants associated with gold-standard ancient DNA protocols - Bo Miao; Yalin Liu; Ruowei Yang; Xiaotian Feng; Feng Liu; Peng Cao; Qingyan Dai; Wanjing Ping; Yichen Liu; Qiaomei Fu (Science Bulletin, 2023)

Integrated multi-omic analyses on yellow Flammulina filiformis cultivar reveal postharvest oxidative damage responses - Yu Fu; Hao Tan; Bo Wang; Weihong Peng; Qun Sun; Yang Yu (Postharvest Biology and Technology, 2023)

One-stage anaerobic fermentation of excess sludge for caproate production by supplementing chain elongation enrichments with ethanol as electron donor - Bo Fu; Yujie Lu; Hongbo Liu; Xuedong Zhang; Hale Ozgun; Mustafa Evren Ersahin; He Liu (Journal of Environmental Management, 2023)

The source distribution and seasonal discrepancies of antibiotic resistance genes among multiple environment media in a cold megacity - Fan Meng; Shaojing Sun; Jialu Geng; Lixin Ma; Jinpan Jiang; Bo Li; Stephen Dauda Yabo; Lu Lu; Donglei Fu; Jimin Shen; Hong Qi (Journal of Cleaner Production, 2023)

Mechanism, performance and modification methods for NH3-SCR catalysts: A review - Zhiwei Shi; Qingguo Peng; Jiaqiang E; Bo Xie; Jia Wei; Ruixue Yin; Guang Fu (Fuel, 2023)

The effect of radio frequency heating on the inactivation and structure of horseradish peroxidase - Yishun Yao; Bo Zhang; Huiyun Pang; Yequn Wang; Hongfei Fu; Xiangwei Chen; Yunyang Wang (Food Chemistry, 2023)

The heated-induced gelation of soy protein isolate at subunit level: Exploring the impacts of α and α′ subunits on SPI gelation based on natural hybrid breeding varieties - Hongling Fu; Jiaxin Li; Xiaoqing Yang; Mohammed Sharif Swallah; Hao Gong; Lei Ji; Xiangze Meng; Bo Lyu; Hansong Yu (Food Hydrocolloids, 2023)

Effects of haloxyfop-p-methyl on the developmental toxicity, neurotoxicity, and immunotoxicity in zebrafish - Yi Liu; Jing Guo; Wenjin Liu; Fengjie Yang; Yunyun Deng; Yunlong Meng; Bo Cheng; Jianping Fu; June Zhang; Xinjun Liao; Lili Wei; Huiqiang Lu (Fish & Shellfish Immunology, 2023)

A mixed selective edge-based smoothed PFEM with second-order cone programming for geotechnical large deformation analysis - Xi-Wen Zhou; Feng-Tao Liu; Yin-Fu Jin; Zhen-Yu Yin; Cheng-Bo Zhang (Computers and Geotechnics, 2023)

Microwave-boosted elemental mercury removal using natural low-grade pyrolusite - Qian Yu; Xiaojie Yang; Yuhao Dong; Zhen Qian; Bo Yuan; Dong Fu (Chemical Engineering Journal, 2023)

Near-infrared I/II emission and absorption carbon dots via constructing localized excited/charge transfer state for multiphoton imaging and photothermal therapy - Wen-Bo Zhao; Dan-Dan Chen; Kai-Kai Liu; Yong Wang; Rui Zhou; Shi-Yu Song; Fu-Kui Li; Lai-Zhi Sui; Qing Lou; Lin Hou; Chong-Xin Shan (Chemical Engineering Journal, 2023)

Construction of modified MXene with “organic–inorganic” structure to enhance the interfacial and mechanical properties of UHMWPE fiber-reinforced epoxy composite - Kui Wang; Lu Shen; Qixuan Zhu; Rouyu Bo; Rong Lu; Xiaoshu Lu; Zixuan Fu (Chemical Engineering Journal, 2023)

Influence of thermal hydrolysis on sludge anaerobic digestion: Release of humic acid promotes electron transport of methanogen - Cheng Zhao; Hongbo Liu; He Liu; Xinmin Zhan; Xuedong Zhang; Bo Fu; Mingze Shi; Shuailing Lu; Fang Huang; Minhua Cui; Yajie Li (Chemical Engineering Journal, 2023)

The self-powered electrochemical biosensing platform with multi-amplification strategy for ultrasensitive detection of microRNA-155 - Yong-ping Gao; Ke-jing Huang; Fu-ting Wang; Yang-yang Hou; Lu-di Zhao; Bo-ya Wang; Jing Xu; Honglei Shuai; Guoqiang Li (Analytica Chimica Acta, 2023)

Separation of Panax notoginseng saponins on modified rosin ester-bonded silica stationary phase and its mechanism - Wen-Bo Xie; Hao Li; Lei Zeng; Li-Juan Jiang; Wen Li; Lu Xia; Fu-Hou Lei (Analytica Chimica Acta, 2023)

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

Novel circularRNA circ-0047078 promotes pancreatic ductal adenocarcinoma progression through mircoRNA miR-11181— Chemokine (C-X-C motif) Ligand 12/Melanoma Cell Adhesion Molecule/Regulator of G-protein signaling 16 pathway - Yuzhou Wang; Hangwei Fu; Yan Jiang; Bo Zhou; Ping Chen (Molecular Biology Reports, 2022)

Impacts of Mercury Exposure Levels and Sources on the Demethylation of Methylmercury Through Human Gut Microbiota - Xian-Feng Yang; Shao-Chen Yang; Fu-Li Wen; Lin Feng; Bo Meng; Hai-Yan Hu; Bao-Lin Wang; Jun Li; Alexandre J. Poulain; Ping Li (Bulletin of Environmental Contamination and Toxicology, 2022)

Shaking table test and numerical analysis of single-layer reticulated domes with or without three-dimensional isolation bearing - Gui-Bo Nie; Dong-fang Li; Xu-dong Zhi; Fu-yang Wang; Chen-xiao Zhang (Bulletin of Earthquake Engineering, 2022)

Climate Warming Mitigation from Nationally Determined Contributions - Bo Fu; Jingyi Li; Thomas Gasser; Philippe Ciais; Shilong Piao; Shu Tao; Guofeng Shen; Yuqin Lai; Luchao Han; Bengang Li (Advances in Atmospheric Sciences, 2022)

Increased water vapor supply in winter and spring leading to the arid Central Asian wetting in last 6000 years - Xu Zhang; Bo Liu; Shengqian Chen; Zhenhao Fu; Tingting Xie; Fahu Chen (Science China Earth Sciences, 2022)

Oct4 facilitates chondrogenic differentiation of mesenchymal stem cells by mediating CIP2A expression - Lexiang Li; Qiwei Fu; Jiahua Shao; Bo Wang; Zheru Ding; Shuai Yuan; Jinhui Peng; Wei Xin; Jun Zhu; Yi Chen (Cell and Tissue Research, 2022)

Cadinane-type sesquiterpenes with potential anti-inflammatory and anti-HIV activities from the stems and leaves of Mappianthus iodoides - Yan-Ping Liu; Xiao-Mei Yu; Ze-Hua Qiao; Bo Jiang; Lan Xie; Hao-Xuan Tang; Xiao Liang; Yan-Hui Fu (Natural Product Research, 2022)

Impact of land cover transformation on urban heat islands in Harbin, China - Stephen Dauda Yabo; Donglei Fu; Bo Li; Xiaofei Shi; Samit Thapa; Xie Shengjin; Lu Lu; Hong Qi; Wei Zhang (Environmental Monitoring and Assessment, 2022)

Wheat Ms2 confers complete male sterility without penalizing other traits - Huifei Zhang; Qunqun Hao; Fei Ni; Bo Lyu; Allan Caplan; Jiajie Wu; Daolin Fu (Cereal Research Communications, 2022)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

A novel anticancer property of Lycium barbarum polysaccharide in triggering ferroptosis of breast cancer cells - Xing Du; Jingjing Zhang; Ling Liu; Bo Xu; Hang Han; Wenjie Dai; Xiuying Pei; Xufeng Fu; Shaozhang Hou (Journal of Zhejiang University-SCIENCE B, 2022)

Long Non-coding Antisense RNA DDIT4-AS1 Regulates Meningitic Escherichia coli-Induced Neuroinflammation by Promoting DDIT4 mRNA Stability - Bo Yang; Bojie Xu; Ruicheng Yang; Jiyang Fu; Liang Li; Dong Huo; Jiaqi Chen; Xiaopei Yang; Chen Tan; Huanchun Chen; Xiangru Wang (Molecular Neurobiology, 2022)
Our previous studies have shown that meningitic Escherichia coli can colonize the brain and cause neuroinflammation. Controlling the balance of inflammatory responses in the host central nervous system is particularly vital. Emerging evidence has shown the important regulatory roles of long non-coding RNAs (lncRNAs) in a wide range of biological and pathological processes. However, whether lncRNAs participate in the regulation of meningitic E. coli -mediated neuroinflammation remains unknown. In the present study, we characterized a cytoplasm-enriched antisense lncRNA DDIT4-AS1 , which showed similar concordant expression patterns with its parental mRNA DDIT4 upon E. coli infection. DDIT4-AS1 modulated DDIT4 expression at both mRNA and protein levels. Mechanistically, DDIT4-AS1 promoted the stability of DDIT4 mRNA through RNA duplex formation. DDIT4-AS1 knockdown and DDIT4 knockout both attenuated E. coli -induced NF-κB signaling as well as pro-inflammatory cytokines expression, and DDIT4-AS1 regulated the inflammatory response by targeting DDIT4 . In summary, our results show that DDIT4-AS1 promotes E. coli -induced neuroinflammatory responses by enhancing the stability of DDIT4 mRNA through RNA duplex formation, providing potential nucleic acid targets for new therapeutic interventions in the treatment of bacterial meningitis.

LncRNA PVT1 facilitates DLBCL development via miR-34b-5p/Foxp1 pathway - Shi Tao; Yu Chen; Min Hu; Lu Xu; Cai-Bo Fu; Xin-Bao Hao (Molecular and Cellular Biochemistry, 2022)

Neuroprotective effect of aldose reductase knockout in a mouse model of spinal cord injury involves NF-κB pathway - Fu-xin Han; Rui Zhang; Xin-xing Yang; Shan-bo Ma; Shi-jie Hu; Bing Li (Experimental Brain Research, 2022)

Toward Exploring Topographic Effects on Evolution and Propagation of Ocean Mesoscale Eddies Through Life Cycle Across Izu-Ogasawara Ridge in Northwestern Pacific Ocean - Rui Nian; Xue Geng; Zhengguang Zhang; Minghan Yuan; Zhen Fu; Hengfu Xu; Hua Yang; Qi Lai; Hui He; Chi Wei Su; Lina Zang; Qiang Yuan; et al. (Frontiers in Marine Science, 2022)
Ocean mesoscale eddies contribute significantly to water transport on a global scale, constituting the ubiquitous, irregular, discrete, nonlinear components. In this manuscript, we propose to explore whether and how the topographic effect of one meridional ridge, could exert considerable influences on the evolution and propagation of mesoscale eddies through their life cycle, directly from the perspectives of real observation statistics. We systematically investigate the known variability of mesoscale eddy trajectories, derived by multimission satellite altimetry from 1993 to 2018, of a life cycle more than 6 months, over the Izu-Ogasawara Ridge, and quantitatively examined the eddy-ridge interaction by observation statistics and wavelet coherence map, with respect to the intrinsic attributes, namely, the amplitude, the rotation speed, the radius. Due to the spatial-temporal diversity, a series of correlative steps have been particularly designed along time-frequency domain to trace back mesoscale eddy trajectories in a variety of origins, location, lifespan, polarity, either completely or partially passing over the ridge, and to facilitate the standardization in statistics across three phases of their life cycle, i.e., before, during and after the interaction with the ridge. It has been revealed in our experiment that three intrinsic attributes of mesoscale eddies within 25 years, all demonstrated noticeable correlation with the variation of topographic relief over the ridge. We observed that most of the cyclonic eddies obviously tended to begin to decay or even demise, while on the contrary, some of the anticyclonic eddies preferred to intensify slightly, or making no significant difference when encountering the upslope until climbing across the top, basically consistent with the expectation of potential vorticity (PV) conservation. The drifting velocity agreed with the tendency that the direction would be more probably modified toward equatorward or poleward by forcing to meridional component, with zonal component reduced at the beginning. The mesoscale eddies with the passage over the ridge exhibited the relatively high average horizontal scales, amplitude, rotation speed on the whole, compared to those with only partially passage. The developed scheme could integrate more evidences on how mesoscale eddies response to the topographic effects during their time-varying evolution and propagation process, and help provide opportunities to potentially identify and predict the underlying dynamic patterns and mechanisms that mesoscale eddies engage in ocean dynamics when proceeding toward meridional ridges on a global scale, with the promise of the end-to-end data-driven solution, such as deep learning architecture involved in the future.

The traditional uses, secondary metabolites, and pharmacology of Lycopodium species - Bo Wang; Canyuan Guan; Qiang Fu (Phytochemistry Reviews, 2022)

Directed movement changes coexistence outcomes in heterogeneous environments - Bo Zhang; King‐Yeung Lam; Wei‐Ming Ni; Rossana Signorelli; Kevin M. Collins; Zhiyuan Fu; Lu Zhai; Yuan Lou; Donald L. DeAngelis; Alan Hastings (Ecology Letters, 2022)
Understanding mechanisms of coexistence is a central topic in ecology. Mathematical analysis of models of competition between two identical species moving at different rates of symmetric diffusion in heterogeneous environments show that the slower mover excludes the faster one. The models have not been tested empirically and lack inclusions of a component of directed movement toward favourable areas. To address these gaps, we extended previous theory by explicitly including exploitable resource dynamics and directed movement. We tested the mathematical results experimentally using laboratory populations of the nematode worm, Caenorhabditis elegans . Our results not only support the previous theory that the species diffusing at a slower rate prevails in heterogeneous environments but also reveal that moderate levels of a directed movement component on top of the diffusive movement allow species to coexist. Our results broaden the theory of species coexistence in heterogeneous space and provide empirical confirmation of the mathematical predictions.

Petrogenesis of the Late Triassic Mengsong strongly peraluminous granites in the southeastern Tibetan Plateau: highly fractionated from crystal mush - Feng Cong; Fu-Yuan Wu; Wen-Chang Li; De-Feng He; Zai-Bo Sun; Xiao-Ming Huang; Zhi-Zhong Hu; Han Zhao (International Geology Review, 2022)

New paraconic acids from the endophytic fungus Xylariaceae sp. J4 - Chao Yuan; Xue-Chun Shu; Lin Fan; Ying-Bo Zhang; Ling-Liang Guan; Fu-Lai Yu; Xiao-Lu Chen; Gang Li (Natural Product Research, 2022)

A community effort to assess and improve computerized interpretation of 12-lead resting electrocardiogram - Zijian Ding; Guijin Wang; Huazhong Yang; Ping Zhang; Dapeng Fu; Zhen Yang; Xinkang Wang; Xia Wang; Zhourui Xia; Chiming Zhang; Wenjie Cai; Binhang Yuan; et al. (Medical & Biological Engineering & Computing, 2022)
Computerized interpretation of electrocardiogram plays an important role in daily cardiovascular healthcare. However, inaccurate interpretations lead to misdiagnoses and delay proper treatments. In this work, we built a high-quality Chinese 12-lead resting electrocardiogram dataset with 15,357 records, and called for a community effort to improve the performances of CIE through the China ECG AI Contest 2019. This dataset covers most types of ECG interpretations, including the normal type, 8 common abnormal types, and the other type which includes both uncommon abnormal and noise signals. Based on the Contest, we systematically assessed and analyzed a set of top-performing methods, most of which are deep neural networks, with both their commonalities and characteristics. This study establishes the benchmarks for computerized interpretation of 12-lead resting electrocardiogram and provides insights for the development of new methods.

Identification of bacterial blight resistance genes in rice landraces from Yunnan Province, China - Caimei Zhao; Fuyou Yin; Ling Chen; Dingqin Li; Suqin Xiao; Qiaofang Zhong; Bo Wang; Xue Ke; Jian Fu; Xiang Li; Yue Chen; Lingxian Wang; et al. (Australasian Plant Pathology, 2022)
Bacterial blight (BB), a serious bacterial disease caused by pathogen Xanthomonas oryzae pv. oryzae ( Xoo ) affects rice growth and yield. Yunnan Province is regarded as a center of rice diversity in China and indeed the world, and has abundant rice landrace resources, which may offer prospective candidate donors in rice improvement and breeding. In this study, a set of 200 rice landraces were evaluated to determine their resistance to 10 pathogenic Xoo strains resistance by the leaf-clipping method. The results indicated that the tested rice landraces had different resistance levels against different Xoo strains. Multiple comparisons showed that the Xoo strain PXO99 was virulent to the tested rice landraces. Sixty-six rice landraces conferred resistance against at least one Xoo strain. These resistant rice landraces screened were then performed the presence of 14 cloned BB resistance genes by closely linked molecular markers and designed specific primers. The results showed that none of these resistant accessions contained xa13 , Xa21 , Xa27 , and Xa45(t) homologous fragments, while 9, 24, 4, 7, 9, 15, 1, 5, 4 and 27 accessions contained Xa1 , Xa2/Xa31(t) , Xa14 , Xa3/Xa26 , Xa4 , xa5 , Xa7 , Xa10 , Xa23 and xa25 homologous fragments, respectively. Sequence analysis further revealed that nucleotide variations around functional nucleotide polymorphisms region were observed within these accessions containing the Xa1 , Xa2/Xa31(t) , Xa14 , Xa3/Xa26 , Xa4 , xa5 , Xa10 , Xa23 and xa25 homologous fragments. These results along with phenotypic resistance spectrum supported that these accessions carried nine resistance homologous genes. Only one accession (Qishanggu_Wenshan) carried the Xa7 resistance gene. We also found that some resistant rice landraces, especially Xilandigu_Baoshan, and Laoyaling_Lincang without the above resistance genes, which mediated broad spectrum resistance to multiple Xoo strains, were identified as potential sources for breeding rice lines resistance to BB.

A novel alphahypovirus that infects the fungal plant pathogen Sclerotinia sclerotiorum - Weibo Liang; Zhongbo Lu; Jie Duan; Daohong Jiang; Jiatao Xie; Jiasen Cheng; Yanping Fu; Tao Chen; Bo Li; Xiao Yu; Weidong Chen; Yang Lin (Archives of Virology, 2022)

Anti-migration and anti-invasion effects of 2-hydroxy-6-tridecylbenzoic acid is associated with the enhancement of CYP1B1 expression through activating the AMPK signaling pathway in triple-negative breast cancer cells - Dayu Zhou; Xiaohui Zhao; Mingxi Yu; Yan Xu; Chenghao Fu; Kexin Zheng; Chao Xia; Bo Huang; Shiliang Ma (Natural Product Research, 2021)

SAR vehicle recognition via scale-coupled Incep_Dense Network (IDNet) - Bo Wang; Qingji Jiang; Dawei Song; Qiqi Zhang; Meng Sun; Xiaoxuan Fu; Junzhi Wang (International Journal of Remote Sensing, 2021)

Intra-annual radial growth and its climate response for Masson pine and Chinese fir in subtropical China - Shengwang Meng; Xiaoli Fu; Bo Zhao; Xiaoqin Dai; Qingkang Li; Fengting Yang; Liang Kou; Huimin Wang (Trees, 2021)

Molecular cloning and characterization of angiopoietin-like protein-8 gene in pigs and its tissue-specific expression in different animals - Chao-Ran Wang; Hong-Bo Xiao; Xiang-Yang Lu; Fu-Shen Huang (Biologia, 2021)

A proteomic analysis of Bcl-2 regulation of cell cycle arrest: insight into the mechanisms - Xing Du; Jingjing Xiao; Xufeng Fu; Bo Xu; Hang Han; Yin Wang; Xiuying Pei (Journal of Zhejiang University-SCIENCE B, 2021)

Degraded polysaccharides from Porphyra haitanensis: purification, physico-chemical properties, antioxidant and immunomodulatory activities - Yun-Feng Huo; Yin-Ting Li; Wei Xia; Chong Wang; Yuan-Yuan Xie; Yan-Bo Wang; Tao Zhou; Ling-Lin Fu (Glycoconjugate Journal, 2021)

Lipidomic analyses reveal enhanced lipolysis in planthoppers feeding on resistant host plants - Xiaohong Zheng; Yeyun Xin; Yaxin Peng; Junhan Shan; Ning Zhang; Di Wu; Jianping Guo; Jin Huang; Wei Guan; Shaojie Shi; Cong Zhou; Rongzhi Chen; et al. (Science China Life Sciences, 2021)

Descending Modulation of Spinal Itch Transmission by Primary Somatosensory Cortex - Zi-Han Wu; Han-Yu Shao; Yuan-Yuan Fu; Xiao-Bo Wu; De-Li Cao; Sheng-Xiang Yan; Wei-Lin Sha; Yong-Jing Gao; Zhi-Jun Zhang (Neuroscience Bulletin, 2021)

Microbial characteristics response to the soil quality of newly created farmland on the Loess Plateau - Chen Xu; Yi-ping Chen; Cui-cui Su; Ji-fu Ma; Jun-hua Wu; Kai-bo Wang; Yi Wang; Yao Jiang (Environmental Science and Pollution Research, 2021)

Effects of the virgin forests to the dissolved organic matters in small forested watershed: a case study of the Tangwang River in Northeast China - Shuhang Wang; Bo Zhang; Zhenghui Fu; Yunyan Guo; Xia Jiang (Environmental Science and Pollution Research, 2021)

Impact of climate change on snowmelt runoff in a Himalayan basin, Nepal - Samit Thapa; Haizhi Li; Bo Li; Donglei Fu; Xiaofei Shi; Stephen Yabo; Lu Lu; Hong Qi; Wei Zhang (Environmental Monitoring and Assessment, 2021)

Lignin Synthesis Related Genes with Potential Significance in the Response of Upland Cotton to Fusarium Wilt Identified by Transcriptome Profiling - Jianan Hou; Fu’an Zhao; Xiaojie Yang; Wu Li; Deyi Xie; Zhongjie Tang; Shuping Lv; Lihong Nie; Yao Sun; Mengmeng Wang; Yajing Zhu; Xiaopei Bo; et al. (Tropical Plant Biology, 2021)
Fusarium wilt, caused by the fungus Fusarium oxysporum Schlecht. f. sp. vasinfectum (Fov) is a destructive soil-borne cotton disease. To profile the genes and pathways responding to Fov infection, we compared transcriptomic responses before and after F. oxysporum inoculation in a highly resistant cotton cultivar, Yumian21, and a highly susceptible cultivar, Jimian11. Although the overall gene expression pattern was downregulated in both cultivars, the global gene expression in the resistant cultivar was stronger than that in the susceptible cultivar. In addition, the expressed genes of two cultivars mostly differed in “cellular process,” “single-organism process,” “metabolic process,” and “response to stimulus” functional groups in the biological process Gene Ontology category: the upregulated differentially expressed genes (DEG) were largely enriched in the resistant cultivar, while the downregulated DEGs were largely enriched in the susceptible cultivar. Phenylpropanoid biosynthesis and phenylalanine metabolism are the key metabolic pathways in cotton in response to Fov. We found that lignin plays a potential role in cotton resistance to Fov. Two coding genes, caffeic acid 3-O-methyltransferase and peroxidase2 , as well as the two transcription factors MYB46 and MYB86 , are possibly involved in the accumulation and synthesis of lignin. Furthermore, the result showed that the quantification of lignin could be potentially used as a selection tool to identify Fusarium wilt resistant cotton.

A new chlorine-containing iridoid glycoside from Plantago maxima - Liang-Liang Ma; Lu-Lu Wang; Yue-Feng Zhang; Xiang-Fu Jiang; Xin-Liu Zhu; Ke Pan; Chuan-Xing Wan; Zhong-Bo Zhou (Natural Product Research, 2021)

Newly isolated strain of Trichoderma asperellum from disease suppressive soil is a potential bio-control agent to suppress Fusarium soil borne fungal phytopathogens - Theint Theint Win; Bo Bo; Przemyslaw Malec; Sikandar Khan; Pengcheng Fu (Journal of Plant Pathology, 2021)

Effects of Spray Parameters on the Effective Spray Width of Single-Rotor Drone in Sugarcane Plant Protection - Ping Zhang; Wei Zhang; Hai-Tian Sun; Feng-Guang He; Hai-Ba Fu; Li-Qiang Qi; Li-Juan Yu; Li-Yu Jin; Bo Zhang; Jian-Sheng Liu (Sugar Tech, 2021)

Warming Iron-Limited Oceans Enhance Nitrogen Fixation and Drive Biogeographic Specialization of the Globally Important Cyanobacterium Crocosphaera - Nina Yang; Carlin A. Merkel; Yu-An Lin; Naomi M. Levine; Nicholas J. Hawco; Hai-Bo Jiang; Ping-Ping Qu; Michelle A. DeMers; Eric A. Webb; Fei-Xue Fu; David A. Hutchins (Frontiers in Marine Science, 2021)
Primary productivity in the nutrient-poor subtropical ocean gyres depends on new nitrogen inputs from nitrogen fixers that convert inert dinitrogen gas into bioavailable forms. Temperature and iron (Fe) availability constrain marine nitrogen fixation, and both are changing due to anthropogenic ocean warming. We examined the physiological responses of the globally important marine nitrogen fixer, Crocosphaera watsonii across its full thermal range as a function of iron availability. At the lower end of its thermal range, from 22 to 27°C, Crocosphaera growth, nitrogen fixation, and Nitrogen-specific Iron Use Efficiencies (N-IUEs, mol N fixed hour –1 mol Fe –1 ) increased with temperature. At an optimal growth temperature of 27°C, N-IUEs were 66% higher under iron-limited conditions than iron-replete conditions, indicating that low-iron availability increases metabolic efficiency. However, Crocosphaera growth and function decrease from 27 to 32°C, temperatures that are predicted for an increasing fraction of tropical oceans in the future. Altogether, this suggests that Crocosphaera are well adapted to iron-limited, warm waters, within prescribed limits. A model incorporating these results under the IPCC RCP 8.5 warming scenario predicts that Crocosphaera N-IUEs could increase by a net 47% by 2100, particularly in higher-latitude waters. These results contrast with published responses of another dominant nitrogen fixer ( Trichodesmium ), with predicted N-IUEs that increase most in low-latitude, tropical waters. These models project that differing responses of Crocosphaera and Trichodesmium N-IUEs to future warming of iron-limited oceans could enhance their current contributions to global marine nitrogen fixation with rates increasing by ∼91 and ∼22%, respectively, thereby shifting their relative importance to marine new production and also intensifying their regional divergence. Thus, interactive temperature and iron effects may profoundly transform existing paradigms of nitrogen biogeochemistry and primary productivity in open ocean regimes.

The MYB transcription factor Baymax1 plays a critical role in rice male fertility - Xiao-Jiao Xiang; Lian-Ping Sun; Ping Yu; Zheng-Fu Yang; Pei-Pei Zhang; Ying-Xin Zhang; Wei-Xun Wu; Dai-Bo Chen; Xiao-Deng Zhan; Riaz-Muhammad Khan; Adil Abbas; Shi-Hua Cheng; et al. (Theoretical and Applied Genetics, 2021)

Characteristics of soil organic carbon fractions under different land use patterns in a tropical area - Zhizhong Zhao; Zeyang Zhao; Bo Fu; Junguang Wang; Wei Tang (Journal of Soils and Sediments, 2021)

Response of palladium in receiving water bodies to rainfall-runoff - Fangfang Ding; Yuyan Liu; Zucheng Wang; Caiye Ji; Dan Wu; Lin Wang; Bo Fu; Lan Zhang; Haofeng Liu (Environmental Science and Pollution Research, 2021)

Melatonin ameliorates spatial memory and motor deficits via preserving the integrity of cortical and hippocampal dendritic spine morphology in mice with neurotrauma - Xiao-Jing Lin; Ruoxu Liu; Chenyi Li; Xueqing Yi; Bo Fu; M. J. Walker; Xiao-Ming Xu; Gang Sun; Cheng-Hsien Lin (Inflammopharmacology, 2020)

Microscopic and Fractal Characterization of Organic Matter within Lacustrine Shale Reservoirs in the First Member of Cretaceous Qingshankou Formation, Songliao Basin, Northeast China - Bo Liu; Meng Yan; Xianda Sun; Yunfeng Bai; Longhui Bai; Xiaofei Fu (Journal of Earth Science, 2020)

Characteristics of methane emissions in the Living Water Garden in Chengdu City from 2012 to 2017 - Ru Xue; Xiaoling Liu; Xiaoying Fu; Hongbing Luo; Ke Zhang; Bruce C. Anderson; Mei Li; Bo Huang; Lijuan Yu; Xiaoting Li; Shuzhi Fu; Aiping Pu; et al. (Environmental Science and Pollution Research, 2020)

Improvements of the coupled WRF-Lake model over Lake Nam Co, Central Tibetan Plateau - Yang Wu; Anning Huang; Lazhu; Xianyu Yang; Bo Qiu; Lijuan Wen; Zhiqi Zhang; Zhipeng Fu; Xueyan Zhu; Xindan Zhang; Shuxin Cai; Yong Tang (Climate Dynamics, 2020)
A series of model sensitivity simulations are carried out to calibrate and improve the Weather Research and Forecasting Model coupled with a one-dimensional lake model (WRF-Lake) based on observations over Lake Nam Co. Using the default lake model parameters, the solution of WRF-Lake exhibits significant biases in both the lake thermodynamics and regional climatology, i.e., higher lake surface temperature (LST), earlier onset of summer thermal stratification, and overestimated near-surface air temperature and precipitation induced by the lake’s excessive warming and moistening impacts. The performance of WRF-Lake is improved through adjusting the initial lake temperature profile, the temperature of maximum water density (Tdmax), the surface roughness length, and the light extinction coefficient. Results show that initializing the water temperature with spring observation mitigates the LST overestimation and reduces the timing error of the onset of thermal stratification. By further adjusting Tdmax from 4 °C to the observed value of 3.5 °C, the LST increase from June to mid-July is enhanced and the buildup of thermal stratification is more accurately predicted. Through incorporating the parameterized surface roughness length and decreasing the light extinction coefficient, the model better reproduces the observed daily evolution of LST and vertical lake temperature profile. The calibrated WRF-Lake effectively mitigates the overestimation of over-lake air temperature at 2 m height and precipitation over regions downwind the lake. This suggests that an improved lake scheme within the coupled WRF-Lake is essential for realistically simulating the lake–air interactions and the regional climate over the lake-rich Tibetan Plateau.

Elastic wave propagation and scattering in prestressed porous rocks - Li-Yun Fu; Bo-Ye Fu; Weijia Sun; Tongcheng Han; Jianlin Liu (Science China Earth Sciences, 2020)

Dynamic Change of Shanks Gene mRNA Expression and DNA Methylation in Epileptic Rat Model and Human Patients - Yujiao Fu; Du Liu; Jialing Guo; Hongyu Long; Wenbiao Xiao; Wei Xiao; Li Feng; Zhaohui Luo; Bo Xiao (Molecular Neurobiology, 2020)

Temporal variation and distribution of size fractionated: platinum group elements and heavy metals in total suspended particulate - Yuyan Liu; Bo Fu; Cheng Liu; Yaxing Shen; Haofeng Liu; Zhang Lan (Meteorology and Atmospheric Physics, 2020)

Fishmeal level affects growth performance of Macrobrachium nipponense via regulating protein and lipid metabolism - Qun-Lan Zhou; Su-Fei Jiang; Yi-Wei Xiong; Bo Liu; Cunxin Sun; Zhenting Jiang; Hongtuo Fu (Aquaculture International, 2020)

Characterization of viromes within mosquito species in China - Jiang Du; Fan Li; Yelin Han; Shihong Fu; Bo Liu; Nan Shao; Haoxiang Su; Weijia Zhang; Dandan Zheng; Wenwen Lei; Jie Dong; Lilian Sun; et al. (Science China Life Sciences, 2020)

Reversal of Social Recognition Deficit in Adult Mice with MECP2 Duplication via Normalization of MeCP2 in the Medial Prefrontal Cortex - Bin Yu; Bo Yuan; Jian-Kun Dai; Tian-lin Cheng; Sheng-Nan Xia; Ling-Jie He; Yi-Ting Yuan; Yue-Fang Zhang; Hua-Tai Xu; Fu-Qiang Xu; Zhi-Feng Liang; Zi-Long Qiu (Neuroscience Bulletin, 2020)

Deformation characteristics and failure mechanism of a reactivated landslide in Leidashi, Sichuan, China, on August 6, 2019: an emergency investigation report - Weile Li; Bo Zhao; Qiang Xu; Fan Yang; Hao Fu; Cong Dai; Xinxin Wu (Landslides, 2020)

Design, synthesis and cholinesterase inhibitory activity of α -mangostin derivatives - Xiao-Qian Chi; Bo Hou; Liu Yang; Cheng-Ting Zi; Yong-Feng Lv; Jin-Yu Li; Fu-Cai Ren; Ming-Yan Yuan; Jiang-Miao Hu; Jun Zhou (Natural Product Research, 2020)

Trend analysis of climatic variables and their relation to snow cover and water availability in the Central Himalayas: a case study of Langtang Basin, Nepal - Samit Thapa; Bo Li; Donglei Fu; Xiaofei Shi; Bo Tang; Hong Qi; Kun Wang (Theoretical and Applied Climatology, 2020)

Synthesis and biological effects of naphthalene-chalcone derivatives - Qing-Hao Jin; Hong-Hai Chen; Wen-Bo Chen; Zhi-Yang Fu; Li-Ping Guan; Hai-Ying Jiang (Medicinal Chemistry Research, 2020)

Numerical simulation study of strip filling for water-preserved coal mining - Wei Bo Sun; Yan Wang; Hua Fu Qiu; Zi Wei Ding (Environmental Science and Pollution Research, 2020)

Impacts of ontogenetic and altitudinal changes on morphological traits and biomass allocation patterns of Fritillaria unibracteata - Bo Xu; Jin-niu Wang; Fu-sun Shi (Journal of Mountain Science, 2020)

Identification and Expression Pattern Analysis of Bacterial Blight Resistance Genes in Oryza officinalis Wall ex Watt Under Xanthomonas oryzae Pv. oryzae Stress - Chunmiao Jiang; Suqin Xiao; Dingqin Li; Ling Chen; Qiaofang Zhong; Fuyou Yin; Tengqiong Yu; Xue Ke; Dunyu Zhang; Jian Fu; Yue Chen; Bo Wang; et al. (Plant Molecular Biology Reporter, 2019)
Background Bacterial blight (BB) caused by Xanthomonas oryzae Pv. oryzae ( Xoo ) is one of the most serious diseases of rice worldwide. Oryza officinalis Wall ex Watt, harboring abundant genetic diversity and disease resistance features, are important resources of exploring resistance genes with broad-spectrum resistance to BB. However, the molecular mechanisms and genes of BB resistance in O. officinalis have been rarely explored. Results Here, the BB resistance of four different origin O. officinalis populations in Yunnan were identified by seven representative hypervirulent Xoo races, which exhibited different BB resistance among four populations, in which the BB resistance of the Gengma_Lincang population was the strongest. In addition, the pathogenetic ability of seven Xoo races to O. officinalis was different in that the pathogenicity of PXO99 was stronger than that of C5. There were no remarkable differences in leaf microstructures among four O. officinalis populations, revealing the differences in resistance of four O. officinalis to BB are caused by the endogenous resistance genes. Furthermore, our results proved that there were no nine cloned BB resistance genes in four populations but possessed dominant Xa5 , dominant Xa13 , and recessive xa3/xa26 homologous alleles of xa5 , xa13 , and Xa3 / Xa26 resistance genes. These three homologous genes were isolated and cloned from four populations and named OoXa5 , OoXa13 , and Ooxa3 / xa26 . The expression profile revealed that the expression levels of OoXa13 and Ooxa3/xa26 were significantly down-regulated under PXO99 and C5 stress, especially in the Gengma_Lincang population, suggesting the O. officinalis might enhance BB resistance by down-regulating the expression level of OoXa13 and Ooxa3 / xa26 . Conclusion The BB resistance genes of O. officinalis had its own characteristics by expression pattern and BLAST analysis of OoXa5 , OoXa13 , and Ooxa3 / xa26 , which indicated that there might be new genes or molecular mechanism of BB resistance in O. officinalis. Our studies provided a solid foundation and reference for revealing the molecular mechanism of BB resistance in O. officinalis .

Factors influencing the accumulation of Pd in mangrove wetland sediments in Dongzhai Harbor, Hainan, China - Yuyan Liu; Caiye Ji; Bo Fu; Linsheng He; Qianqian Fu; Mengchen Shen; Zhizhong Zhao (Journal of Coastal Conservation, 2019)

Inositol as a new enhancer for improving lipid production and accumulation in Schizochytrium sp. SR21 - Zhao-Xin Liu; Shuai You; Bin-Ping Tang; Bo Wang; Sheng Sheng; Fu-An Wu; Jun Wang (Environmental Science and Pollution Research, 2019)

Interception of sulfate deposition from a closed canopy to a forest gap edge canopy in a subalpine dragon spruce plantation - Yu Zhang; Fu-zhong Wu; Bo Tan; Zhen-feng Xu; Han Li; Jun-cheng Liu; Hai-rong Zhao; Si-yi Tan; Cheng-ming You; Wan-qin Yang (Journal of Mountain Science, 2019)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

Electron Probe Microanalysis of Monazite and Its Applications to U-Th-Pb Dating of Geological Samples - Wenbin Ning; Junpeng Wang; Deng Xiao; Fenfang Li; Bo Huang; Dong Fu (Journal of Earth Science, 2019)

3D-Printed Wearable Personalized Orthodontic Retainers for Sustained Release of Clonidine Hydrochloride - Heliu Jiang; Junhui Fu; Mingguang Li; Shanshan Wang; Bo Zhuang; Haiyan Sun; Cheng Ge; Bin Feng; Yiguang Jin (AAPS PharmSciTech, 2019)

African Orphan Crops Consortium (AOCC): status of developing genomic resources for African orphan crops - Prasad S. Hendre; Samuel Muthemba; Robert Kariba; Alice Muchugi; Yuan Fu; Yue Chang; Bo Song; Huan Liu; Min Liu; Xuezhu Liao; Sunil Kumar Sahu; Sibo Wang; et al. (Planta, 2019)

Numerical simulation of ground motion amplification in Modong area, Lushan - Chao Han; Jiashun Yu; Wei-Zu Liu; Jian-Long Yuan; Xiao-Bo Fu; Xiao-Ping Hou (Applied Geophysics, 2019)

Transformation Mechanism of a Fault and Its Associated Microstructures in Low-Porosity Rocks: A Case Study of the Tanan Depression in the Hailar-Tamtsag Basin - Ru Jia; Bo Liu; Xiaofei Fu; Lei Gong; Zhida Liu (Journal of Marine Science and Engineering, 2019)
Faults have complex internal structures, which can be divided into the fault core and the damaged zone. During the fault formation process, the damaged zone will develop a large number of fractures cross cutting the adjacent host rocks, where the size and density of fractures would decrease as a function of distance from the fault core. Statistics show that compared with the host rocks, the rock’s secondary porosity may significantly get improved until it is 5%–10% higher than the host rock’s, and the permeability could be increased from zero to six orders of magnitude higher where fractures are developed. Based on the distribution of the fault core and damaged zone, we established an idealized geologic model to analyze the influence of the fault associated microstructures on the fluid flow efficiency. The results demonstrated that the reservoir property will be effectively improved when the fractures are developed to a certain magnitude, which will provide an advantageous conduit for fluid flow. The physical properties of wells are significantly different between the reservoirs transformed by the fractures and the reservoirs that have not been affected. The reservoir unit near faults has been modified by the associated fractures improving the reservoir quality. In addition, the portions of the reservoir farther from the fault core are less influenced and retain their initial poor characteristics. In order to evaluate the enhanced reservoir properties caused by faults and associated fractures, we performed statistical analysis of valid porosity ratio of the Nantun reservoirs as a function of the distance from 49 wells to faults in the research area. The results of this study demonstrated that connected fractures enhance the properties of the reservoirs and there is a distinct range that separates oil producing wells and water producing ones. This phenomenon verifies that faults are important and must be considered carefully during the exploration and production for hydrocarbon to provide higher quality reservoirs.

Correction to: Chronic phencyclidine treatment impairs spatial working memory in rhesus monkeys - Bo Zhang; Fei Xiong; Yuanye Ma; Bing Li; Yu Mao; Zhu Zhou; Hualin Yu; JingHui Li; Chuanyu Li; Juan Fu; Jianhong Wang; Xudong Zhao (Psychopharmacology, 2019)

Chronic phencyclidine treatment impairs spatial working memory in rhesus monkeys - Bo Zhang; Fei Xiong; Yuanye Ma; Bing Li; Yu Mao; Zhu Zhou; Hualin Yu; JingHui Li; Chuanyu Li; Juan Fu; Jianhong Wang; Xudong Zhao (Psychopharmacology, 2019)

The associations of air pollution exposure during pregnancy with fetal growth and anthropometric measurements at birth: a systematic review and meta-analysis - Li Fu; Yi Chen; Xinyi Yang; Zuyao Yang; Sha Liu; Lei Pei; Baixiang Feng; Ganxiang Cao; Xin Liu; Hualiang Lin; Xing Li; Yufeng Ye; et al. (Environmental Science and Pollution Research, 2019)

Neural Differentiation of Mouse Neural Stem Cells as a Tool to Assess Developmental Neurotoxicity of Drinking Water in Taihu Lake - Yang Zhou; Yu Fu; Zhendong Bai; Peixin Li; Bo Zhao; Yuehua Han; Ting Xu; Ningyan Zhang; Lin Lin; Jian Cheng; Jun Zhang; Jing Zhang (Biological Trace Element Research, 2019)

Early Cambrian Muli arc–ophiolite complex: a relic of the Proto-Tethys oceanic lithosphere in the Qilian Orogen, NW China - Zhen Yan; Changlei Fu; Jonathan C. Aitchison; Manlan Niu; Solomon Buckman; Bo Cao (International Journal of Earth Sciences, 2019)

Whole-exome sequencing identified four loci influencing craniofacial morphology in northern Han Chinese - Wei Wu; Guiying Zhai; Zejun Xu; Bo Hou; Dahua Liu; Tianyi Liu; Wei Liu; Fu Ren (Human Genetics, 2019)

Mitochondrial Gene Heterogeneity and Population Genetics of Haemaphysalis longicornis (Acari: Ixodidae) in China - Zhong-Bo Li; Yi-Tian Fu; Tian-Yin Cheng; Guo-Min Yao; Qiang-Hong Hou; Fen Li; Yu Zhao; Feng-Cai Zou; Guo-Hua Liu (Acta Parasitologica, 2019)

Global Observations of Fine-Scale Ocean Surface Topography With the Surface Water and Ocean Topography (SWOT) Mission - Rosemary Morrow; Lee-Lueng Fu; Fabrice Ardhuin; Mounir Benkiran; Bertrand Chapron; Emmanuel Cosme; Francesco d’Ovidio; J. Thomas Farrar; Sarah T. Gille; Guillaume Lapeyre; Pierre-Yves Le Traon; Ananda Pascual; et al. (Frontiers in Marine Science, 2019)

Metanephric mesenchyme-derived Foxd1+ mesangial precursor cells alleviate mesangial proliferative glomerulonephritis - Meiling Jin; Zhong Yin; Kai Wei; Yuansheng Xie; Xueyuan Bai; Bo Fu; Zhe Feng; Qinggang Li; Xiangmei Chen (Journal of Molecular Medicine, 2019)

Dexamethasone protects the glycocalyx on the kidney microvascular endothelium during severe acute pancreatitis - Wen-qiao Yu; Shao-yang Zhang; Shui-qiao Fu; Qing-hui Fu; Wei-na Lu; Jian Zhang; Zhong-yan Liang; Yun Zhang; Ting-bo Liang (Journal of Zhejiang University-SCIENCE B, 2019)

Influence of provenance and shade on biomass production and triterpenoid accumulation in Cyclocarya paliurus - Bo Deng; Shengzuo Fang; Xulan Shang; Xiangxiang Fu; Yan Li (Agroforestry Systems, 2019)

Application of the Fractal Method to the Characterization of Organic Heterogeneities in Shales and Exploration Evaluation of Shale Oil - Bo Liu; Liangwen Yao; Xiaofei Fu; Bo He; Longhui Bai (Journal of Marine Science and Engineering, 2019)
The first member of the Qingshankou Formation, in the Gulong Sag in the northern part of the Songliao Basin, has become an important target for unconventional hydrocarbon exploration. The organic-rich shale within this formation not only provides favorable hydrocarbon source rocks for conventional reservoirs, but also has excellent potential for shale oil exploration due to its thickness, abundant organic matter, the overall mature oil generation state, high hydrocarbon retention, and commonly existing overpressure. Geochemical analyses of the total organic carbon content (TOC) and rock pyrolysis evaluation (Rock-Eval) have allowed for the quantitative evaluation of the organic matter in the shale. However, the organic matter exhibits a highly heterogeneous spatial distribution and its magnitude varies even at the millimeter scale. In addition, quantification of the TOC distribution is significant to the evaluation of shale reservoirs and the estimation of shale oil resources. In this study, well log data was calibrated using the measured TOC of core samples collected from 11 boreholes in the study area; the continuous TOC distribution within the target zone was obtained using the △logR method; the organic heterogeneity of the shale was characterized using multiple fractal models, including the box-counting dimension (Bd), the power law, and the Hurst exponent models. According to the fractal dimension (D) calculation, the vertical distribution of the TOC was extremely homogeneous. The power law calculation indicates that the vertical distribution of the TOC in the first member of the Qingshankou Formation is multi-fractal and highly heterogeneous. The Hurst exponent varies between 0.23 and 0.49. The lower values indicate higher continuity and enrichment of organic matter, while the higher values suggest a more heterogeneous organic matter distribution. Using the average TOC, coefficient of variation (CV), Bd, D, inflection point, and the Hurst exponent as independent variables, the interpolation prediction method was used to evaluate the exploration potential of the study area. The results indicate that the areas containing boreholes B, C, D, F, and I in the western part of the Gulong Sag are the most promising potential exploration areas. In conclusion, the findings of this study are of significant value in predicting favorable exploration zones for unconventional reservoirs.

The tectono-magmatic evolution of the West Junggar terrane (NW China) unravelled by U–Pb ages of detrital zircons in modern river sands - Bo Liu; Bao-Fu Han; En-Pu Gong; Jia-Fu Chen (International Geology Review, 2019)

Assembly and dispersal history of continental blocks within the Altun-Qilian-North Qaidam mountain belt, NW China - Changlei Fu; Zhen Yan; Xianqing Guo; Manlan Niu; Bo Cao; Qi Wu; Xiucai Li; Zongqi Wang (International Geology Review, 2019)

Improved Jayaweera-Mikkelsen model to quantify ammonia volatilization from rice paddy fields in China - Xiaoying Zhan; Chuan Chen; Qihui Wang; Feng Zhou; Kentaro Hayashi; Xiaotang Ju; Shu Kee Lam; Yonghua Wang; Yali Wu; Jin Fu; Luping Zhang; Shuoshuo Gao; et al. (Environmental Science and Pollution Research, 2019)

Application of computed tomography in the analysis of glass beads unearthed in Shanpula cemetery (Khotan), Xinjiang Uyghur Autonomous Region - Qian Cheng; Xueyan Zhang; Jinlong Guo; Bo Wang; Yong Lei; Guangzhao Zhou; Ya’nan Fu (Archaeological and Anthropological Sciences, 2019)

Optimized back analysis method for stress determination based on identification of local stress measurements and its application - Qitao Pei; Xiuli Ding; Yuankun Liu; Bo Lu; Shuling Huang; Jing Fu (Bulletin of Engineering Geology and the Environment, 2019)

Luminescence chronology of the Palaeolithic–Neolithic transition in the Yujiagou site at the Nihewan Basin, northern China - Xue Rui; Yu‐Jie Guo; Jia‐Fu Zhang; Yue Hu; Hui‐Jie Mei; You‐Ping Wang; Fei Xie; Bo Li (Journal of Quaternary Science, 2019)
The relationship between the Palaeolithic–Neolithic cultural transition and environmental changes is important for understanding human history. However, the timing and nature of human behaviour at the transition, and their relationship to local environmental conditions, remain poorly understood. The Yujiagou archaeological site in the Nihewan Basin, northern China, provides valuable chronological and archaeological information about cultural changes in northern China due to its continuous archaeological sequence of cultural layers from the Palaeolithic to Neolithic. In this study, we apply post‐infrared infrared stimulated luminescence (pIRIR) dating on individual feldspar grains to date the Yujiagou deposits. We provide a revised chronology for the archaeological sequence at the site. We combine these results with multi‐proxy climatic indicators to gain insights into palaeoenvironmental changes in the region. The results show that the age of the artefact‐bearing deposits ranges from 13.5 to 9.7 ka. Polished stones and pottery begin to occur in the archaeological layer around 13 ka, corresponding to a transitional period when the local climate changed from cold to warm. This site provides evidence for understanding the process that led to the regional transition from hunter‐gathering to farming.

Reduced hsa-miR-124-3p levels are associated with the poor survival of patients with hepatocellular carcinoma - Hui-Deng Long; Yu-Shui Ma; Hui-Qiong Yang; Shao-Bo Xue; Ji-Bin Liu; Fei Yu; Zhong-Wei Lv; Ji-Yu Li; Ru-Ting Xie; Zheng-Yan Chang; Gai-Xia Lu; Wen-Ting Xie; et al. (Molecular Biology Reports, 2018)

Saikosaponin-d inhibits proliferation by up-regulating autophagy via the CaMKKβ–AMPK–mTOR pathway in ADPKD cells - Weiwei Shi; Dechao Xu; Junhui Gu; Cheng Xue; Bo Yang; Lili Fu; Shuwei Song; Dongmei Liu; Wei Zhou; Jiayi Lv; Ke Sun; Meihan Chen; et al. (Molecular and Cellular Biochemistry, 2018)

Enzymatic gene expression by Pleurotus tuoliensis (Bailinggu): differential regulation under low temperature induction conditions - Shuang Hua; Bo Zhang; Yongping Fu; Bao Qi; Yanshuang Li; Fenghua Tian; Yu Li (World Journal of Microbiology and Biotechnology, 2018)

Spatiotemporal characteristics of earthquake disaster losses in China from 1993 to 2016 - Xiaoli Li; Zhiqiang Li; Jiansi Yang; Yaohui Liu; Bo Fu; Wenhua Qi; Xiwei Fan (Natural Hazards, 2018)

A new abietane diterpenoid from the roots of Tripterygium regelii - Zhi-Hua Jiang; Yan-Ping Liu; Miao He; Jin-Hua Zhao; Ting-Ting Wang; Xing-Yang Feng; Hao Yue; Ren-Bo An; Yan-Hui Fu (Natural Product Research, 2018)

The relative abundance of alkane‐degrading bacteria oscillated similarly to a sinusoidal curve in an artificial ecosystem model from oil‐well products - Guoqiang Li; Peike Gao; Bo Zhi; Bing Fu; Ge Gao; Zhaohui Chen; Mengli Gao; Mengmeng Wu; Ting Ma (Environmental Microbiology, 2018)
Summary Microbial phylogenetic diversity and species interactions in natural ecosystems have been investigated extensively, but our knowledge about their ecological roles, community dynamics and succession patterns is far from complete. This knowledge is essential to understand the complicated interactions of microorganisms in natural ecosystems. Here, an artificial ecosystem model of microorganisms was constructed from oil‐well products and cultivated in a chemostat to investigate the succession pattern of alkane‐degrading bacteria, a functional population in oil reservoirs. Their abundance was quantified by an improved qPCR technique. Our results showed that the phylogenetic structure of this artificial ecosystem model is stable during most of the chemostat cultivation process, while the genotype structure of alkane‐degrading bacteria containing alk B genes shifted and their relative abundance oscillated similarly to a sinusoidal curve, like the succession pattern of producers in the Lotka–Volterra model. These results suggest that some theoretical frameworks of macroecology may work well in microbial ecosystems and be an efficient tool to understand them.

Effects of heat stress on piglet production/performance parameters - Zhenhua Guo; Lei Lv; Di Liu; Bo Fu (Tropical Animal Health and Production, 2018)

Kinetics and mechanism of diclofenac removal using ferrate(VI): roles of Fe3+, Fe2+, and Mn2+ - Junfeng Zhao; Qun Wang; Yongsheng Fu; Bo Peng; Gaofeng Zhou (Environmental Science and Pollution Research, 2018)

Host species effects on bacterial communities associated with the fruiting bodies of Tuber species from the Sichuan Province in Southwest China - Lei Ye; Qiang Li; Yu Fu; Pierre Sourzat; Hao Tan; Jie Zou; Bo Zhang; Xiaolin Li (Mycological Progress, 2018)

Remapping of the stripe rust resistance gene Yr10 in common wheat - Cuiling Yuan; Jingzheng Wu; Baiqiang Yan; Qunqun Hao; Chaozhong Zhang; Bo Lyu; Fei Ni; Allan Caplan; Jiajie Wu; Daolin Fu (Theoretical and Applied Genetics, 2018)

Transdimensional Bayesian inversion of time-domain airborne EM data - Zong-Hui Gao; Chang-Chun Yin; Yan-Fu Qi; Bo Zhang; Xiu-Yan Ren; Yong-Chao Lu (Applied Geophysics, 2018)

Microarray expression profiling and co-expression network analysis of circulating LncRNAs and mRNAs associated with neurotoxicity induced by BPA - Wei Pang; Fu-Zhi Lian; Xue Leng; Shu-min Wang; Yi-bo Li; Zi-yu Wang; Kai-ren Li; Zhi-xian Gao; Yu-gang Jiang (Environmental Science and Pollution Research, 2018)

Isotope Chronology and Geochemistry of the Lower Carboniferous Granite in Xilinhot, Inner Mongolia, China - Xiaocheng Zhao; Wenxiao Zhou; Dong Fu; Bo Huang; Mengchun Ge (Journal of Earth Science, 2018)

Gcn5‐dependent histone H3 acetylation and gene activity is required for the asexual development and virulence of Beauveria bassiana - Qing Cai; Juan‐Juan Wang; Bo Fu; Sheng‐Hua Ying; Ming‐Guang Feng (Environmental Microbiology, 2018)
Summary Gcn5 is a core histone acetyltransferase that catalyzes histone H3 acetylation on N‐terminal lysine residues in yeasts and was reported to catalyze H3K9/K14 acetylation required for activating asexual development in Aspergillus . Here, we report a localization of Gcn5 ortholog in the nucleus and cytoplasm of Beauveria bassiana , a fungal insect pathogen. Deletion of gcn5 led to hypoacetylated H3 at K9/14/18/27 and 97% reduction in conidiation capacity as well as severe defects in colony growth and conidial thermotolerance. Two master conidiation genes, namely brlA and abaA , were transcriptionally repressed to undetectable level in Δ gcn5 , but sharply upregulated in wild‐type, at the beginning time of conidiation. Based on chromatin immunoprecipitation, both DNA and acetylation levels of the distal and proximal fragments of the brlA promoter bound by acetylated H3K14 alone were upregulated in wild‐type, but not in Δ gcn5 , at the mentioned time. In Δ gcn5 , normal cuticle infection was abolished while virulence through cuticle‐bypassing infection was greatly attenuated, accompanied by drastically reduced activities of putative cuticle‐degrading enzymes, retarded dimorphic transition and transcriptional repression of associated genes. These findings unveil a novel mechanism by which Gcn5 activates asexual development pathway by acetylating H3K14 and regulates the virulence‐related cellular events in B. bassiana .

VPS9 domain‐containing proteins are essential for autophagy and endocytosis in Pyricularia oryzae - Xue‐Ming Zhu; Shuang Liang; Huan‐Bin Shi; Jian‐Ping Lu; Bo Dong; Qian‐Sheng Liao; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2018)
Summary Pyricularia oryzae is the causal pathogen of rice blast disease. Autophagy has been shown to play important roles in P . oryzae development and plant infection. The P. oryzae endosomal system is highly dynamic and has been shown to be associated with conidiogenesis and pathogenicity as well. To date, the crosstalk between autophagy and endocytosis has not been explored in P. oryzae . Here, we identified three P. oryzae VPS9 domain‐containing proteins, PoVps9, PoMuk1 and PoVrl1. We found that PoVps9 and PoMuk1 are localized to vesicles and are each co‐localized with PoVps21, a recognized marker of early endosomes. Deletion of PoVPS9 resulted in severe defects in endocytosis and autophagosome degradation and impaired the localization of PoVps21 to endosomes. Additionally, deletion of the PoMUK1 gene in the Δ Povps9 mutant background exhibited more severe defects in development, autophagy and endocytosis compared with the Δ Povps9 mutant. Pull‐down assay showed that PoVps9 interacts with PoVps21, PoRab11 and PoRab1, which have been verified to participate in endocytosis. Furthermore, yeast two‐hybrid and co‐immunoprecipitation assays confirmed that PoVps9 directly interacts with the GDP form of PoVps21. Thus, PoVps9 is a key protein involved in autophagy and in endocytosis.

Sp1 is an important transcriptional regulation factor for forkhead box N1 in pig - Dong Jie Zhang; Liang Wang; Zhong Qiu Li; Bo Fu; Guo Wei Yang; Di Liu (Journal of Genetics, 2018)

3D forward modeling and response analysis for marine CSEMs towed by two ships - Bo Zhang; Chang-Chun Yin; Yun-He Liu; Xiu-Yan Ren; Yan-Fu Qi; Jing Cai (Applied Geophysics, 2018)

Fiber-type distribution and expression of myosin heavy chain isoforms in newborn heterozygous myostatin-knockout pigs - Xiao-Xu Xing; Mei-Fu Xuan; Long Jin; Qing Guo; Zhao-Bo Luo; Jun-Xia Wang; Qi-Rong Luo; Guang-Lei Zhang; Cheng-Du Cui; Zheng-Yun Cui; Jin-Dan Kang; Xi-Jun Yin (Biotechnology Letters, 2017)

Molecular diversity of phenothiazines: design and synthesis of phenothiazine–dithiocarbamate hybrids as potential cell cycle blockers - Dong-Jun Fu; Ruo-Han Zhao; Jia-Huan Li; Jia-Jia Yang; Ruo-Wang Mao; Bo-Wen Wu; Ping Li; Xiao-Lin Zi; Qing-Qing Zhang; Hui-Jie Cai; Sai-Yang Zhang; Yan-Bing Zhang; et al. (Molecular Diversity, 2017)

Drought Alleviated the Negative Effects of Elevated O3 on Lonicera maackii in Urban Area - Sheng Xu; Wei Fu; Xingyuan He; Wei Chen; Weiwei Zhang; Bo Li; Yanqing Huang (Bulletin of Environmental Contamination and Toxicology, 2017)

Behavioural genetic differences between Chinese and European pigs - Qingpo Chu; Tingting Liang; Lingling Fu; Huizhi Li; Bo Zhou (Journal of Genetics, 2017)

Developing the science product algorithm testbed for Chinese next-generation geostationary meteorological satellites: Fengyun-4 series - Min Min; Chunqiang Wu; Chuan Li; Hui Liu; Na Xu; Xiao Wu; Lin Chen; Fu Wang; Fenglin Sun; Danyu Qin; Xi Wang; Bo Li; et al. (Journal of Meteorological Research, 2017)

Simple additive simulation overestimates real influence: altered nitrogen and rainfall modulate the effect of warming on soil carbon fluxes - Xiangyin Ni; Wanqin Yang; Zemin Qi; Shu Liao; Zhenfeng Xu; Bo Tan; Bin Wang; Qinggui Wu; Changkun Fu; Chengming You; Fuzhong Wu (Global Change Biology, 2017)
Experiments and models have led to a consensus that there is positive feedback between carbon (C) fluxes and climate warming. However, the effect of warming may be altered by regional and global changes in nitrogen (N) and rainfall levels, but the current understanding is limited. Through synthesizing global data on soil C pool, input and loss from experiments simulating N deposition, drought and increased precipitation, we quantified the responses of soil C fluxes and equilibrium to the three single factors and their interactions with warming. We found that warming slightly increased the soil C input and loss by 5% and 9%, respectively, but had no significant effect on the soil C pool. Nitrogen deposition alone increased the soil C input (+20%), but the interaction of warming and N deposition greatly increased the soil C input by 49%. Drought alone decreased the soil C input by 17%, while the interaction of warming and drought decreased the soil C input to a greater extent (−22%). Increased precipitation stimulated the soil C input by 15%, but the interaction of warming and increased precipitation had no significant effect on the soil C input. However, the soil C loss was not significantly affected by any of the interactions, although it was constrained by drought (−18%). These results implied that the positive C fluxes–climate warming feedback was modulated by the changing N and rainfall regimes. Further, we found that the additive effects of [warming × N deposition] and [warming × drought] on the soil C input and of [warming × increased precipitation] on the soil C loss were greater than their interactions, suggesting that simple additive simulation using single‐factor manipulations may overestimate the effects on soil C fluxes in the real world. Therefore, we propose that more multifactorial experiments should be considered in studying Earth systems.

Cancer risk from gaseous carbonyl compounds in indoor environment generated from household coal combustion in Xuanwei, China - Ka-Hei Lui; Wen-Ting Dai; Chi-Sing Chan; Linwei Tian; Bo-Fu Ning; Yiping Zhou; Xiaolin Song; Bei Wang; Jinwen Li; Jun-Ji Cao; Shun-Cheng Lee; Kin-Fai Ho (Environmental Science and Pollution Research, 2017)

CDK inhibitor SU9516 induces tetraploid blastocyst formation from parthenogenetically activated porcine embryos - Qing Guo; Long Jin; Hai-Ying Zhu; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Guang-Lei Zhang; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Jin-Dan Kang; et al. (Biotechnology Letters, 2017)

Unusual incubation behavior and embryonic tolerance of hypothermia in the Sichuan Partridge (Arborophila rufipectus) - Yiqiang Fu; Bo Dai; Longying Wen; Benping Chen; Simon Dowell; Zhengwang Zhang (Journal of Ornithology, 2017)

Both AtrbohD and AtrbohF are essential for mediating responses to oxygen deficiency in Arabidopsis - Bo Liu; Lirong Sun; Liya Ma; Fu-Shun Hao (Plant Cell Reports, 2017)

Characterization and speciation of mercury in mosses and lichens from the high-altitude Tibetan Plateau - Jun-juan Shao; Cheng-bin Liu; Qing-hua Zhang; Jian-jie Fu; Rui-qiang Yang; Jian-bo Shi; Yong Cai; Gui-bin Jiang (Environmental Geochemistry and Health, 2017)

Knockdown of cardiac Kir3.1 gene with siRNA can improve bradycardia in an experimental sinus bradycardia rat model - Yang Li; Xiaodan Fu; Zhi Zhang; Bo Yu (Molecular and Cellular Biochemistry, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Elements in Fine Particulate Matter (PM $$_{2.5}$$ 2.5 ) from Indoor Air During Household Stoves Coal Combustion at Xuanwei, China - K. H. Lui; C. S. Chan; Linwei Tian; Bo-Fu Ning; Yiping Zhou; Xiaolin Song; Jinwen Li; Jun-Ji Cao; S. C. Lee; K. F. Ho (Aerosol Science and Engineering, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Early Cretaceous porphyry copper mineralization in Northeast China: the Changfagou example - Yong Zhang; Shu–Wen Xing; Chao Li; Shi–Fu Liang; Zheng–Tao Yu; Xiao–Hui Du; Yan Wang; Zeng–Jie Zhang; Yu–Bo Ma (International Geology Review, 2017)

Exploring the potential role of feature selection in global land-cover mapping - Le Yu; Haohuan Fu; Bo Wu; Nicolas Clinton; Peng Gong (International Journal of Remote Sensing, 2016)

Boundary-reflected waves and ultrasonic coda waves in rock physics experiments - Bo-Ye Fu; Li-Yun Fu; Wei Wei; Yan Zhang (Applied Geophysics, 2016)

MoRad6‐mediated ubiquitination pathways are essential for development and pathogenicity in Magnaporthe oryzae - Huan‐Bin Shi; Guo‐Qing Chen; Ya‐Ping Chen; Bo Dong; Jian‐Ping Lu; Xiao‐Hong Liu; Fu‐Cheng Lin (Environmental Microbiology, 2016)
Summary The ubiquitin system modulates protein functions through targeting substrates for ubiquitination. Here, E2 conjugating enzyme MoRad6‐related ubiquitination pathways are identified and analyzed in Magnaporthe oryzae , the causal agent of rice blast disease. Disruption of MoRad6 leads to severe defects in growth, sporulation, conidial germination, appressorium formation, and plant infection. To depict the functions of MoRad6, three putative ubiquitin ligases, MoRad18, MoBre1 and MoUbr1, are also characterized. Deletion of MoRad18 causes minor phenotypic changes, while MoBre1 is required for growth, conidiation and pathogenicity in M. oryzae . Defects in ΔMobre1 likely resulted from the reduction in di‐ and tri‐methylation level of Histone 3 lysine 4 (H3K4). Notably, MoUbr1 is crucial for conidial adhesion and germination, possibly by degrading components of cAMP/PKA and mitogen‐activated protein kinase (MAPK) Pmk1 signaling pathways via the N‐end rule pathway. Germination failure of ΔMoubr1 conidia could be rescued by elevation of cAMP level or enhanced Pmk1 phosphorylation resulting from further deletion of MoIra1, the M. oryzae homolog of yeast Ira1/2. These reveal vital effects of cAMP/PKA and MAPK Pmk1 signaling on conidial germination in M. oryzae . Altogether, our results suggest that MoRad6‐mediated ubiquitination pathways are essential for the infection‐related development and pathogenicity of M. oryzae .

Transcriptome analysis of sika deer in China - Bo-Yin Jia; Heng-Xing Ba; Gui-Wu Wang; Ying Yang; Xue-Zhe Cui; Ying-Hua Peng; Jun-Jun Zheng; Xiu-Mei Xing; Fu-He Yang (Molecular Genetics and Genomics, 2016)

Sensitivity of a regional climate model to land surface parameterization schemes for East Asian summer monsoon simulation - Wenkai Li; Weidong Guo; Yongkang Xue; Congbin Fu; Bo Qiu (Climate Dynamics, 2016)

Combination of antibiotics suppressed the increase of a part of ARGs in fecal microorganism of weaned pigs - Huizhi Li; Qingpo Chu; Feilong Xu; Lingling Fu; Tingting Liang; Yuan Li; Bo Zhou (Environmental Science and Pollution Research, 2016)

Characterization of the waxy gene in diploid Triticum L. and Aegilops L. species and its geographic distribution - Wei Li; Bang-Bo Fu; Zhe Li; Ya-Xi Liu; Zhi-En Pu; Peng-Fei Qi; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng (Genetic Resources and Crop Evolution, 2016)

Improvement and comparison of the rainfall–runoff methods in SWAT at the monsoonal watershed of Baocun, Eastern China - Qin-Bo Cheng; Christian Reinhardt-Imjela; Xi Chen; Achim Schulte; Xiang Ji; Fu-Lin Li (Hydrological Sciences Journal, 2016)

Removal of Color Compounds from Sugarcane Juice by Modified Sugarcane Bagasse: Equilibrium and Kinetic Study - Bo-hua Chai; He-cheng Meng; Zhen-gang Zhao; Qiang Huang; Xiong Fu (Sugar Tech, 2016)

Antinociceptive effects induced by intra-lateral habenula complex injection of the galanin receptor 1 agonist M617 in rats - Li-Bo Fu; Ying Wang; Xiao-Xiao Sun; Xiao-Xia Liu; Ying Wang; Wen Zhuang (Experimental Brain Research, 2016)

Enhancement of naphthalene tolerance in transgenic Arabidopsis plants overexpressing the ferredoxin-like protein (ADI1) from rice - Xiao-Yan Fu; Bo Zhu; Hong-Juan Han; Wei Zhao; Yong-Sheng Tian; Ri-He Peng; Quan-Hong Yao (Plant Cell Reports, 2016)

Impact of misplaced subclavian vein catheter into jugular vein on transpulmonary thermodilution measurement variables - Wen-qiao Yu; Yun Zhang; Shao-yang Zhang; Zhong-yan Liang; Shui-qiao Fu; Jia Xu; Ting-bo Liang (Journal of Zhejiang University-SCIENCE B, 2016)

Relationships between plant colonization and soil characteristics in the natural recovery of an earthquake-triggered debris flow gully in the Wanglang National Nature Reserve, China - Bo Xu; Jin-niu Wang; Fu-sun Shi; Ning Wu (Journal of Mountain Science, 2016)

Overexpression of d-amino acid oxidase from Bradyrhizobium japonicum, enhances resistance to glyphosate in Arabidopsis thaliana - Hongjuan Han; Bo Zhu; Xiaoyan Fu; Shuanghong You; Bo Wang; Zhenjun Li; Wei Zhao; Rihe Peng; Quanhong Yao (Plant Cell Reports, 2015)

Antiviral effect of lithium chloride on infection of cells by canine parvovirus - Pei Zhou; Xinliang Fu; Zhongshan Yan; Bo Fang; San Huang; Cheng Fu; Malin Hong; Shoujun Li (Archives of Virology, 2015)

The small GTP ase MoYpt 7 is required for membrane fusion in autophagy and pathogenicity of M agnaporthe oryzae - Xiao‐Hong Liu; Si‐Miao Chen; Hui‐Min Gao; Guo‐Ao Ning; Huan‐Bin Shi; Yao Wang; Bo Dong; Yao‐Yao Qi; Dong‐Mei Zhang; Guo‐Dong Lu; Zong‐Hua Wang; Jie Zhou; et al. (Environmental Microbiology, 2015)
Summary R ab GTP ases are required for vesicle–vacuolar fusion during vacuolar biogenesis in fungi. To date, little is known about the biological functions of the R ab small GTP ase components in M agnaporthe oryzae . In this study, we investigated MoYpt 7 of M . oryzae , a homologue of the small R as‐like GTP ase Ypt7 in S accharomyces cerevisiae . Cellular localization assays showed that MoYpt 7 was predominantly localized to vacuolar membranes. Using a targeted gene disruption strategy, a Δ MoYPT7 mutant was generated that exhibited defects in mycelial growth and production of conidia. The conidia of the Δ MoYPT7 mutant were malformed and defective in the formation of appressoria. Consequently, the Δ MoYPT7 mutant failed to cause disease in rice and barley. Furthermore, the Δ MoYPT7 mutant showed impairment in autophagy, breached cell wall integrity, and higher sensitivity to both calcium and heavy metal stress. Transformants constitutively expressing an active MoYPT7 allele ( MoYPT7 ‐ CA , G ln67 L eu) exhibited distinct phenotypes from the Δ MoYPT7 mutant. Expression of MoYPT7 ‐ CA in MoYpt 7 reduced pathogenicity and produced more appressoria‐forming single‐septum conidia. These results indicate that MoYPT7 is required for fungal morphogenesis, vacuole fusion, autophagy, stress resistance and pathogenicity in M . oryzae .

Retraction Note to: Genetic polymorphisms in VDR, ESR1 and ESR2 genes may contribute to susceptibility to Parkinson’s disease: a meta-analysis - Zhan Gao; Hong-Juan Fu; Ju-Jun Xue; Zhi-Xuan Wu; Li-Bo Zhao (Molecular Biology Reports, 2015)

Isoprenaline induces epithelial–mesenchymal transition in gastric cancer cells - Yan-Jie Lu; Zhi-Jun Geng; Xiao-Yan Sun; Yu-Hong Li; Xiao-Bing Fu; Xiang-Yang Zhao; Bo Wei (Molecular and Cellular Biochemistry, 2015)

Developmental expression and localization of MHC class I molecules in the human central nervous system - Aifeng Zhang; Hong Yu; Youji He; Yuqing Shen; Ying Zhang; Jiane Liu; Bo Fu; Dan Lv; Fengqin Miao; Jianqiong Zhang (Experimental Brain Research, 2015)

Improving Rice Ability to Degrade Different Polycyclic Aromatic Hydrocarbons Through Multigene Transformation of a Hybrid Dioxygenase System - Ri-He Peng; Biao Shi; Xiao-Yan Fu; Yong-Sheng Tian; Wei Zhao; Bo Zhu; Jing Xu; Hong-Juan Han; Zhong-Yi Yuan; Kai-Hong Liu; Quan-Hong Yao (Plant Molecular Biology Reporter, 2015)

Gene expression profile of Arabidopsis under sodium bisulfite treatment by oligo-microarray analysis - Bo Zhu; Shuang-Hong You; Hong-Juan Han; Xiao-Yan Fu; Wei Zhao; Jian-Jie Gao; Yong Xue; Ri-He Peng; Quan-Hong Yao (Acta Physiologiae Plantarum, 2015)

Elevated Serum Homocysteine (Hcy) Levels May Contribute to the Pathogenesis of Cerebral Infarction - Hong-Juan Fu; Li-Bo Zhao; Ju-Jun Xue; Zhi-Xuan Wu; Yue-Ping Huang; Wei Liu; Zhan Gao (Journal of Molecular Neuroscience, 2015)

Bioconversion of H2/CO2 by acetogen enriched cultures for acetate and ethanol production: the impact of pH - Shuyun Xu; Bo Fu; Lijuan Zhang; He Liu (World Journal of Microbiology and Biotechnology, 2015)

The potential mechanism of bursal-derived BP8 on B cell developments - Xiao-Dong Liu; Fu-Bo Zhang; Hu Shan; Pu-Yan Chen (Biotechnology Letters, 2015)

A new phenylpropanoid from the roots of Euphorbia nematocypha - Hai-Yang Jia; Zhi-Xin Liao; Fu-Yue Liu; Ling Wu; Chen Xu; Bo Zuo (Natural Product Research, 2015)

Nd(III)-Induced Rice Mitochondrial Dysfunction Investigated by Spectroscopic and Microscopic Methods - Cai-Fen Xia; Long Lv; Xin-You Chen; Bo-Qiao Fu; Ke-Lin Lei; Cai-Qin Qin; Yi Liu (The Journal of Membrane Biology, 2015)

Toll-Like Receptor 2 Deficiency Shifts PrP106-126-Induced Microglial Activation from a Neurotoxic to a Neuroprotective Phenotype - Jihong Wang; Deming Zhao; Bo Pan; Yongyao Fu; Fushan Shi; Mohammed Kouadir; Lifeng Yang; Xiaomin Yin; Xiangmei Zhou (Journal of Molecular Neuroscience, 2015)

Characterization and high expression of recombinant Ustilago maydis xylanase in Pichia pastoris - Hongjuan Han; Shuang You; Bo Zhu; Xiaoyan Fu; Baihui Sun; Jin Qiu; Chengye Yu; Lei Chen; Rihe Peng; Quanhong Yao (Biotechnology Letters, 2015)

Spatial distribution of heavy metal contamination in soils near a primitive e-waste recycling site - Sheng-Xiang Quan; Bo Yan; Fan Yang; Ning Li; Xian-Ming Xiao; Jia-Mo Fu (Environmental Science and Pollution Research, 2015)

EZH2-Induced H3K27me3 is Associated with Epigenetic Repression of the ARHI Tumor-Suppressor Gene in Ovarian Cancer - Yibing Fu; Jing Chen; Bo Pang; Chunyan Li; Jing Zhao; Keng Shen (Cell Biochemistry and Biophysics, 2015)

Association of PPARγ gene polymorphisms with osteoarthritis in a southeast Chinese population - DING ZHERU; FU PEILIANG; WU YULI; WU HAISHAN; QIAN QIRONG; LI XIAOHUA; ZHAO HUI; WANG BO; FU QIWEI (Journal of Genetics, 2014)

SHRIMP U–Pb zircon age of tephra identified in the Yahe section of Liushan Basin and its significance as a regional stratigraphic marker - Yu Zhang; Hua Yang; Duoyun Wang; Jinhua Fu; Bushe Xin; Bo Zuo (Arabian Journal of Geosciences, 2014)

Gene expression profiles of arabidopsis under the stress of methyl viologen: a microarray analysis - Hong-Juan Han; Ri-He Peng; Bo Zhu; Xiao-Yan Fu; Wei Zhao; Biao Shi; Quan-Hong Yao (Molecular Biology Reports, 2014)

Expression, purification, and characterization of recombinant mangrove glutamine synthetase - Wei Zhao; Jun Yang; Yongsheng Tian; Xiaoyan Fu; Bo Zhu; Yong Xue; Jianjie Gao; Hong-Juan Han; Rihe Peng; Quan-Hong Yao (Molecular Biology Reports, 2014)

Synthesis and cytotoxic activities of novel bergenin derivatives - Na-Na Liu; Fu-Kai Bao; Jing-Bo Chen; Xiang-Hui Zeng; Shui-Jing Chi; Jian-Ping Liu (Medicinal Chemistry Research, 2014)

Identification and characterization of a novel phage display-derived peptide with affinity for human brain metastatic breast cancer - Bo Fu; Ying Zhang; Wei Long; Aifeng Zhang; Yafen Zhang; Yanli An; Fengqin Miao; Fang Nie; Mingli Li; Youji He; Jianqiong Zhang; Gaojun Teng (Biotechnology Letters, 2014)

Accumulation of FLT3+ CD11c+ dendritic cells in psoriatic lesions and the anti-psoriatic effect of a selective FLT3 inhibitor - Heng-Xiu Yan; Wei-Wei Li; Yan Zhang; Xia-Wei Wei; Li-Xin Fu; Guo-Bo Shen; Tao Yin; Xiu-Ying Li; Hua-Shan Shi; Yang Wan; Qing-Yin Zhang; Jiong Li; et al. (Immunologic Research, 2014)

Ectopic expression of Dendrobium EREB5 gene in Arabidopsis influences leaf morphology - Yuqiang Sun; Ying Shen; Anna Li; Wenfeng Fu; Yu Wang; Qicai Ying; Juan Hao; Brian Jones; Bo Shen; Huizhong Wang (In Vitro Cellular & Developmental Biology - Plant, 2014)

RETRACTED ARTICLE: Genetic polymorphisms in VDR, ESR1 and ESR2 genes may contribute to susceptibility to Parkinson’s disease: a meta-analysis - Zhan Gao; Hong-Juan Fu; Ju-Jun Xue; Zhi-Xuan Wu; Li-Bo Zhao (Molecular Biology Reports, 2014)

Levels of BNP and Stress Blood Glucose in Acute Coronary Syndrome Patients and Their Relationships with the Severity of Coronary Artery Lesion - Peng Wei; Hai-bo Wang; Qiang Fu; Jie Bai; Qi Zhu (Cell Biochemistry and Biophysics, 2014)

Sources and flows of embodied CO2 emissions in import and export trade of China - Yanmei Li; Jiafeng Fu; Zhanyun Ma; Bo Yang (Chinese Geographical Science, 2014)

Primordial follicle assembly was regulated by notch signaling pathway in the mice - Chun-Lei Chen; Xia-Fei Fu; Lin-Qing Wang; Jun-Jie Wang; Hua-Gang Ma; Shun-Feng Cheng; Zhu-Mei Hou; Jin-Mei Ma; Guo-Bo Quan; Wei Shen; Lan Li (Molecular Biology Reports, 2014)

Uptake and recovery of soil nitrogen by bryophytes and vascular plants in an alpine meadow - Jin-niu Wang; Fu-sun Shi; Bo Xu; Qian Wang; Yan Wu; Ning Wu (Journal of Mountain Science, 2014)

Screening of multi-copy mannanase recombinants of Pichia pastoris based on colony size - Jia Zheng; Ning Guo; Fu-lai Lin; Li-shuang Wu; Hong-bo Zhou (World Journal of Microbiology and Biotechnology, 2014)

Molecular Cloning and Characterization of a Trichome-Specific Promoter of Artemisinic Aldehyde Δ11(13) Reductase (DBR2) in Artemisia annua - Weimin Jiang; Xu Lu; Bo Qiu; Fangyuan Zhang; Qian Shen; Zongyou Lv; Xueqing Fu; Tingxiang Yan; Erdi Gao; Mengmeng Zhu; Lingxian Chen; Ling Zhang; et al. (Plant Molecular Biology Reporter, 2014)

Occurrence and reactivation of viable but non-culturable E. coli in sewage sludge after mesophilic and thermophilic anaerobic digestion - Bo Fu; Qian Jiang; Hongbo Liu; He Liu (Biotechnology Letters, 2014)

Alda-1 reduces cerebral ischemia/reperfusion injury in rat through clearance of reactive aldehydes - Si-Hai Fu; Hong-Feng Zhang; Zhong-Bao Yang; Ting-Bo Li; Bin Liu; Zheng Lou; Qi-Lin Ma; Xiu-Ju Luo; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Genetic variation in alkaloid accumulation in leaves of Nicotiana - Bo Sun; Fen Zhang; Guo-jun Zhou; Guo-hai Chu; Fang-fang Huang; Qiao-mei Wang; Li-feng Jin; Fu-cheng Lin; Jun Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Verapamil Reverses Myocardial No-Reflow After Primary Percutaneous Coronary Intervention in Patients with Acute Myocardial Infarction - Qiang Fu; Wen Lu; Yi-jie Huang; Qiang Wu; Lin-guang Wang; Hai-bo Wang; Shu-zhong Jiang; Yan-jiong Wang (Cell Biochemistry and Biophysics, 2013)

Association of Serum Calcium and Hypertension Among Adolescents Aged 12–17 Years in the Rural Area of Northeast China - Hao Sun; Jingpu Shi; Hailong Wang; Lingyu Fu; Bo Zhou; Xiaomei Wu; Wei Dong; Hui Li; Wenli Wang (Biological Trace Element Research, 2013)

Microsatellite-based analysis of genetic diversity in 91 commercial Brassica oleracea L. cultivars belonging to six varietal groups - Nur Kholilatul Izzah; Jonghoon Lee; Sampath Perumal; Jee Young Park; Kyounggu Ahn; Donghui Fu; Goon-Bo Kim; Young-Woo Nam; Tae-Jin Yang (Genetic Resources and Crop Evolution, 2013)

Expression of exoinulinase genes in Saccharomyces cerevisiae to improve ethanol production from inulin sources - Bo Yuan; Shi-An Wang; Fu-Li Li (Biotechnology Letters, 2013)

Factors underlying the association of body mass index with serum ALT in Chinese hypertensive adults without known hepatic diseases - Yan Zhang; Xian-hui Qin; Jian-ping Li; Yi-min Cui; Ze-yuan Liu; Zhi-gang Zhao; Jun-bo Ge; De-ming Guan; Jian Hu; Yan-ni Wang; Fu-min Zhang; Xin Xu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Developmental expression and possible functional roles of mouse Nlrp4e in preimplantation embryos - Bo-hao Chang; Xu Liu; Jun Liu; Fu-sheng Quan; Ze-kun Guo; Yong Zhang (In Vitro Cellular & Developmental Biology - Animal, 2013)

Overexpression of TFAM Protects 3T3-L1 Adipocytes from NYGGF4 (PID1) Overexpression-Induced Insulin Resistance and Mitochondrial Dysfunction - Chun-Mei Shi; Guang-Feng Xu; Lei Yang; Zi-Yi Fu; Ling Chen; Hai-Long Fu; Ya-Hui Shen; Lu Zhu; Chen-Bo Ji; Xi-Rong Guo (Cell Biochemistry and Biophysics, 2013)

RP105 involved in activation of mouse macrophages via TLR2 and TLR4 signaling - Bo Liu; Naisheng Zhang; Zhicheng Liu; Yunhe Fu; Shuang Feng; Shan Wang; Yongguo Cao; Depeng Li; Dejie Liang; Fengyang Li; Xiaojing Song; Zhengtao Yang (Molecular and Cellular Biochemistry, 2013)

Investigation of the relationship between chromobox homolog 8 and nucleus pulposus cells degeneration in rat intervertebral disc - Xu Zhou; Hai-Long Zhang; Guang-Fei Gu; Yue Ding; Jian-Bo Jia; Qing-Song Fu; Shi-Sheng He (In Vitro Cellular & Developmental Biology - Animal, 2013)

Preparation and evaluation of a new releasable PEGylated tumor necrosis factor-α (TNF-α) conjugate for therapeutic application - ChuanYun Dai; Ya Fu; ShaoCheng Chen; Biao Li; Bo Yao; WanHong Liu; LiQing Zhu; Nan Chen; Ji Chen; Qiang Zhang (Science China Life Sciences, 2013)

Comparative transcriptome analysis of tobacco (Nicotiana tabacum) leaves to identify aroma compound-related genes expressed in different cultivated regions - Bo Lei; Xue-Hua Zhao; Kai Zhang; Jie Zhang; Wei Ren; Zhu Ren; Yi Chen; Hui-Na Zhao; Wen-Jie Pan; Wei Chen; Hong-Xun Li; Wen-Ya Deng; et al. (Molecular Biology Reports, 2013)

Exon 47 skipping of fibrillin-1 leads preferentially to cardiovascular defects in patients with thoracic aortic aneurysms and dissections - Wen-Jing Wang; Peili Han; Jun Zheng; Fang-Yuan Hu; Yun Zhu; Jin-Sheng Xie; Jian Guo; Zhe Zhang; Jie Dong; Gu-Yan Zheng; Huiqing Cao; Tian-Shu Liu; et al. (Journal of Molecular Medicine, 2013)

Endothelial progenitor cells: the promise of cell-based therapies for acute lung injury - Mei Mao; Xilin Xu; Yong Zhang; Bo Zhang; Zu-hong Fu (Inflammation Research, 2013)

Salidroside attenuates inflammatory responses by suppressing nuclear factor-κB and mitogen activated protein kinases activation in lipopolysaccharide-induced mastitis in mice - Depeng Li; Yunhe Fu; Wen Zhang; Gaoli Su; Bo Liu; Mengyao Guo; Fengyang Li; Dejie Liang; Zhicheng Liu; Xichen Zhang; Yongguo Cao; Naisheng Zhang; et al. (Inflammation Research, 2013)

Optimization of fermentation process for the production of intracellular polysaccharide from Paecilomyces cicadae and the immuno-stimulating activity of intracellular polysaccharide - Jun-Wen Cheng; Yan-Bin Wang; Liang He; Hua Qian; Li-Zhong Fu; Hai-Bo Li (World Journal of Microbiology and Biotechnology, 2012)

Quantitative assessment of the associations between four polymorphisms (FokI, ApaI, BsmI, TaqI) of vitamin D receptor gene and risk of diabetes mellitus - Qijuan Wang; Bo Xi; Kathleen Heather Reilly; Man Liu; Maosun Fu (Molecular Biology Reports, 2012)

Sprout vacuum-infiltration: a simple and efficient agroinoculation method for virus-induced gene silencing in diverse solanaceous species - Hua-xue Yan; Da-qi Fu; Ben-zhong Zhu; Hai-ping Liu; Xiao-ying Shen; Yun-bo Luo (Plant Cell Reports, 2012)

Effects of fertilization and drought stress on tannin biosynthesis of Casuarina equisetifolia seedlings branchlets - Li Hua Zhang; Hong Bo Shao; Gong Fu Ye; Yi Ming Lin (Acta Physiologiae Plantarum, 2012)

Anomalous temperature–growth response of Abies faxoniana to sustained freezing stress along elevational gradients in China’s Western Sichuan Province - Zong Shan Li; Guo Hua Liu; Bo Jie Fu; Chan Juan Hu; Shu Zheng Luo; Xing Liang Liu; Fei He (Trees, 2012)

Partial antiviral activities of the Asn631 chicken Mx against newcastle disease virus and vesicular stomatitis virus - Bichun Li; Dezhi Fu; Yani Zhang; Qi Xu; Ligang Ni; Guobin Chang; Mengmeng Zheng; Bo Gao; Huaichang Sun; Guohong Chen (Molecular Biology Reports, 2012)

Analysis of 2,297 expressed sequence tags (ESTs) from a cDNA library of flax (Linum ustitatissimum L.) bark tissue - Song-Hua Long; Xin Deng; Yu-Fu Wang; Xiang Li; Rui-Qing Qiao; Cai-Sheng Qiu; Yuan Guo; Dong-Mei Hao; Wan-Qi Jia; Xin-Bo Chen (Molecular Biology Reports, 2012)

Spontaneous retroperitoneal hemorrhage after hemodialysis involving anticoagulant agents - Wen-xing Fan; Zheng-xu Deng; Fang Liu; Rong-bo Liu; Ling He; Bogati Amrit; Li Zang; Jing-wen Li; Xian-rong Liu; Song-min Huang; Ping Fu (Journal of Zhejiang University-SCIENCE B, 2012)

Analysis of gene expression profile of Arabidopsis genes under trichloroethylene stresses with the use of a full-length cDNA microarray - Bo Zhu; Ri-He Peng; Ai-Sheng Xiong; Xiao-Yan Fu; Wei Zhao; Yong-Sheng Tian; Xiao-Fen Jin; Yong Xue; Jing Xu; Hong-Juan Han; Chen Chen; Jian-Jie Gao; et al. (Molecular Biology Reports, 2012)

Identification of microRNA-like RNAs in a plant pathogenic fungus Sclerotinia sclerotiorum by high-throughput sequencing - Jiahong Zhou; Yanping Fu; Jiatao Xie; Bo Li; Daohong Jiang; Guoqing Li; Jiasen Cheng (Molecular Genetics and Genomics, 2012)

An Accurate Method of Computing the Gradient of Seismic Wave Reflection Coefficients (SWRCs) for the Inversion of Stratum Parameters - Xiao-Bo Liu; Fu-Ping Liu; Xian-Jun Meng; Jia-Qi Xiao (Surveys in Geophysics, 2012)

Stress responses to phenol in Arabidopsis and transcriptional changes revealed by microarray analysis - Jing Xu; Zhen-Hong Su; Chen Chen; Hong-Juan Han; Bo Zhu; Xiao-Yan Fu; Wei Zhao; Xiao-Fen Jin; Ai-Zhong Wu; Quan-Hong Yao (Planta, 2012)

Overexpression of a vacuolar H+-pyrophosphatase and a B subunit of H+-ATPase cloned from the halophyte Halostachys caspica improves salt tolerance in Arabidopsis thaliana - You-zhen Hu; You-ling Zeng; Bo Guan; Fu-chun Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Construction and characterization of a normalized cDNA library from the river snail Bellamya aeruginosa after exposure to copper - Zi-Cheng Li; Li-Hui An; Qing Fu; Ying Liu; Lei Zhang; Hao Chen; Xing-Ru Zhao; Li-Jing Wang; Bing-Hui Zheng; Lin-Bo Zhang (Ecotoxicology, 2012)

Clinical Study of Autologous Cytokine-Induced Killer Cells for the Treatment of Elderly Patients with Diffuse Large B-Cell Lymphoma - Xue-chun Lu; Bo Yang; Rui-li Yu; Xiao-hua Chi; Shuai Tuo; Chao-wei Tuo; Hong-li Zhu; Yao Wang; Chao-guang Jiang; Xiao-bing Fu; Yang Yang; Yang Liu; et al. (Cell Biochemistry and Biophysics, 2012)

The Potential Influence of Seasonal Climate Variables on the Net Primary Production of Forests in Eastern China - Zong Shan Li; Guo Hua Liu; Bo Jie Fu; Jin Long Zhang (Environmental Management, 2011)

Analysis of variable sites between two complete South China tiger (Panthera tigris amoyensis) mitochondrial genomes - Wenping Zhang; Bisong Yue; Xiaofang Wang; Xiuyue Zhang; Zhong Xie; Nonglin Liu; Wenyuan Fu; Yaohua Yuan; Daqing Chen; Danghua Fu; Bo Zhao; Yuzhong Yin; et al. (Molecular Biology Reports, 2011)

Molecular epidemiology of norovirus gastroenteritis in children in Jiangmen, China, 2005–2007 - Ying-chun Dai; Gui-fang Hu; Xu-fu Zhang; Can-lei Song; Wen-long Xiang; Xian-bo Wu; Le-yi Wang; Xi Jiang; Jun Nie (Archives of Virology, 2011)

Identification of a Novel Bacterial K+ Channel - Guanghua Tang; Bo Jiang; Yuan Huang; Ming Fu; Lingyun Wu; Rui Wang (The Journal of Membrane Biology, 2011)

A double-blind, placebo-controlled study of traditional Chinese medicine sarsasapogenin added to risperidone in patients with negative symptoms dominated schizophrenia - Shi-Fu Xiao; Hai-Bo Xue; Xia Li; Chao Chen; Guan-Jun Li; Cheng-Mei Yuan; Ming-Yuan Zhang (Neuroscience Bulletin, 2011)

A model of BmK CT in inhibiting glioma cell migration via matrix metalloproteinase-2 from experimental and molecular dynamics simulation study - Yue-Jun Fu; Na An; Kok-Gan Chan; Yan-Bo Wu; Shu-Hua Zheng; Ai-Hua Liang (Biotechnology Letters, 2011)

Molecular characterisation of cereal cyst nematodes in winter wheat on the Huang-Huai floodplain of China using RFLP and rDNA-ITS sequence analyses - Bo Fu; Hong-xia Yuan; Yu Zhang; Xing-song Hou; Gao-lei Nian; Peng Zhang; Xiao-ping Xing; Bing-jian Sun; Ian T. Riley; Hong-lian Li (Australasian Plant Pathology, 2011)

COD removal from expanded granular sludge bed effluent using a moving bed biofilm reactor and their microbial community analysis - Bo Fu; Xiaoyi Liao; Rui Liang; Lili Ding; Ke Xu; Hongqiang Ren (World Journal of Microbiology and Biotechnology, 2011)

Significant association of SNP rs2106261 in the ZFHX3 gene with atrial fibrillation in a Chinese Han GeneID population - Cong Li; Fan Wang; Yanzong Yang; Fenfen Fu; Chengqi Xu; Lisong Shi; Sisi Li; Yunlong Xia; Gang Wu; Xiang Cheng; Hui Liu; Chuchu Wang; et al. (Human Genetics, 2011)

Gastric duplication cyst lined by pseudostratified columnar ciliated epithelium: a case report and literature review - Wu Jiang; Bo Zhang; Yan-biao Fu; Jia-wei Wang; Shun-liang Gao; Su-zhan Zhang; Yu-lian Wu (Journal of Zhejiang University-SCIENCE B, 2011)

Identification of differentially expressed transcripts involved in the salt-stress response of Salsola ferganica by suppression subtractive hybridization - Bo Guan; Gang-qiang Jiang; Ying-xin Wang; Zhi-cai Wang; Yakupjan Haxim; Qian Bao; You-zhen Hu; Fu-chun Zhang; Yan Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Characterization of microbial community in an aerobic moving bed biofilm reactor applied for simultaneous nitrification and denitrification - Bo Fu; Xiaoyi Liao; Lili Ding; Hongqiang Ren (World Journal of Microbiology and Biotechnology, 2010)

Erratum to: AtCPK6, a functionally redundant and positive regulator involved in salt/drought stress tolerance in Arabidopsis - Jing Xu; Yong-Sheng Tian; Ri-He Peng; Ai-Sheng Xiong; Bo Zhu; Xiao-Fen Jin; Feng Gao; Xiao-Yan Fu; Xi-Lin Hou; Quan-Hong Yao (Planta, 2010)

Endemic Seed Plant Species from Hainan Island: A Checklist - Javier Francisco-Ortega; Fa-Guo Wang; Zhong-Sheng Wang; Fu-Wu Xing; Hong Liu; Han Xu; Wei-Xiang Xu; Yi-Bo Luo; Xi-Qiang Song; Stephan Gale; David E. Boufford; Mike Maunder; et al. (The Botanical Review, 2010)

Seed Plant Endemism on Hainan Island: A Framework for Conservation Actions - Javier Francisco-Ortega; Zhong-Sheng Wang; Fa-Guo Wang; Fu-Wu Xing; Hong Liu; Han Xu; Wei-Xiang Xu; Yi-Bo Luo; Xi-Qiang Song; Stephan Gale; David E. Boufford; Mike Maunder; et al. (The Botanical Review, 2010)

Population variation of invasive Spartina alterniflora can differentiate bacterial diversity in its rhizosphere - Ming Nie; Le Xuan Gao; Jun Hong Yan; Xiao Hua Fu; Ming Xiao; Ji Yang; Bo Li (Plant Ecology, 2010)

Analysis of Brassica rapa ESTs: gene discovery and expression patterns of AP2/ERF family genes - Jing Zhuang; Ai-Sheng Xiong; Ri-He Peng; Feng Gao; Bo Zhu; Jian Zhang; Xiao-Yan Fu; Xiao-Feng Jin; Jian-Min Chen; Zhen Zhang; Yu-Shan Qiao; Quan-Hong Yao (Molecular Biology Reports, 2010)

AtCPK6, a functionally redundant and positive regulator involved in salt/drought stress tolerance in Arabidopsis - Jing Xu; Yong-Sheng Tian; Ri-He Peng; Ai-Sheng Xiong; Bo Zhu; Xiao-Fen Jin; Feng Gao; Xiao-Yan Fu; Xi-Lin Hou; Quan-Hong Yao (Planta, 2010)

Evaluation of genetic diversity in Lentinula edodes strains using RAPD, ISSR and SRAP markers - Li-Zhong Fu; Hong-Yu Zhang; Xue-Qian Wu; Hai-Bo Li; Hai-Long Wei; Qing-Qi Wu; Li-An Wang (World Journal of Microbiology and Biotechnology, 2010)

Chloroplast transformation of rapeseed (Brassica napus) by particle bombardment of cotyledons - Lin Cheng; He-Ping Li; Bo Qu; Tao Huang; Jin-Xing Tu; Ting-Dong Fu; Yu-Cai Liao (Plant Cell Reports, 2010)

Dynamic routing modeling for flash flood forecast in river system - Wen-Cheng Liu; Wei-Bo Chen; Ming-Hsi Hsu; Jin-Cheng Fu (Natural Hazards, 2010)

Molecular characterization, expression profile and association analysis with fat deposition traits of the porcine APOM gene - Gang Pan; Yayuan Fu; Bo Zuo; Zhuqing Ren; Dequan Xu; Minggang Lei; Rong Zheng; Yuan-Zhu Xiong (Molecular Biology Reports, 2010)

Effects of moniliformin and selenium on human articular cartilage metabolism and their potential relationships to the pathogenesis of Kashin-Beck disease - An Zhang; Jun-ling Cao; Bo Yang; Jing-hong Chen; Zeng-tie Zhang; Si-yuan Li; Qiang Fu; Clare E. Hugnes; Bruce Caterson (Journal of Zhejiang University-SCIENCE B, 2010)

Pancreatic somatostatinoma with obscure inhibitory syndrome and mixed pathological pattern - Bo Zhang; Qiu-ping Xie; Shun-liang Gao; Yan-biao Fu; Yu-lian Wu (Journal of Zhejiang University-SCIENCE B, 2010)

Tetrahydroxy stilbene glucoside reduces the cognitive impairment and overexpression of amyloid precursor protein induced by aluminum exposure - Hong-Bo Luo; Jin-Sheng Yang; Xiang-Qun Shi; Xue-Feng Fu; Qi-Dong Yang (Neuroscience Bulletin, 2009)

Two new species of Stemphylium from Northwest China - Yong Wang; Hong-Bo Fu; Nichole R. O’Neill; Xiu-Guo Zhang (Mycological Progress, 2009)

A revised method of presenting wavenumber–frequency power spectrum diagrams that reveals the asymmetric nature of tropical large-scale waves - Winston C. Chao; Bo Yang; Xiouhua Fu (Climate Dynamics, 2009)

Combined Effects of Repeated Administration of 2,3,7,8-Tetrachlorodibenzo-p-dioxin and Polychlorinated Biphenyls on Kidneys of Male Rats - Chun-Feng Lu; Yi-Mei Wang; Shuang-Qing Peng; Li-Bo Zou; De-Hong Tan; Gang Liu; Ze Fu; Qiao-Xu Wang; Jing Zhao (Archives of Environmental Contamination and Toxicology, 2009)

Effects of proteinase a on cultivation and viability characteristics of industrial Saccharomyces cerevisiae WZ65 - Hong-bo Zhang; Hai-feng Zhang; Qi-he Chen; Hui Ruan; Ming-liang Fu; Guo-qing He (Journal of Zhejiang University-SCIENCE B, 2009)

An investigation of vitamin B12 deficiency in elderly inpatients in neurology department - Yu-Hui Wang; Fang Yan; Wen-Bo Zhang; Gang Ye; Yun-Yun Zheng; Xu-Hua Zhang; Fu-Yuan Shao (Neuroscience Bulletin, 2009)

Gender difference in the effect of daytime sleep on declarative memory for pictures - Bo Wang; Xiao-lan Fu (Journal of Zhejiang University-SCIENCE B, 2009)

Protective effect of DNA-mediated immunization with liposome-encapsulated GRA4 against infection of Toxoplasma gondii - Rui Chen; Shao-hong Lu; Qun-bo Tong; Di Lou; Dong-yan Shi; Bing-bing Jia; Guo-ping Huang; Jin-fu Wang (Journal of Zhejiang University-SCIENCE B, 2009)

Cloning and characterization of phosphorus starvation inducible Brassica napus PURPLE ACID PHOSPHATASE 12 gene family, and imprinting of a recently evolved MITE-minisatellite twin structure - Kun Lu; You-Rong Chai; Kai Zhang; Rui Wang; Li Chen; Bo Lei; Jun Lu; Xin-Fu Xu; Jia-Na Li (Theoretical and Applied Genetics, 2008)

Construction of recombinant industrial Saccharomyces cerevisiae strain with bglS gene insertion into PEP4 locus by homologous recombination - Qiang Zhang; Qi-he Chen; Ming-liang Fu; Jin-ling Wang; Hong-bo Zhang; Guo-qing He (Journal of Zhejiang University-SCIENCE B, 2008)

Aldehyde volatiles emitted in succession from mechanically damaged leaves of poplar cuttings - Zeng-hui Hu; Ying-bai Shen; You-qing Luo; Fan-yi Shen; Hai-bo Gao; Rong-fu Gao (Journal of Plant Biology, 2008)

Identification of the distinct promoters for the two transcripts of apoptosis related protein 3 and their transcriptional regulation by NFAT and NFκB - Guodong Yang; Fang Yu; Haiyan Fu; Fan Lu; Bo Huang; Liyuan Bai; Zhongliang Zhao; Libo Yao; Zifan Lu (Molecular and Cellular Biochemistry, 2007)

Edaravone neuroprotection effected by suppressing the gene expression of the Fas signal pathway following transient focal ischemia in rats - Bo Xiao; Fang -Fang Bi; Yue -Qiang Hu; Fa -Fa Tian; Zhi -Guo Wu; Hadi M. Mujlli; Ling Ding; Xin -Fu Zhou (Neurotoxicity Research, 2007)

Isolation of a strain of Acidithiobacillus caldus and its role in bioleaching of chalcopyrite - Qiu Guan Zhou; Fu Bo; Zhou Hong Bo; Liu Xi; Gao Jian; Liu Fei Fei; Chen Xin Hua (World Journal of Microbiology and Biotechnology, 2007)

Identification of the distinct promoters for the two transcripts of apoptosis related protein 3 and their transcriptional regulation by NFAT and NFκB - Guodong Yang; Fang Yu; Haiyan Fu; Fan Lu; Bo Huang; Liyuan Bai; Zhongliang Zhao; Libo Yao; Zifan Lu (Molecular and Cellular Biochemistry, 2007)

Sustainability Evaluation of the Grain for Green Project: From Local People’s Responses to Ecological Effectiveness in Wolong Nature Reserve - Jian-Ying Xu; Li-Ding Chen; Yi-He Lu; Bo-Jie Fu (Environmental Management, 2007)

Relationships between O isotope equilibrium, mineral alteration and Rb–Sr chronometric validity in granitoids: implications for determination of cooling rate - Jiang Feng Chen; Yong-Fei Zheng; Zi-Fu Zhao; Bo Li; Zhi Xie; Bing Gong; Hui Qian (Contributions to Mineralogy and Petrology, 2007)

The displacement computation and construction pre-control of a foundation pit in Shanghai utilizing FEM and intelligent methods - You-Liang Chen; Rafig Azzam; Fu-Bo Zhang (Geotechnical and Geological Engineering, 2006)

Purification and Characterization of a Cold-active Iron Superoxide Dismutase from a Psychrophilic Bacterium, Marinomonas sp. NJ522 - Zhou Zheng; Ying-Hui Jiang; Jin-Lai Miao; Quan-Fu Wang; Bo-Tao Zhang; Guang-You Li (Biotechnology Letters, 2006)

Controllable Regioselective Acylation of Rutin Catalyzed by Enzymes in Non-aqueous Solvents - Yong-mei Xiao; Qi Wu; Wei-bo Wu; Qing-yi Zhang; Xian-fu Lin (Biotechnology Letters, 2005)

Activation of gelatinases by fibrin is PA/plasmin system-dependent in human glomerular endothelial cells - Guangyan Cai; Xiangmei Chen; Bo Fu; Yang Lu (Molecular and Cellular Biochemistry, 2005)

Regioselective Enzymatic Synthesis of Non-Steroidal Anti-Inflammatory Drugs Containing Glucose in Organic Media - Na Wang; Bo Kai Liu; Qi Wu; Jun Liang Wang; Xian Fu Lin (Biotechnology Letters, 2005)

Regioselective enzymatic acylation of ribavirin to give potential multifunctional derivatives - Bo-Kai Liu; Na Wang; Qi Wu; Chuan-Ying Xie; Xian-Fu Lin (Biotechnology Letters, 2005)

Eco-hydrological effects of landscape pattern change - Bo-Jie Fu; Wen-Wu Zhao; Li-Ding Chen; Zhan-Feng Liu; Yi-He Lü (Landscape and Ecological Engineering, 2005)

Paragonimus skrjabini Chen, 1959 (Digenea: Paragonimidae) and related species in eastern Asia: a combined molecular and morphological approach to identification and taxonomy - David Blair; Chang Zhengshan; Chen Minggang; Cui Aili; Wu Bo; Takeshi Agatsuma; Moritoshi Iwagami; David Corlis; Fu Chengbin; Zhan Ximei (Systematic Parasitology, 2005)

Study on the framework system of digital agriculture - Yong Liang; Xiu-shan Lu; De-gui Zhang; Fu Liang; Zhi-bo Ren (Chinese Geographical Science, 2003)

Finding spatial regularity in mosaic landscapes: two methods integrated - Ke-Ming Ma; Bo-Jie Fu; Xu-Dong Guo; Hua-Feng Zhou (Plant Ecology, 2000)